Composition containing inorganic solid electrolyte, sheet for all-solid-state secondary battery, secondary battery, and method for producing the same
By using a combination of an inorganic solid electrolyte and a low adsorption rate polymer binder in the constituent layer of an all-solid secondary battery, the dispersion and fluidity of the solid particle material are solved, and the high cycle characteristics and low resistance constituent layer of the battery are achieved.
Patent Information
- Application Number
- CN202080060605.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-05-21
- Filing Date
- 2020-08-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-08-17
AI Technical Summary
In an all-solid secondary battery, it is necessary to stably maintain excellent dispersion and fluidity of the solid particle material in the constituent layer forming material, and at the same time have good surface properties to improve battery performance, especially circulation characteristics.
By using the inorganic solid electrolyte in combination with a polymer binder showing an adsorption rate of less than 60% to the inorganic solid electrolyte, the recondensation or precipitation of the inorganic solid electrolyte is inhibited and the increase of viscosity is controlled, thereby forming a composition with excellent dispersion stability and handling properties.
The flat surface properties and low resistance of the constituent layer are achieved, the cycle characteristics and high conductivity of all-solid-state secondary batteries are improved, the life of the battery is extended and its applicability in high-performance applications.
Smart Images

Figure CN114303258B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a composition containing an inorganic solid electrolyte, a sheet material for an all-solid-state secondary battery, an all-solid-state secondary battery, and a method for manufacturing the sheet material for an all-solid-state secondary battery and the all-solid-state secondary battery. Background Art
[0002] In all-solid-state secondary batteries, all negative electrodes, electrolytes, and positive electrodes are made of solids, which can greatly improve the safety or reliability of batteries using organic electrolytes as a subject. And it can also extend the life. In addition, all-solid-state secondary batteries can be set as a structure in which electrodes and electrolytes are directly arranged and configured in series. Therefore, compared with secondary batteries using organic electrolytes, it can become high energy density, and it is expected to be applied to electric vehicles or large batteries.
[0003] In this all-solid-state secondary battery, as the material forming the constituent layer (solid electrolyte layer, negative electrode active material layer and positive electrode active material layer), inorganic solid electrolytes, active materials, etc. can be cited. The inorganic solid electrolyte, especially oxide-based inorganic solid electrolytes and sulfide-based inorganic solid electrolytes, have been expected in recent years as electrolyte materials with high ion conductivity close to that of organic electrolytes.
[0004] As a material (constituent layer forming material) forming a constituent layer of an all-solid-state secondary battery, a material containing the above-mentioned inorganic solid electrolyte and the like is proposed. For example, Patent Document 1 describes a solid electrolyte composition comprising an inorganic solid electrolyte (A) having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, an average particle size of a binder particle (B) of 10 nm or more and 1,000 nm or less composed of a polymer in which a macromolecular monomer (X) having a number average molecular weight of 1,000 or more is incorporated as a side chain component, and a dispersion medium (C). In addition, Patent Document 2 describes a solid electrolyte composition containing an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and a polymer binder, wherein the polymer binder is composed of a polymer having a hard segment and a soft segment.
[0005] Previous technical literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-088486
[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-088480 Summary of the invention
[0009] Technical issues to be solved by the invention
[0010] When the constituent layer of an all-solid-state secondary battery is formed by solid particle materials (inorganic solid electrolytes, active materials, conductive additives, etc.), in the constituent layer forming material, from the viewpoint of improving the battery performance (such as cycle characteristics) of the all-solid-state secondary battery with the constituent layer thus formed, it is required to stably maintain the solid particle material (also referred to as solid particles) just after preparation. Excellent dispersibility characteristics (dispersion stability) and having appropriate viscosity to maintain excellent dispersion characteristics and good surface properties (handling properties). Dispersion stability and handling properties are considered to be one of the important factors of the correlation between inorganic solid electrolytes and adhesives. However, the solid electrolyte composition described in patent documents 1 and 2 does not describe this viewpoint.
[0011] However, in recent years, the research and development of high performance and practical application of electric vehicles has progressed rapidly, and the requirements for battery performance (e.g., cycle characteristics) required for all-solid-state secondary batteries have become increasingly high. In order to meet such requirements in recent years, it is necessary to develop a constituent layer forming material that has both dispersion stability and handling properties (fluidity, surface properties of the coating surface) at a higher level.
[0012] The present invention aims to provide a composition containing an inorganic solid electrolyte with excellent dispersion stability and handling properties. In addition, the present invention aims to provide a sheet material for an all-solid-state secondary battery and an all-solid-state secondary battery using the composition containing an inorganic solid electrolyte, and a method for manufacturing the sheet material for an all-solid-state secondary battery and the all-solid-state secondary battery.
[0013] Means for solving technical problems
[0014] The inventors of the present invention have repeatedly conducted various studies focusing on the correlation between inorganic solid electrolytes and adhesives, and have found that in order to suppress the re-agglomeration or precipitation caused by the inorganic solid electrolyte over time in a composition containing an inorganic solid electrolyte, and to suppress the excessive increase in viscosity (thickening) by combining an inorganic solid electrolyte with a polymer adhesive having an adsorption rate of less than 60% for the inorganic solid electrolyte. Therefore, by using the composition containing an inorganic solid electrolyte as a constituent layer forming material, it is found that a sheet for an all-solid-state secondary battery with a flat coating surface and good surface properties and a low-resistance constituent layer, as well as an all-solid-state secondary battery with excellent cycle characteristics, can be achieved. The present invention has been further repeatedly studied based on these insights, thereby completing the present invention.
[0015] That is, the above-mentioned problems are solved by the following means.
[0016] <1> A composition containing an inorganic solid electrolyte, comprising an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a polymer binder, and a dispersion medium, wherein:
[0017] The polymer binder includes a polymer binder having an adsorption rate of less than 60% with respect to the inorganic solid electrolyte in the dispersion medium.
[0018] <2> The composition containing an inorganic solid electrolyte according to <1>, wherein
[0019] The polymer binder having an adsorption rate of less than 60% is dissolved in the dispersion medium.
[0020] <3> The composition containing an inorganic solid electrolyte according to <1> or <2>, wherein
[0021] The difference in SP value between the polymer forming the polymer binder having an adsorption rate of less than 60% and the dispersion medium is 3 or less.
[0022] <4> The composition containing an inorganic solid electrolyte according to any one of <1> to <3>, wherein
[0023] The polymer forming the polymer binder having an adsorption rate of less than 60% contains a constituent component having a functional group selected from the following functional group group (a).
[0024] <Functional group (a)>
[0025] Hydroxyl, amino, carboxyl, sulfone, phosphoric acid, phosphonic acid, sulfanyl, ether bond, imino, ester bond, amide bond, carbamate bond, urea bond, heterocyclic group, aromatic group, carboxylic anhydride group, fluoroalkyl group, siloxane group
[0026] <5> The inorganic solid electrolyte-containing composition according to <4>, wherein the content of the constituent component having a functional group selected from the functional group group (a) in the polymer forming the polymer binder is 0.01 to 50 mol %.
[0027] <6> The composition containing an inorganic solid electrolyte according to any one of <1> to <5>, wherein
[0028] The polymer forming the polymer binder having an adsorption rate of less than 60% has a constituent component represented by any one of the following formulae (1-1) to (1-5).
[0029] [Chemical formula 1]
[0030]
[0031] In the formula, R 1 represents a hydrogen atom or an alkyl group, R 2 represents a group having a hydrocarbon group having 4 or more carbon atoms, R 3It represents a linking group having a mass average molecular weight of 500 or more and 200,000 or less containing a polybutadiene chain or a polyisoprene chain.
[0032] <7> The composition containing an inorganic solid electrolyte according to any one of <1> to <6>, wherein
[0033] The polymer forming the polymer binder having an adsorption rate of less than 60% has a polymer chain having at least one bond selected from urethane bonds, urea bonds, amide bonds, imide bonds, and ester bonds, or a carbon-carbon double bond in the main chain.
[0034] <8> The composition containing an inorganic solid electrolyte according to any one of <1> to <7>, characterized in that:
[0035] The contact angle of the polymer forming the polymer binder having an adsorption rate of less than 60% with respect to the dispersion medium is 40 degrees or less.
[0036] <9> The composition containing an inorganic solid electrolyte according to any one of <6> to <8>, wherein
[0037] The invention comprises two or more polymer binders having an adsorption rate of less than 60%, wherein the polymer constituting at least one of the polymer binders is a hydrocarbon polymer.
[0038] <10> The composition containing an inorganic solid electrolyte according to any one of <1> to <9>, wherein
[0039] The polymer binder includes a particulate binder having an average particle size of 1 to 1000 nm.
[0040] <11> The inorganic solid electrolyte-containing composition according to any one of <1> to <10>, comprising an active material.
[0041] <12> The composition containing an inorganic solid electrolyte according to <11>, wherein
[0042] The polymer binder having an adsorption rate of less than 60% with respect to the active material has an adsorption rate of 90% or less.
[0043] <13> The composition containing an inorganic solid electrolyte according to <12>, wherein
[0044] The polymer binder having an adsorption rate of less than 60% has an adsorption rate of 90% or less with respect to the active material.
[0045] <14> The inorganic solid electrolyte-containing composition according to any one of <1> to <13>, further comprising a conductive auxiliary agent.
[0046] <15> The composition containing an inorganic solid electrolyte according to any one of <1> to <14>, wherein
[0047] The inorganic solid electrolyte is a sulfide-based inorganic solid electrolyte.
[0048] <16> A method for producing a sheet for an all-solid-state secondary battery, comprising forming a film of the composition containing an inorganic solid electrolyte according to any one of <1> to <15>.
[0049] <17> An all-solid-state secondary battery sheet having a layer formed by the method for producing an all-solid-state secondary battery sheet according to <16> above.
[0050] <18> A method for producing an all-solid-state secondary battery, comprising the method for producing an all-solid-state secondary battery sheet according to <16> above.
[0051] <19> An all-solid-state secondary battery comprising, in order, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein:
[0052] At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer formed by the method for producing an all-solid-state secondary battery sheet described in <16>.
[0053] Effects of the Invention
[0054] The present invention can provide a composition containing an inorganic solid electrolyte having excellent dispersion characteristics such as dispersion stability and handling properties (fluidity, surface properties). In addition, the present invention can provide a sheet material for an all-solid-state secondary battery and an all-solid-state secondary battery having a layer composed of the composition containing an inorganic solid electrolyte. In addition, the present invention can provide a sheet material for an all-solid-state secondary battery and a method for manufacturing an all-solid-state secondary battery using the composition containing an inorganic solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a longitudinal sectional view schematically showing an all-solid-state secondary battery according to a preferred embodiment of the present invention.
[0056] Figure 2 It is a longitudinal cross-sectional view schematically showing a button-type all-solid-state secondary battery produced in the example. DETAILED DESCRIPTION
[0057] In the present invention, the numerical range represented by "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0058] In the present invention, the term "compound" (for example, when the term "compound" is appended to the end) includes not only the compound itself but also its salts and ions, and includes derivatives in which a part is changed by introducing a substituent, etc., within the range that does not impair the effects of the present invention.
[0059] In the present invention, (meth)acrylic acid refers to one or both of acrylic acid and methacrylic acid. The same applies to (meth)acrylate.
[0060] In the present invention, regarding the substituent, linking group, etc. (hereinafter referred to as substituent, etc.) that is not clearly recorded as substituted or unsubstituted, it means that the group may also have a suitable substituent. Therefore, in the present invention, even if it is simply recorded as a YYY group, the YYY group further includes a mode with a substituent in addition to the mode without a substituent. This is also the same for compounds that are not clearly recorded as substituted or unsubstituted. As a preferred substituent, for example, the substituent Z described later can be cited.
[0061] In the present invention, when there are multiple substituents etc. represented by specific symbols or when multiple substituents etc. are specified simultaneously or selectively, it means that each substituent etc. may be the same or different from each other. Furthermore, even if there is no special description, when multiple substituents etc. are adjacent, it means that these may be linked or fused to each other to form a ring.
[0062] In the present invention, the polymer refers to a polymer, but has the same meaning as a so-called high molecular compound.
[0063] [Composition containing inorganic solid electrolyte]
[0064] The composition containing an inorganic solid electrolyte of the present invention contains an inorganic solid electrolyte having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a polymer binder, and a dispersion medium. The polymer binder contained in the composition containing an inorganic solid electrolyte includes one or more polymer binders (sometimes referred to as "low-adsorption binders") having an adsorption rate of less than 60% with respect to the inorganic solid electrolyte.
[0065] That is, the composition containing an inorganic solid electrolyte of the present invention may contain a low-adsorption binder as a polymer binder, and its containing state is not particularly limited. For example, in the composition containing an inorganic solid electrolyte, the low-adsorption binder may or may not be adsorbed on the inorganic solid electrolyte, and when adsorbed, the degree thereof may be within the range of the adsorption rate described below.
[0066] The low-adsorption binder functions as a binder that binds solid particles such as an inorganic solid electrolyte (in addition, active materials and conductive aids that can coexist) to each other (for example, inorganic solid electrolytes to each other, inorganic solid electrolytes and active materials, and active materials to each other) in a layer formed at least by a composition containing an inorganic solid electrolyte. In addition, it also functions as a binder that binds the collector and solid particles. In the composition containing an inorganic solid electrolyte, the low-adsorption binder may or may not have the function of bonding solid particles to each other.
[0067] The composition containing an inorganic solid electrolyte of the present invention is preferably a slurry in which an inorganic solid electrolyte is dispersed in a dispersion medium. In this case, the low-adsorption binder preferably has the function of dispersing solid particles in the dispersion medium. In addition, when the low-adsorption binder (in a solid state) is dispersed in the dispersion medium, a part of it can be dissolved in the dispersion medium within the range that does not impair the effect of the present invention.
[0068] The composition containing an inorganic solid electrolyte of the present invention has excellent dispersion stability and handling properties. By using the composition containing an inorganic solid electrolyte as a constituent layer forming material, a sheet for an all-solid-state secondary battery having a constituent layer with a flat surface and excellent surface properties and low resistance can be realized, and an all-solid-state secondary battery with excellent cycle characteristics can be realized.
[0069] In the embodiment in which the active material layer formed on the current collector is formed from the composition containing the inorganic solid electrolyte of the present invention, strong adhesion between the current collector and the active material layer can be achieved, and the cycle characteristics can be further improved.
[0070] The detailed reason is not clear, but it is believed to be as follows. That is, it is believed that the low-adsorption binder showing an adsorption rate of less than 60% with respect to the inorganic solid electrolyte is not excessively adsorbed to the inorganic solid electrolyte in the composition containing the inorganic solid electrolyte, and can suppress the re-aggregation or precipitation of the inorganic solid electrolyte not only immediately after the composition containing the inorganic solid electrolyte is prepared, but also after a period of time. As a result of the low-adsorption binder showing a correlation with such an adsorption state with respect to the inorganic solid electrolyte, it is possible to stably maintain a high degree of dispersibility (excellent dispersion stability) immediately after preparation, and also suppress excessive increase in viscosity and express good fluidity (excellent handling properties).
[0071] If the composition containing an inorganic solid electrolyte of the present invention showing such excellent dispersion characteristics is used to form a constituent layer, then even when the constituent layer is formed into a film (for example, when the composition containing an inorganic solid electrolyte is applied and when dried), the re-agglomerates or precipitates of the inorganic solid electrolyte can be suppressed. Thus, the deviation of the contact state between the inorganic solid electrolytes in the constituent layer can be suppressed. In particular, when the composition containing an inorganic solid electrolyte contains an active substance, etc., it is believed that specific particles such as active substances are not easy to be unevenly distributed in the constituent layer (solid particles are uniformly arranged in the constituent layer). As a result, the rise of the interface resistance between the solid particles and the resistance of the constituent layer can be suppressed. In addition, when the composition containing an inorganic solid electrolyte is formed into a film, especially when applied, the composition containing an inorganic solid electrolyte flows appropriately (smooth), and there is no concave and convex surface roughness caused by insufficient or excessive flow (excellent surface property of the coating surface), and it becomes a constituent layer with good surface property. In this way, it is believed that a sheet for all-solid-state secondary batteries with a constituent layer having a flat surface and low resistance (high conductivity) can be realized.
[0072] Moreover, the all-solid-state secondary battery with a constituent layer having a suppressed resistance rise and a flat surface is not easy to generate overcurrent during charge and discharge, and can prevent the degradation of solid particles, and the interface contact state of other layers adjacent to the surface of the constituent layer becomes good (high adhesion). Therefore, it is believed that even if repeated charge and discharge can be achieved, it will not cause a significant reduction in battery characteristics and an all-solid-state secondary battery with excellent cycle characteristics, and even in addition to showing excellent cycle characteristics, it also shows a high conductivity (ionic conductivity, electronic conductivity) All-solid-state secondary battery.
[0073] When the active material layer is formed by the composition containing an inorganic solid electrolyte of the present invention, as described above, a constituent layer is formed while maintaining a highly (uniform) dispersed state just after preparation. Therefore, it is believed that the contact (fit) between the low adsorption adhesive and the collector surface by the solid particles of the preferential precipitation etc. will not be hindered, and the low adsorption adhesive can contact (fit) with the collector surface in a state dispersed with the solid particles. Thus, the electrode sheet for all-solid-state secondary batteries formed by the composition containing an inorganic solid electrolyte of the present invention on the collector for active material layer can realize the strong fit between the collector and the active material. Moreover, the all-solid-state secondary battery formed by the composition containing an inorganic solid electrolyte of the present invention on the collector for active material layer shows the strong fit between the collector and the active material and further improves the cycle characteristics, and in addition to the excellent cycle characteristics, the improvement of conductivity can also be realized.
[0074] The composition containing an inorganic solid electrolyte of the present invention can be preferably used as a sheet material for an all-solid-state secondary battery (including an electrode sheet for an all-solid-state secondary battery) or a forming material (constituent layer forming material) of a solid electrolyte layer or an active material layer of an all-solid-state secondary battery. In particular, it can be preferably used as a forming material for a negative electrode sheet or a negative electrode active material layer for an all-solid-state secondary battery containing a negative electrode active material that has large expansion and contraction caused by charge and discharge, and in this way, high cycle characteristics and high conductivity can also be achieved.
[0075] The composition containing an inorganic solid electrolyte of the present invention is preferably a non-aqueous composition. In the present invention, the non-aqueous composition, in addition to including a mode that does not contain water, also includes a mode in which the water content (also referred to as water content) is preferably 500 ppm or less. In the non-aqueous composition, the water content is more preferably 200 ppm or less, further preferably 100 ppm or less, and particularly preferably 50 ppm or less. If the composition containing an inorganic solid electrolyte is a non-aqueous composition, the degradation of the inorganic solid electrolyte can be suppressed. The water content represents the amount of water contained in the composition containing an inorganic solid electrolyte (to the mass ratio of the composition containing an inorganic solid electrolyte), specifically, it is set to a value obtained by filtering with a 0.02 μm membrane filter and measuring using Karl Fischer titration.
[0076] The inorganic solid electrolyte-containing composition of the present invention also includes an embodiment in which it contains an active material, a conductive auxiliary agent, etc. in addition to the inorganic solid electrolyte (a composition of this embodiment is referred to as an electrode composition).
[0077] Hereinafter, components contained in and components that may be contained in the inorganic solid electrolyte composition of the present invention will be described.
[0078] <Inorganic solid electrolyte>
[0079] The inorganic solid electrolyte-containing composition of the present invention contains an inorganic solid electrolyte.
[0080] In the present invention, an inorganic solid electrolyte refers to an inorganic solid electrolyte, and a solid electrolyte refers to a solid electrolyte that enables ions to move inside it. Considering that an organic substance that is not included as the main ion conductive material is not included, it is clearly distinguished from an organic solid electrolyte (a polymer electrolyte represented by polyethylene oxide (PEO), etc., an organic electrolyte salt represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), etc.). In addition, since the inorganic solid electrolyte is solid in a stable state, it is usually not dissociated or freed into cations and anions. At this point, it is clearly distinguished from an inorganic electrolyte salt (LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), LiCl, etc.) that is dissociated or freed into cations and anions in an electrolyte or a polymer. As long as the inorganic solid electrolyte has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, it is not particularly limited and usually does not have electronic conductivity. When the all-solid-state secondary battery of the present invention is a lithium-ion battery, the inorganic solid electrolyte preferably has ion conductivity of lithium ions.
[0081] The above-mentioned inorganic solid electrolyte can be appropriately selected from solid electrolyte materials commonly used in all-solid-state secondary batteries. For example, as inorganic solid electrolytes, (i) sulfide-based inorganic solid electrolytes, (ii) oxide-based inorganic solid electrolytes, (iii) halide-based inorganic solid electrolytes, and (iv) hydride-based solid electrolytes can be cited. From the perspective of being able to form a better interface between the active material and the inorganic solid electrolyte, sulfide-based inorganic solid electrolytes are preferred.
[0082] (i) Sulfide-based inorganic solid electrolytes
[0083] The sulfide-based inorganic solid electrolyte preferably contains a sulfur atom and has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table and is an electronically insulating compound. The sulfide-based inorganic solid electrolyte preferably contains at least Li, S, and P as elements and has lithium ion conductivity, but may contain elements other than Li, S, and P depending on the purpose or circumstances.
[0084] Examples of the sulfide-based inorganic solid electrolyte include lithium ion conductive inorganic solid electrolytes having a composition represented by the following formula (S1).
[0085] L a1 M b1 P c1 S d1 A e1 (S1)
[0086] In the formula, L represents an element selected from Li, Na and K, preferably Li. M represents an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al and Ge. A represents an element selected from I, Br, Cl and F. a1~e1 represent the composition ratio of each element, and a1:b1:c1:d1:e1 satisfies 1~12:0~5:1:2~12:0~10. a1 is preferably 1~9, and more preferably 1.5~7.5. b1 is preferably 0~3, and more preferably 0~1. d1 is preferably 2.5~10, and more preferably 3.0~8.5. e1 is preferably 0~5, and more preferably 0~3.
[0087] As described below, the composition ratio of each element can be controlled by adjusting the blending amount of the raw material compound when producing the sulfide-based inorganic solid electrolyte.
[0088] The sulfide-based inorganic solid electrolyte may be amorphous (glass), crystallized (glass ceramic), or only partially crystallized. For example, Li-PS-based glass containing Li, P, and S or Li-PS-based glass ceramic containing Li, P, and S may be used.
[0089] Sulfide-based inorganic solid electrolytes can be manufactured by reacting at least two or more raw materials, for example, lithium sulfide (Li2S), phosphorus sulfide (for example, phosphorus pentasulfide (P2S5)), elemental phosphorus, elemental sulfur, sodium sulfide, hydrogen sulfide, lithium halide (for example, LiI, LiBr, LiCl) and sulfides of the elements represented by the above M (for example, SiS2, SnS, GeS2).
[0090] The ratio of Li2S to P2S5 in the Li-PS glass and Li-PS glass ceramics is preferably 60:40 to 90:10, and more preferably 68:32 to 78:22, in terms of the molar ratio of Li2S:P2S5. By setting the ratio of Li2S to P2S5 to this range, the lithium ion conductivity can be improved. Specifically, the lithium ion conductivity can be preferably set to 1×10 -4 S / cm or more, more preferably 1×10 -3 S / cm or more. Although there is no specific upper limit, it is actually 1×10 -1 S / cm or less.
[0091] As specific examples of sulfide-based inorganic solid electrolytes, the combination of raw materials is shown below. For example, Li2S-P2S5, Li2S-P2S5-LiCl, Li2S-P2S5-H2S, Li2S-P2S5-H2S-LiCl, Li2S-LiI-P2S5, Li2S-LiI-Li2O-P2S5, Li2S-LiBr-P2S5, Li2S-Li2O-P2S5, Li2S-Li3PO4-P2S5, Li2S-P2S5-P2O5, Li2S-P2S5-SiS2, Li2S-P2S5-SiS2-LiCl, Li2S-P2S5-SnS, Li2S-P2S5-Al2 S3, Li2S-GeS2, Li2S-GeS2-ZnS, Li2S-Ga2S3, Li2S-GeS2-Ga2S3, Li2S-GeS2-P2S5, Li2S-GeS2-Sb2S5, Li2S-GeS2-Al2S3, Li2S-SiS2, Li2S-Al2S3, Li2S-SiS2-Al2S3, Li2S-SiS2-P2S5, Li2S-SiS2-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li 10 GeP2S 12 etc. Among them, the mixing ratio of each raw material is not limited. As a method for synthesizing a sulfide-based inorganic solid electrolyte material using such a raw material composition, for example, an amorphization method can be cited. As an amorphization method, for example, a mechanical polishing method, a solution method, and a melt quenching method can be cited. It is possible to perform treatment at room temperature, thereby simplifying the manufacturing process.
[0092] (ii) Oxide-based inorganic solid electrolytes
[0093] The oxide-based inorganic solid electrolyte is preferably a compound that contains oxygen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0094] The ion conductivity of the oxide-based inorganic solid electrolyte is preferably 1×10 -6 S / cm or more, more preferably 5×10 -6 S / cm or more, particularly preferably 1×10 -5 S / cm or more. Although there is no specific upper limit, it is actually 1×10 -1 S / cm or less.
[0095] As specific examples of compounds, for example, Li xa La yaTiO3〔xa satisfies 0.3≤xa≤0.7, ya satisfies 0.3≤ya≤0.7.〕(LLT); Li xb La yb Zr zb M bb mb O nb (M bb is one or more elements selected from the group consisting of Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In and Sn. xb satisfies 5≤xb≤10, yb satisfies 1≤yb≤4, zb satisfies 1≤zb≤4, mb satisfies 0≤mb≤2, and nb satisfies 5≤nb≤20. ); Li xc B yc M cc zc O nc (M cc is one or more elements selected from C, S, Al, Si, Ga, Ge, In and Sn. xc satisfies 0<xc≤5, yc satisfies 0<yc≤1, zc satisfies 0<zc≤1, and nc satisfies 0<nc≤6. ); Li xd (Al, Ga) yd (Ti, Ge) zd Si ad P md O nd (xd satisfies 1≤xd≤3, yd satisfies 0≤yd≤1, zd satisfies 0≤zd≤2, ad satisfies 0≤ad≤1, md satisfies 1≤md≤7, and nd satisfies 3≤nd≤13.) (3-2xe) M ee xe D ee O(xe represents a number greater than or equal to 0 and less than or equal to 0.1, M ee Represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. );Li xf Si yf O zf (xf satisfies 1≤xf≤5, yf satisfies 0<yf≤3, zf satisfies 1≤zf≤10.) xg S yg O zg (xg satisfies 1≤xg≤3, yg satisfies 0<yg≤2, zg satisfies 1≤zg≤10.);Li3BO3;Li3BO3-Li2SO4;Li2O-B2O3-P2O5;Li2O-SiO2;Li6BaLa2Ta2O 12 ;Li3PO (4-3 / 2w) N w(w satisfies w<1); Li with LISICON (Lithium super ionicconductor) type crystal structure 3.5 Zn 0.25 GeO4; La with perovskite crystal structure 0.55 Li 0.35 TiO3; LiTi2P3O with NASICON (Natrium super ionic conductor) type crystal structure 12 ;Li 1+xh+yh (Al, Ga) xh (Ti, Ge) 2-xh Si yh P 3-yh O 12 (xh satisfies 0≤xh≤1, yh satisfies 0≤yh≤1.); Li7La3Zr2O with garnet crystal structure 12 (LLZ) etc.
[0096] Furthermore, phosphorus compounds containing Li, P, and O are also preferred. Examples thereof include lithium phosphate (Li3PO4); LiPON in which a part of oxygen in lithium phosphate is substituted with nitrogen; and LiPOD 1 (D 1 Preferably, it is one or more elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt and Au. ) etc.
[0097] In addition, LiA can also be preferably used 1 ON(A 1 It is one or more elements selected from Si, B, Ge, Al, C and Ga. ) etc.
[0098] (iii) Halide-based inorganic solid electrolytes
[0099] The halide-based inorganic solid electrolyte is preferably a compound containing halogen atoms, having ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and having electron insulating properties.
[0100] There are no particular restrictions on the halide-based inorganic solid electrolyte, and examples thereof include LiCl, LiBr, LiI, and compounds such as Li3YBr6 and Li3YCl6 described in ADVANCED MATERIALS, 2018, 30, 1803075. Among them, Li3YBr6 and Li3YCl6 are preferred.
[0101] (iv) Hydride-based inorganic solid electrolytes
[0102] The hydride-based inorganic solid electrolyte is preferably a compound that contains hydrogen atoms, has ion conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and has electron insulating properties.
[0103] The hydride-based inorganic solid electrolyte is not particularly limited, and examples thereof include LiBH4, Li4(BH4)3I, and 3LiBH4-LiCl.
[0104] The inorganic solid electrolyte is preferably in the form of particles. In this case, the particle size (volume average particle size) of the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.1 μm or more. The upper limit is preferably 100 μm or less, more preferably 50 μm or less.
[0105] The particle size of the inorganic solid electrolyte is determined by the following steps. In a 20 mL sample bottle, the inorganic solid electrolyte particles are diluted with water (heptane in the case of substances unstable to water) to prepare a 1% dispersion. The diluted dispersion sample is irradiated with 1 kHz ultrasound for 10 minutes and then used immediately in the test. Using the dispersion sample, a laser diffraction / scattering particle size distribution analyzer LA-920 (trade name, manufactured by HORIBA, Ltd.) is used and 50 data collections are performed at a temperature of 25°C using a quartz cell for measurement to obtain the volume average particle size. For other detailed conditions, refer to JIS Z8828:2013 "Particle Size Analysis-Dynamic Light Scattering Method" as needed. Five samples are prepared for each level and their average value is adopted.
[0106] The inorganic solid electrolyte may contain one kind or two or more kinds.
[0107] When a solid electrolyte layer is formed, the solid electrolyte layer has a surface area (cm 2 The mass (mg) (weight per unit area) of the inorganic solid electrolyte is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0108] When the composition containing an inorganic solid electrolyte contains an active material described later, the total amount of the active material and the inorganic solid electrolyte is preferably within the above range regarding the weight per unit area of the inorganic solid electrolyte.
[0109] The content of the inorganic solid electrolyte, the composition containing the inorganic solid electrolyte is not particularly limited, from the viewpoint of cohesiveness, and then from the viewpoint of dispersibility, in 100% by mass of solid content, preferably 50% by mass or more, more preferably 70% by mass or more, and especially preferably 90% by mass or more. As the upper limit, from the same viewpoint, preferably 99.9% by mass or less, more preferably 99.5% by mass or less, especially preferably 99% by mass or less.
[0110] However, when the composition containing an inorganic solid electrolyte contains an active material described below, the total content of the active material and the inorganic solid electrolyte in the composition containing an inorganic solid electrolyte is preferably within the above range.
[0111] In the present invention, the solid content refers to the components that do not disappear when the composition containing the inorganic solid electrolyte is dried at 150° C. for 6 hours under a nitrogen atmosphere at a pressure of 1 mmHg. Typically, it refers to the components other than the dispersion medium described below.
[0112] <Polymer Binder>
[0113] The composition containing an inorganic solid electrolyte of the present invention contains a polymer binder, and the polymer binder includes one or more polymer binders (low-adsorption binders) having an adsorption rate of less than 60% relative to the inorganic solid electrolyte in the composition. The polymer binder contained in the composition containing an inorganic solid electrolyte of the present invention may contain polymer binders other than low-adsorption binders, for example, polymer binders having an adsorption rate of 60% or more relative to the inorganic solid electrolyte in the composition (high-adsorption binders), and granular polymer binders (preferably polymer binders having an adsorption rate of 60% or more relative to the inorganic solid electrolyte in the composition).
[0114] In the present invention, the polymer binder refers to a binder containing a polymer.
[0115] (Low adsorption adhesive)
[0116] First, the low-adsorption binder contained as a polymer binder in the inorganic solid electrolyte-containing composition of the present invention will be described.
[0117] The low-adsorption binder is used together with solid particles such as an inorganic solid electrolyte in an inorganic solid electrolyte-containing composition containing a dispersion medium, thereby improving the dispersion stability and handling properties of the inorganic solid electrolyte-containing composition (slurry).
[0118] In the present invention, the adsorption rate of the binder is a value measured using the inorganic solid electrolyte and the dispersion medium contained in the composition containing the inorganic solid electrolyte, and is an index showing the degree of adsorption of the binder in the dispersion medium to the inorganic solid electrolyte. Here, the adsorption of the binder to the inorganic solid electrolyte includes not only physical adsorption but also chemical adsorption (adsorption by forming a chemical bond, adsorption by electron donation, etc.).
[0119] When the composition containing an inorganic solid electrolyte contains multiple inorganic solid electrolytes, the adsorption rate is the inorganic solid electrolyte having the same composition (type and content) as the inorganic solid electrolyte composition in the composition containing an inorganic solid electrolyte. When the composition containing an inorganic solid electrolyte contains multiple dispersion media, the adsorption rate is also measured using a dispersion medium having the same composition (type and content) as the dispersion medium in the composition containing an inorganic solid electrolyte. In addition, when multiple low-adsorption adhesives are used, the adsorption rate for multiple low-adsorption adhesives is also set in the same manner as the composition containing an inorganic solid electrolyte.
[0120] In the present invention, the adsorption rate of the low-adsorption binder is set to a value calculated by the method described in the Examples.
[0121] In the present invention, the adsorption rate of the inorganic solid electrolyte can be appropriately set by the type of polymer that forms the low-adsorption binder (the structure and composition of the polymer chain), the type or content of the functional groups possessed by the polymer, the form of the low-adsorption binder (the amount dissolved in the dispersion medium), etc.
[0122] The adsorption rate of the low-adsorption adhesive is less than 60%. If the low-adsorption adhesive shows the above adsorption rate, it is possible to suppress excessive adsorption of the inorganic solid electrolyte and improve the dispersion stability and handling properties of the composition containing the inorganic solid electrolyte. From the perspective of being able to take into account both dispersion stability and handling properties at a higher level, the adsorption rate is preferably 40% or less, more preferably 30% or less, further preferably 20% or less, and particularly preferably 10% or less. On the other hand, the lower limit of the adsorption rate is not particularly limited and can also be set to 0%. From the perspective of dispersion stability and handling properties, the lower limit of the adsorption rate is preferably small. On the other hand, from the perspective of improving the adhesion of the inorganic solid electrolyte, it is preferably 0.1% or more, and more preferably 1% or more.
[0123] The low-adsorption binder may be soluble (soluble binder) or insoluble in the dispersion medium contained in the composition containing the inorganic solid electrolyte, but preferably a soluble binder that dissolves in the dispersion medium. When two or more low-adsorption binders are contained, preferably at least one low-adsorption binder is soluble, and it is also a preferred embodiment that all low-adsorption binders are soluble.
[0124] In the present invention, the binder being dissolved in the dispersion medium means that the binder is dissolved in the dispersion medium of the composition containing the inorganic solid electrolyte, for example, it means that the solubility is 80% or more in a solubility measurement. The solubility measurement method is as follows.
[0125] That is, a predetermined amount of the adhesive to be measured is weighed in a glass bottle, 100 g of a dispersion medium of the same type as the dispersion medium contained in the composition containing the inorganic solid electrolyte is added thereto, and stirred at a rotation speed of 80 rpm on a mixing rotor at a temperature of 25°C for 24 hours. The transmittance of the mixed solution obtained after stirring for 24 hours is measured under the following conditions. The test (transmittance measurement) is carried out by changing the amount of adhesive dissolved (the above-mentioned predetermined amount), and the upper limit concentration X (mass %) at which the transmittance becomes 99.8% is set as the solubility of the adhesive in the above-mentioned dispersion medium.
[0126] <Transmittance measurement conditions>
[0127] Dynamic light scattering (DLS) measurement
[0128] Device: DLS measuring device DLS-8000 manufactured by Otsuka Electronics Co., Ltd.
[0129] Laser wavelength, output: 488nm / 100mW
[0130] Sample cell: NMR tube
[0131] When the composition containing an inorganic solid electrolyte of the present invention contains an active material described later (when an active material layer is formed by a composition containing an inorganic solid electrolyte), the adsorption rate of the low-adsorption binder on the active material is not particularly limited. From the perspective of enhancing the dispersion stability and handling properties of the composition containing an inorganic solid electrolyte and the bonding properties of the solid particles, it is preferably 90% or less, more preferably 0.1 to 50%, and further preferably 1 to 10%. In the present invention, the adsorption rate of the binder on the active material is a value measured using the active material and the dispersion medium contained in the composition containing an inorganic solid electrolyte, and is an indicator showing the degree to which the binder in the dispersion medium is adsorbed on the active material. Here, the adsorption of the binder to the active material includes not only physical adsorption, but also chemical adsorption (adsorption by forming a chemical bond, adsorption by electron transfer, etc.).
[0132] When the composition containing an inorganic solid electrolyte contains a plurality of active substances or dispersion media, in the case of using a plurality of binders, the adsorption rate of the inorganic solid electrolyte is the same as that of the above-mentioned binder. In the present invention, the adsorption rate of the binder to the active substance is set to the value calculated by the method described in the embodiment. In the present invention, the adsorption rate to the active substance can be appropriately set in the same manner as the adsorption rate to the inorganic solid electrolyte.
[0133] --Polymers that form low adsorption adhesives--
[0134] As long as the polymer forming the low adsorption adhesive satisfies the above-mentioned adsorption rate relative to the inorganic solid electrolyte, there is no particular limitation, and various polymers can be used. Among them, preferably, a polymer having at least one bond selected from a carbamate bond, a urea bond, an amide bond, an imide bond, and an ester bond or a polymer chain having a carbon-carbon double bond in the main chain can be listed. When containing two or more low adsorption adhesives, it is preferred that the polymer forming at least one low adsorption adhesive is a polymer having the above-mentioned bond or polymer chain in the main chain, and it is also one of the preferred methods that the polymer forming all low adsorption adhesives is a polymer having the above-mentioned bond or polymer chain in the main chain.
[0135] In the present invention, the main chain of a polymer refers to a linear molecular chain that can be regarded as a branch chain or a comb-shaped chain relative to the main chain, which constitutes the polymer. Although it depends on the mass average molecular weight of the molecular chain regarded as a branch chain or a comb-shaped chain, it is typically the longest chain among the molecular chains constituting the polymer that becomes the main chain. However, the terminal groups at the ends of the polymer are not included in the main chain. In addition, the side chain of the polymer refers to the molecular chain other than the main chain, including short molecular chains and long molecular chains.
[0136] As long as the above-mentioned bonds are included in the main chain of the polymer, there are no particular restrictions, and they can be in any form included in the constituent units (repeating units) and / or included as bonds connecting different constituent units. In addition, the above-mentioned bonds included in the main chain are not limited to one type, and can be more than two types, preferably 1 to 6 types, and more preferably 1 to 4 types. In this case, there is no particular restriction on the bonding mode of the main chain, and it can randomly have more than two types of bonds, or it can be a partitioned main chain with partitions having specific bonds and partitions having other bonds.
[0137] The main chain having the above bonds is not particularly limited, but is preferably a main chain having at least one segment of the above bonds, more preferably a main chain consisting of polyamide, polyurea, polyurethane, or (meth)acrylic polymer, and further preferably a main chain consisting of polyurethane or (meth)acrylic polymer.
[0138] Examples of polymers having a urethane bond, urea bond, amide bond, imide bond or ester bond in the main chain include stepwise polymerization (polycondensation, polyaddition or addition condensation) polymers such as polyurethane, polyurea, polyamide, polyimide, polyester, and copolymers thereof. The copolymer may be a block copolymer using the above polymers as segments, or a random copolymer in which the constituent components constituting two or more of the above polymers are randomly bonded.
[0139] As polymers having a polymer chain with a carbon-carbon double bond in the main chain, chain polymers such as fluorine-based polymers (fluorine-containing polymers), hydrocarbon-based polymers, ethylene-based polymers, (meth)acrylic polymers, etc. can be cited. The polymerization method of these chain polymers is not particularly limited, and they can be any of block copolymers, alternating copolymers, and random copolymers.
[0140] As the polymer forming the low-adsorption adhesive, the above-mentioned polymers can be appropriately selected, but a polymer other than (hydrogenated) styrene-butadiene copolymer polymer, styrene-butadiene-styrene block copolymer polymer or styrene-ethylene-butylene-styrene copolymer polymer (hydrocarbon-based polymer) or PVdF-HFP copolymer (fluorine-based polymer) is one of the preferred forms, and more preferably a polyurethane, polyurea, polyester or (meth) acrylic polymer.
[0141] The polymer forming the low-adsorption binder may be one kind or two or more kinds.
[0142] The polymer forming the low-adsorption binder preferably has a constituent component represented by any one of the following formulas (1-1) to (1-5), and more preferably has a constituent component represented by the following formula (1-1) or formula (1-2). When two or more low-adsorption binders are contained, the polymer forming at least one low-adsorption binder preferably has a constituent component represented by any one of the following formulas (1-1) to (1-5), and it is also one of the preferred embodiments that all low-adsorption binders have this constituent component. If the polymer forming the low-adsorption binder has a constituent component represented by any one of the following formulas, the adsorption rate of the polymer binder relative to the inorganic solid electrolyte can be reduced, and the dispersion stability and handleability of the composition containing the inorganic solid electrolyte can be improved.
[0143] [Chemical formula 2]
[0144]
[0145] In formula (1-1), R 1 represents a hydrogen atom or an alkyl group (the number of carbon atoms is preferably 1 to 12, more preferably 1 to 6, and even more preferably 1 to 3). 1The alkyl group may have a substituent. The substituent is not particularly limited, and examples thereof include the substituent Z described below, and is preferably a group other than the functional group selected from the functional group group (a), and preferably includes a halogen atom.
[0146] R 2 In the present invention, the group having a hydrocarbon group includes a group consisting of a hydrocarbon group itself (a hydrocarbon group directly bonded to R 1 The carbon atom in the above formula to which it is bonded. ) and connected by R 2 The group consisting of the carbon atom and the hydrocarbon group in the above formula bonded (the hydrocarbon group is bonded to R via the linking group) 1 The carbon atom in the above formula to which it is bonded. ).
[0147] A hydrocarbon group is a group composed of carbon atoms and hydrogen atoms, usually introduced into R 2 The hydrocarbon group is not particularly limited, but is preferably an aliphatic hydrocarbon group, more preferably an aliphatic saturated hydrocarbon group (alkyl group), and further preferably a linear or branched alkyl group. The number of carbon atoms in the hydrocarbon group may be 4 or more, preferably 6 or more, and more preferably 10 or more. The upper limit is not particularly limited, but is preferably 20 or less, and more preferably 14 or less.
[0148] The linking group is not particularly limited, and examples thereof include alkylene groups (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and even more preferably 1 to 3 carbon atoms), alkenylene groups (preferably having 2 to 6 carbon atoms, more preferably 2 to 3 carbon atoms), arylene groups (preferably having 6 to 24 carbon atoms, more preferably 6 to 10 carbon atoms), oxygen atoms, sulfur atoms, imino groups (-NR N -:R N represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. ), a carbonyl group, a phosphoric acid linking group (-OP(OH)(O)-O-), a phosphonic acid linking group (-P(OH)(O)-O-), or a group related to a combination thereof. An alkylene group and an oxygen atom can also be combined to form a polyalkyleneoxy chain. As a linking group, a group composed of an alkylene group, an arylene group, a carbonyl group, an oxygen atom, a sulfur atom, and an imino group is preferably combined, and a group composed of an alkylene group, an arylene group, a carbonyl group, an oxygen atom, and an imino group is more preferably combined, and a group containing a -CO-O- group, a -CO-N(R N )-base (R N As mentioned above. ) group, particularly preferably -CO-O- group or -CO-N(R N )-base (R N As described above.). The number of atoms constituting the linking group and the number of connecting atoms are described below. However, the polyalkyleneoxy chain constituting the linking group is not limited to the above.
[0149] In the present invention, the number of atoms constituting the linking group is preferably 1 to 36, more preferably 1 to 24, further preferably 1 to 12, and particularly preferably 1 to 6. The number of connecting atoms of the linking group is preferably 10 or less, more preferably 8 or less. The lower limit is 1 or more. The above-mentioned number of connecting atoms refers to the minimum number of atoms connecting the specified structural parts. For example, in the case of -CH2-C(=O)-O-, the number of atoms constituting the linking group becomes 6, but the number of connecting atoms becomes 3.
[0150] The hydrocarbon group and the linking group may or may not have a substituent. Examples of the substituent that may be present include a substituent Z, preferably a group other than the functional group selected from the functional group group (a), and preferably a halogen atom or the like.
[0151] In the above formula (1-1), R 1 The carbon atom adjacent to the bonded carbon atom has two hydrogen atoms, but may have one or two substituents in the present invention. The substituent is not particularly limited, and may include the substituent Z described below, and is preferably a group other than the functional group selected from the functional group group (a).
[0152] The compound to be introduced into the constituent component represented by formula (1-1) is not particularly limited, and examples thereof include linear alkyl (meth)acrylate compounds (linear alkyl refers to an alkyl group having 4 or more carbon atoms).
[0153] In formula (1-2) to formula (1-5), R 3 It represents a linking group having a mass average molecular weight of 500 or more and 200,000 or less containing a polybutadiene chain or a polyisoprene chain.
[0154] Can be used as R 3 The terminal of the above chain can be appropriately changed to R 3 Common chemical structures that can be incorporated into the constituent components represented by the above-mentioned formulae.
[0155] In the above formulas, R 3 It is a divalent molecular chain, but at least one hydrogen atom is replaced by -NH-CO-, -CO-, -O-, -NH- or -N<, and it can become a trivalent or higher chain.
[0156] Can be used as R 3As long as the polybutadiene chain and the polyisoprene chain satisfy the mass average molecular weight, the chains composed of known polybutadiene and polyisoprene can be cited. The polybutadiene chain and the polyisoprene chain are both diene polymers having double bonds in the main chain, but in the present invention, polymers whose double bonds are hydrogenated (reduced) (for example, non-diene polymers having no double bonds in the main chain) are included. In the present invention, hydrogenated products of polybutadiene chains or polyisoprene chains are preferred.
[0157] The polybutadiene chain and the polyisoprene chain preferably have a reactive group at their terminal as a raw material compound, and more preferably have a polymerizable terminal reactive group. The polymerizable terminal reactive group forms a terminal reactive group with R of the above formula by polymerization. 3 As such terminal reactive groups, hydroxyl, carboxyl, amino, etc. can be cited, among which hydroxyl is preferred. As polybutadiene and polyisoprene having terminal reactive groups, for example, NISSO-PB series (manufactured by NIPPON SODA CO., LTD.), Claysol series (manufactured by TOMOE Engineering Co., Ltd.), PolyVEST-HT series (manufactured by EVONIK CO., LTD.), poly-bd series (manufactured by Idemitsu Kosan Co., Ltd.), poly-ip series (manufactured by Idemitsu Kosan Co., Ltd.), EPOL (manufactured by Idemitsu Kosan Co., Ltd.), etc., all of which are trade names, can be preferably used.
[0158] Can be used as R 3 The above chain preferably has a mass average molecular weight (in terms of polystyrene) of 500 to 200,000. The lower limit is preferably 500 or more, more preferably 700 or more, and further preferably 1,000 or more. As the upper limit, it is preferably 100,000 or less, and more preferably 10,000 or less. For the raw material compound before being incorporated into the main chain of the polymer, the mass average molecular weight is measured by the method described below.
[0159] The content of the constituent represented by any one of the above formulae (1-1) to (1-5) in the polymer is not particularly limited, but is preferably 10 to 100 mol %, more preferably 30 to 98 mol %, and further preferably 50 to 95 mol % from the viewpoint of improving dispersion stability and handling properties. On the other hand, from the viewpoint of improving adhesion, it is preferably 0 to 90 mol %, more preferably 10 to 80 mol %, and further preferably 20 to 70 mol %.
[0160] When two or more low-adsorption binders are contained, the content of the constituent component represented by any one of formulas (1-1) to (1-5) relative to the total molar number of constituent components of the polymers forming all the low-adsorption binders is not particularly limited and can be appropriately set according to the content in the above-mentioned polymers.
[0161] The polymer forming the low-adsorption adhesive preferably contains, for example, a constituent having a functional group selected from the following functional group group (a) as a substituent. When more than two low-adsorption adhesives are contained, the polymer forming at least one low-adsorption adhesive preferably contains a constituent having the functional group, and it is also one of the preferred modes that the polymer forming all low-adsorption adhesives contains a constituent having the functional group. The constituent having the functional group has the function of increasing the adsorption rate of the low-adsorption adhesive relative to the inorganic solid electrolyte, and can also be any constituent forming the polymer. The functional group can be incorporated into the main chain of the polymer or into the side chain. When incorporated into the side chain, it has a connecting group that bonds the functional group and the main chain. There is no particular limitation as the connecting group, and the connecting group described later can be cited. The functional group possessed by one constituent may be one or more than two. When there are more than two, they may be bonded to each other or not.
[0162] <Functional group (a)>
[0163] Hydroxyl group, amino group, carboxyl group, sulfone group, phosphoric acid group, phosphonic acid group, sulfanyl group, ether bond (-O-), imino group (=NR, -NR-), ester bond (-CO-O-), amide bond (-CO-NR-), carbamate bond (-NR-CO-O-), urea bond (-NR-CO-NR-), heterocyclic group, aromatic group, carboxylic anhydride group, fluoroalkyl group, siloxane group
[0164] The amino group, sulfo group, phosphoric acid group (phosphoryl group), heterocyclic group, and aryl group contained in the functional group (a) are not particularly limited, and have the same meaning as the corresponding groups of the substituent Z described later. Among them, the number of carbon atoms of the amino group is more preferably 0 to 12, further preferably 0 to 6, and particularly preferably 0 to 2. There is no particular limitation on the phosphonic acid group, and examples thereof include phosphonic acid groups having 0 to 20 carbon atoms. When an amino group, an ether bond, an imino group (-NR-), an ester bond, an amide bond, a carbamate bond, a urea bond, etc. are contained in a ring structure, they are classified as heterocyclic rings. Hydroxyl, amino group, carboxyl group, sulfo group, phosphoric acid group, phosphonic acid group, and sulfanyl group can form salts.
[0165] The fluoroalkyl group is a group obtained by substituting at least one hydrogen atom in an alkyl group or a cycloalkyl group with a fluorine atom, and the number of carbon atoms is preferably 1 to 20, more preferably 2 to 15, and even more preferably 3 to 10. The number of fluorine atoms on the carbon atoms may be partial or all substitutions for hydrogen atoms (perfluoroalkyl group).
[0166] The siloxane group is not particularly limited, and preferably has a siloxane group consisting of -(SiR2-O) n The repeating number n is preferably an integer of 1 to 100, more preferably an integer of 5 to 50, and even more preferably an integer of 10 to 30.
[0167] R in each bond represents a hydrogen atom or a substituent, preferably a hydrogen atom. The substituent is not particularly limited and is selected from the substituent Z described below, and is preferably an alkyl group.
[0168] There are no particular restrictions on the carboxylic acid anhydride group, and include groups formed by removing one or more hydrogen atoms from carboxylic acid anhydride (for example, a group represented by the following formula (2a)), and further as a constituent formed by copolymerization of a polymerizable carboxylic acid anhydride as a copolymerizable compound (for example, a constituent represented by the following formula (2b)). As a group formed by removing one or more hydrogen atoms from a carboxylic acid anhydride, it is preferably a group formed by removing one or more hydrogen atoms from a cyclic carboxylic acid anhydride. The carboxylic acid anhydride group derived from a cyclic carboxylic acid anhydride is also equivalent to a heterocyclic group, but is classified as a carboxylic acid anhydride group in the present invention. For example, non-cyclic carboxylic acid anhydrides such as acetic anhydride, propionic anhydride, and benzoic acid rod, maleic anhydride, phthalic anhydride, fumaric acid rod, succinic anhydride and other cyclic carboxylic acid anhydrides, etc. can be cited. There are no particular restrictions on the polymerizable carboxylic acid anhydride, and carboxylic acid anhydrides having unsaturated bonds in the molecule can be cited, preferably polymerizable cyclic carboxylic acid anhydrides. Specifically, maleic anhydride and the like can be cited.
[0169] Examples of the carboxylic anhydride group include a group represented by the following formula (2a) or a constituent represented by the formula (2b), but the present invention is not limited thereto. In each formula, * represents a bonding position.
[0170] [Chemical formula 3]
[0171]
[0172] In a step-polymerized polymer, when the chemical structure of the polymer is represented by the constituents derived from the raw material compounds, an ester bond (-CO-O-), an amide bond (-CO-NR-), a urethane bond (-NR-CO-O-), and a urea bond (-NR-CO-NR-) are represented by being divided into a -CO- group and an -O- group, a -CO group and a -NR- group, a -NR-CO- group and an -O- group, and a -NR-CO- group and a -NR- group, respectively. Therefore, in the present invention, as constituents having these bonds, regardless of the labeling of the polymer, constituents derived from carboxylic acid compounds or constituents derived from isocyanate compounds are defined, and constituents derived from polyols or polyamine compounds are not included.
[0173] Furthermore, in the chain polymer, the constituent having an ester bond (excluding the ester bond forming a carboxyl group) or an amide bond means a constituent in which the ester bond or the amide bond is not directly bonded to an atom of the main chain constituting the chain polymer or the main chain of a polymer chain woven as a branch or comb-shaped chain in the chain polymer (for example, a polymer chain possessed by a macromonomer), and for example, does not include a constituent derived from an alkyl (meth)acrylate.
[0174] There is no particular limitation on the connecting group between the bonding functional group and the main chain, and R of the above formula (1-1) can be used. 2 The meaning of the connecting group in the group having a hydrocarbon group with more than 4 carbon atoms is the same as that of the connecting group except for the particularly preferred connecting group. As the connecting group for the bonding functional group and the main chain, the particularly preferred connecting group is a -CO-O- group or a -CO-N(R N )-base (R N As described above. ) and an alkylene or polyalkyleneoxy chain.
[0175] The constituent having the above-mentioned functional group is not particularly limited as long as it has the above-mentioned functional group. For example, there can be mentioned a constituent having the above-mentioned functional group introduced into a constituent represented by any one of the above-mentioned formulas (1-1) to (1-5), a constituent represented by the later-described formula (I-1) or (I-2), a constituent derived from a compound represented by the later-described formula (I-5), and a constituent having the above-mentioned functional group introduced into a constituent represented by the later-described formula (I-3) or (I-4) or a constituent derived from a compound represented by the later-described formula (I-6), the later-described (meth)acrylic compound (M1) or other polymerizable compound (M2), and a constituent having the above-mentioned functional group introduced into a constituent represented by any one of the later-described formulas (b-1) to (b-3).
[0176] The compound into which the constituent having the functional group is introduced is not particularly limited, and examples thereof include compounds into which the functional group is introduced into a short-chain alkyl (meth)acrylate compound (a short-chain alkyl group refers to an alkyl group having 3 or less carbon atoms).
[0177] The content of the constituent having the functional group in the polymer is not particularly limited as long as the adsorption rate of the low-adsorption binder to the inorganic solid electrolyte can be suppressed to less than 60%.
[0178] In the step-polymerized polymer, from the viewpoint of the cohesiveness of the solid particles, it is preferably 0.01 to 50 mol%, more preferably 0.1 to 50 mol%, and further preferably 0.3 to 50 mol%. In the chain-polymerized polymer, from the viewpoint of the cohesiveness of the solid particles, it is preferably 0.01 to 80 mol%, more preferably 0.01 to 70 mol%, further preferably 0.1 to 50 mol%, and particularly preferably 0.3 to 50 mol%. In the step-polymerized polymer and the chain-polymerized polymer, the lower limit of the content can also be set to 5 mol% or more or 20 mol% or more.
[0179] When two or more low-adsorption binders are contained, the content of the constituent component having the functional group relative to the total number of moles of constituent components of the polymers forming all the low-adsorption binders is not particularly limited and can be appropriately set according to the content in the above-mentioned polymers.
[0180] -Gradual Polymerization-
[0181] The stepwise polymerized polymer as a polymer forming a low adsorption adhesive preferably has the above-mentioned constituent having a functional group selected from the functional group group (a) or the above-mentioned constituent represented by any one of formulas (1-2) to (1-5), and may also have constituents different from these constituents. Among the constituents shown below, the constituent represented by formula (I-1) or formula (I-2) and the constituent derived from the compound represented by formula (I-5) are also equivalent to the constituent having a functional group selected from the functional group group (a), but are described together with other constituents. As other constituents, for example, there can be mentioned one or more (preferably 1 to 8, more preferably 1 to 4) of the constituent represented by the following formula (I-1) or (I-2) and the constituent represented by the following formula (I-3) or (I-4), or a constituent obtained by stepwise polymerization of a carboxylic acid dianhydride represented by the following formula (I-5) and a diamine compound introduced into the constituent represented by the following formula (I-6). The combination of each component can be appropriately selected according to the polymer species. One component used in the combination of components refers to a component represented by any of the following formulas, and even if two components represented by one of the following formulas are included, they are not interpreted as two components.
[0182] [Chemical formula 4]
[0183]
[0184] In the formula, R P1 and R P2Respectively represent molecular chains with a (mass average) molecular weight of 20 or more and 200,000 or less. The molecular weight of the molecular chain cannot be uniquely determined because it depends on its type, etc., for example, it is preferably 30 or more, more preferably 50 or more, further preferably 100 or more, and particularly preferably 150 or more. As an upper limit, it is preferably 100,000 or less, more preferably 10,000 or less. The molecular weight of the molecular chain is measured for the raw material compound before being incorporated into the main chain of the polymer.
[0185] R P1 and R P2 The molecular chain that can be used is not particularly limited, and is preferably a hydrocarbon chain, a polyalkylene oxide chain, a polycarbonate chain or a polyester chain, more preferably a hydrocarbon chain or a polyalkylene oxide chain, and further preferably a hydrocarbon chain, a polyethylene oxide chain or a polypropylene oxide chain.
[0186] R P1 and R P2 The hydrocarbon chain that can be used refers to a hydrocarbon chain composed of carbon atoms and hydrogen atoms, and more specifically, refers to a structure formed by the separation of at least two atoms (e.g., hydrogen atoms) or groups (e.g., methyl groups) in a compound composed of carbon atoms and hydrogen atoms. However, in the present invention, for example, as the hydrocarbon group represented by the following formula (M2), the hydrocarbon chain also includes a chain having a group containing an oxygen atom, a sulfur atom or a nitrogen atom in the chain. The terminal group that may be present at the end of the hydrocarbon chain is not included in the hydrocarbon chain. The hydrocarbon chain may have a carbon-carbon unsaturated bond, or may have a ring structure of an aliphatic ring and / or an aromatic ring. That is, the hydrocarbon chain may be a hydrocarbon chain composed of hydrocarbons selected from aliphatic hydrocarbons and aromatic hydrocarbons.
[0187] Such a hydrocarbon chain may be any hydrocarbon chain as long as it satisfies the above-mentioned molecular weight, and includes both hydrocarbon chains consisting of a low-molecular-weight hydrocarbon group and a hydrocarbon chain consisting of a hydrocarbon-based polymer (also referred to as a hydrocarbon-based polymer chain).
[0188] The low molecular weight hydrocarbon chain is a chain composed of a common (non-polymerizable) hydrocarbon group, and examples of the hydrocarbon group include aliphatic or aromatic hydrocarbon groups, and specifically, preferably an alkylene group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and further preferably 1 to 3 carbon atoms), an arylene group (preferably having 6 to 22 carbon atoms, preferably 6 to 14, and more preferably 6 to 10 carbon atoms), or a group composed of a combination thereof. P2 The hydrocarbon group of the low molecular weight hydrocarbon chain that can be used is more preferably an alkylene group, more preferably an alkylene group having 2 to 6 carbon atoms, and particularly preferably an alkylene group having 2 or 3 carbon atoms. The hydrocarbon chain may have a polymer chain (eg, a (meth)acrylic acid polymer) as a substituent.
[0189] The aliphatic hydrocarbon group is not particularly limited, and examples thereof include hydrogen-reduced products of aromatic hydrocarbon groups represented by the following formula (M2), partial structures possessed by known aliphatic diisocyanate compounds (for example, groups composed of isophorone), and the like.
[0190] Examples of the aromatic hydrocarbon group include hydrocarbon groups possessed by the constituent components described below, preferably an arylene group (for example, a group obtained by further removing one or more hydrogen atoms from an aryl group listed in the substituent Z described below, specifically a phenylene group, a tolylene group or a xylene group) or a hydrocarbon group represented by the following formula (M2).
[0191] [Chemical formula 5]
[0192]
[0193] In formula (M2), X represents a single bond, -CH2-, -C(CH3)2-, -SO2-, -S-, -CO- or -O-, and from the viewpoint of adhesion, is preferably -CH2- or -O-, and more preferably -CH2-. The alkylene group and alkyl group exemplified herein may be substituted by a substituent Z, preferably a halogen atom (more preferably a fluorine atom).
[0194] R M2 ~R M5 Each of R represents a hydrogen atom or a substituent, preferably a hydrogen atom. M2 ~R M5 The substituents that can be used are not particularly limited, and examples thereof include alkyl groups having 1 to 20 carbon atoms, alkenyl groups having 1 to 20 carbon atoms, -OR M6 ,―N(R M6 )2. -SR M6 (R M6 represents a substituent, preferably an alkyl group having 1 to 20 carbon atoms or an aryl group having 6 to 10 carbon atoms. ), a halogen atom (e.g., a fluorine atom, a chlorine atom, or a bromine atom). As -N(R M6 )2, for example, an alkylamino group (preferably having 1 to 20 carbon atoms, more preferably 1 to 6 carbon atoms) or an arylamino group (preferably having 6 to 40 carbon atoms, more preferably 6 to 20 carbon atoms).
[0195] The hydrocarbon polymer chain is a polymer chain formed by polymerizing a polymerizable hydrocarbon (at least 2). As long as it is a chain composed of a hydrocarbon polymer having a carbon number greater than the above-mentioned low molecular weight hydrocarbon chain, there is no particular limitation, and it is a chain containing a hydrocarbon polymer preferably composed of 30 or more, more preferably 50 or more carbon atoms. The upper limit of the number of carbon atoms constituting the hydrocarbon polymer is not particularly limited, for example, it can be set to 3,000. The hydrocarbon polymer chain is preferably a chain of a hydrocarbon polymer composed of aliphatic hydrocarbons whose main chain satisfies the above-mentioned number of carbon atoms, and more preferably a chain of a polymer (preferably an elastomer) composed of aliphatic saturated hydrocarbons or aliphatic unsaturated hydrocarbons. As a polymer, specifically, a diene polymer having a double bond on the main chain and a non-diene polymer having no double bond on the main chain can be cited. As a diene polymer, for example, a styrene-butadiene copolymer, a styrene-vinyl-butadiene copolymer, a copolymer of isobutylene and isoprene (preferably butyl rubber (IIR)), a vinyl-propylene-diene copolymer, etc. can be cited. Examples of the non-diene polymer include olefin polymers such as ethylene-propylene copolymers and styrene-ethylene-propylene copolymers, and hydrogen-reduced products of the above diene polymers.
[0196] The hydrocarbon forming the hydrocarbon chain preferably has a reactive group at its terminal, and more preferably has a terminal reactive group capable of polycondensation. The terminal reactive group capable of polycondensation or polyaddition forms a bond to R P1 or R P2 Examples of such terminal reactive groups include isocyanate groups, hydroxyl groups, carboxyl groups, amino groups, and acid anhydrides, among which hydroxyl groups are preferred.
[0197] As the hydrocarbon-based polymer having a terminal reactive group, for example, NISSO-PB series (manufactured by NIPPON SODA CO., LTD.), Claysol series (manufactured by TOMOE Engineering Co., Ltd.), PolyVEST-HT series (manufactured by EVONIK CO., LTD.), poly-bd series (manufactured by Idemitsu Kosan Co., Ltd.), poly-ip series (manufactured by Idemitsu Kosan Co., Ltd.), EPOL (manufactured by Idemitsu Kosan Co., Ltd.) and POLYTAIL series (manufactured by Mitsubishi Chemical Corporation) all of which are trade names can be preferably used.
[0198] As the polyalkylene oxide chain (polyalkylene oxide chain), a chain composed of a known polyalkyleneoxy group can be mentioned. The carbon number of the alkyleneoxy group in the polyalkylene oxide chain is preferably 1 to 10, more preferably 1 to 6, and further preferably 2 or 3 (polyethylene oxide chain or polypropylene oxide chain). The polyalkylene oxide chain may be a chain composed of one type of alkylene oxide group, or a chain composed of two or more types of alkylene oxide groups (for example, a chain composed of ethylene oxide and propylene oxide).
[0199] Examples of the polycarbonate chain or the polyester chain include chains composed of known polycarbonates or polyesters.
[0200] The polyalkyleneoxy chain, the polycarbonate chain or the polyester chain preferably has an alkyl group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6 carbon atoms) at the terminal.
[0201] R P1 and R P2 The ends of the polyalkylene oxide chain, polycarbonate chain and polyester chain that can be used can be appropriately changed to P1 and R P2 The common chemical structure that can be incorporated into the constituents represented by the above formulae. For example, a polyalkyleneoxy chain is formed by removing the terminal oxygen atom as R of the above constituents. P1 or R P2 And merged.
[0202] The alkyl group contained in the molecular chain may have an ether group (-O-), a thioether group (-S-), a carbonyl group (>C=O), an imino group (>NR N : R N is a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms).
[0203] In the above formulas, R P1 and R P2 It is a divalent molecular chain, but at least one hydrogen atom is replaced by -NH-CO-, -CO-, -O-, -NH- or -N<, and it can become a trivalent or higher molecular chain.
[0204] R P1 Among the above molecular chains, hydrocarbon chains are preferred, low molecular weight hydrocarbon chains are more preferred, hydrocarbon chains composed of aliphatic or aromatic hydrocarbon groups are further preferred, and hydrocarbon chains composed of aliphatic hydrocarbon groups are particularly preferred.
[0205] R P2 Among the above molecular chains, preferred are low molecular weight hydrocarbon chains (more preferably aliphatic hydrocarbon groups) or molecular chains other than low molecular weight hydrocarbon chains (more preferably polyalkylene oxide chains).
[0206] Specific examples of the constituents represented by the above formula (I-1) are shown below and in the Examples. In addition, as a raw material compound (isocyanate compound) for introducing the constituents represented by the above formula (I-1), for example, an isocyanate compound represented by formula (M1) and its specific example, and further polymerized 4,4'-diphenylmethane isocyanate, etc., described in International Publication No. 2018 / 020827, can be cited. In addition, in the present invention, the constituents represented by formula (I-1) and the raw material compounds introduced therein are not limited to the following specific examples and the contents recorded in the above-mentioned documents.
[0207] [Chemical formula 6]
[0208]
[0209] The raw material compound (carboxylic acid or its acid chloride, etc.) for introducing the constituent component represented by the above formula (I-2) is not particularly limited, and examples thereof include carboxylic acid or acid chloride compounds described in paragraph
[0074] of International Publication No. 2018 / 020827 and specific examples thereof (e.g., adipic acid or its esters).
[0210] Specific examples of the constituents represented by the above formula (I-3) or formula (I-4) are shown below and in the examples. In addition, there are no particular restrictions on the raw material compound (diol compound or diamine compound) for introducing the constituents represented by the above formula (I-3) or formula (I-4), for example, the compounds described in International Publication No. 2018 / 020827 and their specific examples, and further dihydroxyacetamide can be mentioned. In addition, in the present invention, the constituents represented by formula (I-3) or formula (I-4) and the raw material compounds introduced therein are not limited to the following specific examples, embodiments and the contents described in the above-mentioned documents.
[0211] In the specific examples described below, when a constituent component has a repeating structure, the number of repetitions is an integer greater than or equal to 1 and is appropriately set within the range satisfying the molecular weight or the number of carbon atoms of the above-mentioned molecular chain.
[0212] [Chemical formula 7]
[0213]
[0214] In formula (I-5), R P3 It represents an aromatic or aliphatic linking group (quadrivalent), and is preferably a linking group represented by any one of the following formulae (i) to (iix).
[0215] [Chemical formula 8]
[0216]
[0217] In formulas (i) to (iix), X 1 represents a single bond or a divalent linking group. As the divalent linking group, an alkylene group having 1 to 6 carbon atoms (e.g., methylene, vinyl, propenyl) is preferred. As the propenyl group, 1,3-hexafluoro-2,2-propanediyl is preferred. L represents -CH2=CH2- or -CH2-. R X and R Y In each formula, * represents a bonding site to the carbonyl group in formula (I-5). X and R Y The substituents that can be used are not particularly limited, and examples include the substituent Z described below, preferably an alkyl group (preferably having 1 to 12 carbon atoms, more preferably 1 to 6, and further preferably 1 to 3) or an aryl group (preferably having 6 to 22 carbon atoms, more preferably 6 to 14, and further preferably 6 to 10).
[0218] The carboxylic acid dianhydride represented by the above formula (I-5) and the raw material compound (diamine compound) for introducing the constituent components represented by the above formula (I-6) are not particularly limited, and examples thereof include the compounds described in International Publication No. 2018 / 020827 and International Publication No. 2015 / 046313 and specific examples thereof.
[0219] R P1 , R P2 and R P3 There are no particular limitations on the substituents, and examples thereof include the substituent Z described below or the groups included in the functional group (a). Preferably, R M2 The above-mentioned substituents which can be used.
[0220] When the polymer forming the low-adsorption adhesive is a step-polymerized polymer, it has a constituent represented by any one of the above formulas (1-1) to (1-5), preferably a constituent having a functional group selected from the functional group group (a) (including a constituent represented by the following formula (I-1)). It may also have a constituent represented by the above formula (I-3), formula (I-4) or formula (I-5). As the constituent represented by formula (I-3), a constituent represented by at least one of the following formulas (I-3A) to (I-3C) can be cited. The constituent represented by formula (I-4) is also the same as the constituent represented by formula (I-3), and the oxygen atom is replaced by a nitrogen atom in each of the following formulas (I-3A) to (I-3C).
[0221] [Chemical formula 9]
[0222]
[0223] In formula (I-1), R P1 As described above. In formula (I-3A), R P2A represents a chain consisting of a low molecular weight hydrocarbon group (preferably an aliphatic hydrocarbon group). P2B represents a polyalkyleneoxy chain. In formula (I-3C), R P2C Represents a hydrocarbon polymer chain. P2A The chain composed of low molecular weight hydrocarbon groups can be R P2B The polyalkylene oxide chain and the polyalkylene oxide chain may be R P2C The meanings of the hydrocarbon polymer chains are respectively the same as those of the hydrocarbon polymer chains in the above formula (I-3) which can be represented by R P2 The aliphatic hydrocarbon group, polyalkyleneoxy chain and hydrocarbon polymer chain have the same meanings and are preferably the same.
[0224] The polymer forming the low adsorption binder may have components other than the components represented by the above formulae. Such components are not particularly limited as long as they can be polymerized sequentially with the raw material compounds for introducing the components represented by the above formulae.
[0225] The (total) content of the constituent components represented by the above formulae (I-1) to (I-6) in the polymer forming the low-adsorption binder is not particularly limited, but is preferably 5 to 100 mol%, more preferably 5 to 80 mol%, and further preferably 10 to 60 mol%. The upper limit of the content may be set to 100 mol% or less, for example, regardless of the above 60 mol%.
[0226] The content of the constituent components other than the constituent components represented by the above-mentioned formulae in the polymer forming the low-adsorption binder is not particularly limited, but is preferably 50% by mass or less.
[0227] When the polymer forming the low-adsorption binder has a constituent represented by any one of the above formulas (I-1) to (I-6), its content is not particularly limited and can be appropriately set in consideration of the structural unit or the SP value of the polymer, for example, it can be set within the following range.
[0228] That is, the content of the constituent represented by formula (I-1) or formula (I-2) or the constituent derived from the carboxylic dianhydride represented by formula (I-5) in the polymer forming the low-adsorption adhesive is not particularly limited, and is preferably the same as the content of the constituent having the functional group mentioned above.
[0229] The content of the constituent represented by formula (I-3), formula (I-4) or formula (I-6) in the polymer forming the low-adsorption binder is not particularly limited, but is preferably 0 to 48 mol%, more preferably 0 to 45 mol%, and further preferably 0 to 40 mol%. The content of the constituent represented by formula (I-3) or formula (I-4) is particularly preferably 0 to 20 mol%.
[0230] The content of each component represented by any one of the above formulae (I-3A) to (I-3C) is appropriately set within the range of the content of the component represented by the above formula (I-3).
[0231] In addition, when the polymer forming the low-adsorption binder has a plurality of constituent components represented by various formulae, the above content of each constituent component is set as the total content.
[0232] The polymer (each component and raw material compound) forming the low adsorption binder may have a substituent. The substituent is not particularly limited, but preferably, a group selected from the following substituent Z is mentioned.
[0233] The polymer forming the low adsorption binder can be synthesized by selecting a raw material compound according to the type of bond possessed by the main chain by a known method and by subjecting the raw material compound to polyaddition or polycondensation. As a synthesis method, for example, reference can be made to International Publication No. 2018 / 151118.
[0234] The method for incorporating the functional group is not particularly limited, and examples thereof include a method of copolymerizing a compound having a functional group selected from the functional group group (a), a method of using a polymerization initiator having (generating) the above functional group, and a method of utilizing a polymer reaction.
[0235] As polymers of polyurethane, polyurea, polyamide, and polyimide that can be used as polymers to form low-adsorption adhesives, in addition to those synthesized in the examples, for example, polymers described in International Publication Nos. 2018 / 020827 and 2015 / 046313, and further in Japanese Patent Application Publication No. 2015-088480 can also be listed.
[0236] -Substituent Z-
[0237] Examples thereof include alkyl groups (preferably alkyl groups having 1 to 20 carbon atoms, for example, methyl, ethyl, isopropyl, tert-butyl, pentyl, heptyl, 1-ethylpentyl, benzyl, 2-ethoxyethyl, 1-carboxymethyl, etc.), alkenyl groups (preferably alkenyl groups having 2 to 20 carbon atoms, for example, vinyl, allyl, oleyl, etc.), alkynyl groups (preferably alkynyl groups having 2 to 20 carbon atoms, for example, ethynyl, butadiynyl, phenylethynyl, etc.), cycloalkyl groups (preferably cycloalkyl groups having 3 to 20 carbon atoms, for example, cyclopropyl, cyclopentyl, cyclohexyl, 4-methylcyclohexyl, etc. In the present specification, when the alkyl group is , usually means including cycloalkyl, but is described separately here. ), aryl (preferably an aryl having 6 to 26 carbon atoms, for example, phenyl, 1-naphthyl, 4-methoxyphenyl, 2-chlorophenyl, 3-methylphenyl, etc.), aralkyl (preferably an aralkyl having 7 to 23 carbon atoms, for example, benzyl, phenethyl, etc.), heterocyclic group (preferably a heterocyclic group having 2 to 20 carbon atoms, more preferably a 5- or 6-membered heterocyclic group having at least one oxygen atom, sulfur atom, or nitrogen atom. The heterocyclic group includes an aromatic heterocyclic group and an aliphatic heterocyclic group. For example, a tetrahydropyranyl ring group, a tetrahydrofuranyl ring group, a 2-pyranyl ring group, 4-pyridyl, 2-imidazolyl, 2-benzimidazolyl, 2-thiazolyl, 2-oxazolyl, pyrrolidonyl, etc.), alkoxy (preferably an alkoxy group having 1 to 20 carbon atoms, for example, methoxy, ethoxy, isopropoxy, benzyloxy, etc.), aryloxy (preferably an aryloxy group having 6 to 26 carbon atoms, for example, phenoxy, 1-naphthyloxy, 3-methylphenoxy, 4-methoxyphenoxy, etc., and the term "aryloxy" in this specification includes aroyloxy), heterocyclic oxy (a group in which an -O- group is bonded to the above heterocyclic group), alkoxycarbonyl (preferably an alkoxy group having 2 to 20 carbon atoms alkoxycarbonyl, for example, ethoxycarbonyl, 2-ethylhexyloxycarbonyl, dodecyloxycarbonyl, etc.), aryloxycarbonyl (preferably aryloxycarbonyl having 6 to 26 carbon atoms, for example, phenoxycarbonyl, 1-naphthyloxycarbonyl, 3-methylphenoxycarbonyl, 4-methoxyphenoxycarbonyl, etc.), amino (preferably amino, alkylamino, arylamino having 0 to 20 carbon atoms, for example, amino (-NH2), N,N-dimethylamino, N,N-diethylamino, N-ethylamino, anilino, etc.), sulfamoyl (preferably sulfamoyl having 0 to 20 carbon atoms, for example, N,N-dimethylsulfamoyl, N-phenylsulfamoyl, etc.), acyl (including alkylcarbonyl, alkenylcarbonyl, alkynylcarbonyl, arylcarbonyl, heterocyclic carbonyl, preferably acyl having 1 to 20 carbon atoms, for example, acetyl, propionyl, butyryl, octanoyl, hexadecanoyl, acryloyl, methacryloyl, crotonyl, benzoyl, naphthoyl, nicotinoyl, etc.), acyloxy (including alkylcarbonyloxy, alkenylcarbonyloxy, alkynylcarbonyloxy, arylcarbonyloxy, heterocyclic carbonyloxy, preferably acyloxy having 1 to 20 carbon atoms, for example, acetyloxy, propionyloxy, butyryloxy, octanoyloxy , hexadecanoyloxy, acryloyloxy, methacryloyloxy, crotonyloxy, benzoyloxy, naphthoyloxy, nicotinyloxy, etc.), aryloxy (preferably aryloxy having 7 to 23 carbon atoms, for example, benzoyloxy, etc.), carbamoyl (preferably carbamoyl having 1 to 20 carbon atoms, for example, N,N-dimethylcarbamoyl, N-phenylcarbamoyl, etc.), acylamino (preferably acylamino having 1 to 20 carbon atoms, for example, acetylamino, benzylamino, etc.), alkylthio (preferably alkylthio having 1 to 20 carbon atoms, for example, methylthio, ethylthio, isopropylthio , benzylthio, etc.), arylthio (preferably arylthio having 6 to 26 carbon atoms, for example, phenylthio, 1-naphthylthio, 3-methylphenylthio, 4-methoxyphenylthio, etc.), heterocyclic thio (a group in which -S- is bonded to the above heterocyclic group), alkylsulfonyl (preferably alkylsulfonyl having 1 to 20 carbon atoms, for example, methylsulfonyl, ethylsulfonyl, etc.), arylsulfonyl (preferably arylsulfonyl having 6 to 22 carbon atoms, for example, benzylsulfonyl, etc.), alkylsilyl (preferably alkylsilyl having 1 to 20 carbon atoms, for example, monomethylsilyl, dimethylsilyl , trimethylsilyl, triethylsilyl, etc.), arylsilyl (preferably arylsilyl having 6 to 42 carbon atoms, for example, triphenylsilyl, etc.), alkoxysilyl (preferably alkoxysilyl having 1 to 20 carbon atoms, for example, monomethoxysilyl, dimethoxysilyl, trimethoxysilyl, triethoxysilyl, etc.), aryloxysilyl (preferably aryloxysilyl having 6 to 42 carbon atoms, for example, triphenoxysilyl, etc.), phosphoryl (preferably phosphate having 0 to 20 carbon atoms, for example, -OP(=O)(R, P ) 2), phosphono group (preferably a phosphono group having 0 to 20 carbon atoms, for example, -P(=O)(R P ) 2), phosphinyl group (preferably a phosphinyl group having 0 to 20 carbon atoms, for example, -P(R P ) 2), phosphonic acid group (preferably a phosphonic acid group having 0 to 20 carbon atoms, for example, -PO(OR P ) 2), sulfo group (sulfonic acid group), carboxyl group, hydroxyl group, sulfanyl group, cyano group, halogen atom (such as fluorine atom, chlorine atom, bromine atom, iodine atom, etc.). Pis a hydrogen atom or a substituent (preferably a group selected from the substituent Z).
[0238] Furthermore, each group listed in these substituents Z may be further substituted by the substituents Z described above.
[0239] The above-mentioned alkyl group, alkylene group, alkenyl group, alkenylene group, alkynyl group and / or alkynylene group etc. may be cyclic or chain-shaped, and may be straight-chain or branched.
[0240] -Chain Polymerization-
[0241] The chain polymerization polymer as the polymer forming the low adsorption binder will be described.
[0242] The chain polymerization polymer preferably has a constituent having a functional group selected from the functional group group (a) or a constituent represented by the above formula (1-1), and more preferably has a constituent having the above functional group and a constituent represented by the formula (1-1), and may further have constituents different from these constituents. The chain polymerization polymer does not have a constituent having a functional group selected from the functional group group (a) or a constituent represented by the above formula (1-1), and may be a polymer composed of another constituent.
[0243] As fluorine-containing polymers, for example, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), copolymers of polyvinylidene fluoride and hexafluoropropylene (PVdF-HFP), copolymers of polyvinylidene fluoride, hexafluoropropylene and tetrafluoroethylene (PVdF-HFP-TFE) can be cited. In PVdF-HFP, the copolymerization ratio of PVdF to HFP [PVdF:HFP] (mass ratio) is not particularly limited, and is preferably 9:1 to 5:5, and is more preferably 9:1 to 7:3 from the viewpoint of adhesion. In PVdF-HFP-TFE, the copolymerization ratio of PVdF, HFP and TFE [PVdF:HFP:TFE] (mass ratio) is not particularly limited, and is preferably 20 to 60:10 to 40:5 to 30, and is more preferably 25 to 50:10 to 35:10 to 25.
[0244] As hydrocarbon polymers, for example, polyethylene, polypropylene, natural rubber, polybutadiene, polyisoprene, polystyrene, polystyrene butadiene copolymer, styrene thermoplastic elastomer, polybutene, acrylonitrile butadiene copolymer, or hydrogenated (hydrogenated) polymers thereof can be cited. As styrene thermoplastic elastomer or its hydrogenate, there is no particular limitation, for example, styrene-ethylene-butylene-styrene block copolymer (SEBS), styrene-isoprene-styrene block copolymer (SIS), hydrogenated SIS, styrene-butadiene-styrene block copolymer (SBS), hydrogenated SBS, styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS), styrene-ethylene-propylene-styrene block copolymer (SEPS), styrene-butadiene rubber (SBR), hydrogenated styrene-butadiene rubber (HSBR), and random copolymers corresponding to the above-mentioned block copolymers such as SEBS can be cited. In the present invention, the hydrocarbon-based polymer is preferred in that the polymer having no unsaturated group (such as 1,2-butadiene constituent component) bonded to the main chain can suppress the formation of chemical crosslinks.
[0245] As the ethylene polymer, for example, a polymer containing 50 mol% or more of ethylene monomers other than the (meth) acrylic acid compound (M1) can be mentioned. As the ethylene monomer, vinyl compounds described below can be mentioned. As the ethylene polymer, specifically, for example, polyvinyl alcohol, polyvinyl acetal, polyvinyl acetate or copolymers containing these can be mentioned.
[0246] The ethylene polymer preferably has a constituent derived from a (meth)acrylic acid compound (M1) forming a (meth)acrylic acid polymer described later, in addition to the constituent derived from the ethylene monomer. The content of the constituent derived from the ethylene monomer is preferably the same as the content of the constituent derived from the (meth)acrylic acid compound (M1) in the (meth)acrylic acid polymer. The content of the constituent derived from the (meth)acrylic acid compound (M1) is not particularly limited as long as it is less than 50% by mass in the polymer, and is preferably 0 to 30% by mass. The content of the constituent (MM) is preferably the same as that in the (meth)acrylic acid polymer.
[0247] As a (meth)acrylic polymer, as other constituents, it is preferred to copolymerize at least one (meth)acrylic compound (M1) selected from (meth)acrylic acid compounds, (meth)acrylic ester compounds, (meth)acrylamide compounds and (meth)acrylic nitrile compounds and obtain the polymer. In addition, it is also preferred to form a (meth)acrylic polymer composed of a copolymer of a (meth)acrylic acid compound (M1) and other polymerizable compounds (M2). As other polymerizable compounds (M2), there is no particular limitation, and vinyl compounds such as styrene compounds, vinyl naphthalene compounds, vinyl carbazole compounds, allyl compounds, vinyl ether compounds, vinyl ester compounds, itaconic acid dialkyl compounds, unsaturated carboxylic acid anhydrides and these fluorides can be cited. As a vinyl compound, for example, the "vinyl monomer" described in Japanese Patent Gazette No. 2015-88486 can be cited.
[0248] The (meth)acrylic acid compound (M1) and other polymerizable compounds (M2) may have a substituent. The substituent is not particularly limited as long as it is a group other than the functional groups included in the functional group group (a), and preferably a group selected from the substituent Z mentioned above is mentioned.
[0249] The content of the other polymerizable compound (M2) in the (meth)acrylic polymer is not particularly limited, and can be, for example, less than 50 mol %.
[0250] The (meth)acrylic acid compound (M1) and the vinyl compound (M2) as constituent components introduced into the (meth)acrylic acid polymer are preferably compounds represented by the following formula (b-1), which are different from the constituent components having the functional groups included in the functional group group (a) and the constituent components represented by the above formula (1-1).
[0251] [Chemical formula 10]
[0252]
[0253] In the formula, R 1 It represents a hydrogen atom, a hydroxyl group, a cyano group, a halogen atom, an alkyl group (preferably having 1 to 24 carbon atoms, more preferably 1 to 12, and particularly preferably 1 to 6), an alkenyl group (preferably having 2 to 24 carbon atoms, more preferably 2 to 12, and particularly preferably 2 to 6), an alkynyl group (preferably having 2 to 24 carbon atoms, more preferably 2 to 12, and particularly preferably 2 to 6), or an aryl group (preferably having 6 to 22 carbon atoms, and more preferably 6 to 14 carbon atoms). Among them, a hydrogen atom or an alkyl group is preferred, and a hydrogen atom or a methyl group is more preferred.
[0254] R 2 represents a hydrogen atom or a substituent. 2The substituent is not particularly limited and may include alkyl (may be branched, but preferably straight chain), alkenyl (preferably having 2 to 12 carbon atoms, more preferably 2 to 6, and particularly preferably 2 or 3), aryl (preferably having 6 to 22 carbon atoms, more preferably 6 to 14), aralkyl (preferably having 7 to 23 carbon atoms, more preferably 7 to 15), and cyano.
[0255] The alkyl group preferably has a carbon number of 1 to 3. The alkyl group may have, for example, a group other than the functional groups included in the functional group group (a) in the substituent Z described above.
[0256] L 1 The linking group is not particularly limited, and examples thereof include an alkylene group having 1 to 6 carbon atoms (preferably 1 to 3), an alkenylene group having 2 to 6 carbon atoms (preferably 2 to 3), an arylene group having 6 to 24 carbon atoms (preferably 6 to 10), an oxygen atom, a sulfur atom, an imino group (-NR N -:R N As mentioned above. ), carbonyl, phosphate linking group (-OP(OH)(O)-O-), phosphonic acid linking group (-P(OH)(O)-O-) or a combination thereof, preferably -CO-O-, -CO-N(R N )-base (R N As described above.). The above-mentioned linking group may have an arbitrary substituent. The number of atoms constituting the linking group and the number of connecting atoms are described below. As an arbitrary substituent, the above-mentioned substituent Z can be cited, for example, an alkyl group or a halogen atom can be cited.
[0257] n is 0 or 1, preferably 1. 1 ) n -R 2 When one substituent (such as an alkyl group) is represented, n is set to 0 and R 2 Let it be a substituent (alkyl).
[0258] The (meth)acrylic compound (M1) is preferably a compound represented by the following formula (b-2) or (b-3), which is different from the compound introduced with the constituent having the functional group included in the functional group group (a) and the constituent represented by the above formula (1-1).
[0259] [Chemical formula 11]
[0260]
[0261] R 1 and n have the same meanings as in the above formula (b-1).
[0262] R 3 With R 2 have the same meaning.
[0263] L 2 is a connecting group, which has the same meaning as L 1 have the same meaning.
[0264] L 3 is a connecting group, which has the same meaning as L 1 ] has the same meaning as , and preferably is an alkylene group having 1 to 6 (preferably 1 to 3) carbon atoms.
[0265] m is an integer of 1-200, preferably an integer of 1-100, and more preferably an integer of 1-50.
[0266] In the above formulae (b-1) to (b-3), the carbon atom that forms the polymerizable group and to which R is not bonded 1 The carbon atom in the carbon atom is represented by an unsubstituted carbon atom (H2C=), but may have a substituent. The substituent is not particularly limited, but for example, R 1 of the above groups.
[0267] In addition, in formulas (b-1) to (b-3), groups having substituents such as alkyl, aryl, alkylene, and arylene may have substituents within the range that does not impair the effects of the present invention. As substituents, any substituent other than the functional group selected from the functional group group (a) may be mentioned, for example, groups selected from the substituent Z described later, specifically, halogen atoms, etc. may be mentioned.
[0268] The (meth)acrylic polymer preferably has a constituent having a functional group selected from the functional group group (a) or a constituent represented by the above formula (1-1), and may have a constituent derived from the (meth)acrylic compound (M1), a constituent derived from the vinyl compound (M2), and other constituents capable of copolymerizing with the compound into which these constituents are introduced. From the viewpoint of dispersion stability, handling properties, and adhesion, it is preferred to have a constituent represented by the above formula (1-1) and a constituent having a functional group selected from the functional group group (a) in the (meth)acrylic compound (M1).
[0269] The content of the constituents in the (meth)acrylic polymer is not particularly limited and can be appropriately selected in consideration of the structural unit or the SP value of the polymer, and can be set, for example, in the following ranges. The content of the constituent represented by the above formula (1-1) and the constituent having a functional group selected from the functional group group (a) is as described above.
[0270] The content of the constituent components derived from the (meth)acrylic acid compound (M1) in the (meth)acrylic acid polymer is not particularly limited and may be 100 mol %, but is preferably 1 to 90 mol %, more preferably 10 to 80 mol %, and particularly preferably 20 to 70 mol %.
[0271] The content of the constituent component derived from the vinyl compound (M2) in the (meth)acrylic polymer is not particularly limited, but is preferably 1 mol % or more and less than 50 mol %, more preferably 10 mol % or more and less than 50 mol %, and particularly preferably 20 mol % or more and less than 50 mol %.
[0272] The chain polymer (each component and raw material compound) may have a substituent. The substituent is not particularly limited as long as it is a group other than the functional groups included in the functional group group (a), and preferably a group selected from the substituent Z mentioned above is mentioned.
[0273] The chain polymerization polymer can be synthesized by selecting a raw material compound by a known method and polymerizing the raw material compound.
[0274] The method for incorporating the functional group is not particularly limited, and examples thereof include a method of copolymerizing a compound having a functional group selected from the functional group group (a), a method of using a polymerization initiator or a chain transfer agent having (generating) the above functional group, a method utilizing a polymer reaction, an ene reaction in a double bond (for example, in the case of a fluoropolymer, formed by a dehydrofluorination reaction of a VDF constituent component, etc.), an ene-thiol reaction, or an ATRP (Atom Transfer Radical Polymerization) polymerization method using a copper catalyst.
[0275] (Physical properties or characteristics of low-adsorption adhesive or polymer forming low-adsorption adhesive, etc.)
[0276] It is preferred that at least one of the low adsorption binders or the polymer forming the low adsorption binder has the following properties or characteristics, etc. It is also a preferred embodiment that two or more low adsorption binders all have the following properties or characteristics, etc.
[0277] The water concentration of the low-adsorption binder (polymer) is preferably 100 ppm (mass basis) or less. The low-adsorption binder may be prepared by crystallizing the polymer and then drying it, or the low-adsorption binder dispersion may be used directly.
[0278] The polymer forming the low adsorption binder is preferably amorphous. In the present invention, the polymer being "amorphous" typically means that no endothermic peak due to melting of crystals is observed when measured at the glass transition temperature.
[0279] When the low-adsorption binder is granular, its shape is not particularly limited, and it may be flat, amorphous, etc., preferably spherical or granular. The average primary particle size of the granular low-adsorption binder is not particularly limited, and is preferably 0.1 nm or more, more preferably 1 nm or more, further preferably 5 nm or more, particularly preferably 10 nm or more, and most preferably 50 nm or more. As an upper limit, it is preferably 5.0 μm or less, more preferably 1 μm or less, further preferably 700 nm or less, and particularly preferably 500 nm or less.
[0280] The average particle size of the low-adsorption binder can be measured in the same manner as the average particle size of the inorganic solid electrolyte described above.
[0281] In addition, the average particle size of the low-adsorption binder in the constituent layer of the all-solid-state secondary battery can be measured, for example, by decomposing the battery and peeling off the constituent layer containing the low-adsorption binder, measuring the constituent layer, and removing the measured value of the particle size of particles other than the low-adsorption binder that has been measured in advance.
[0282] The average particle size of the low-adsorption binder can be adjusted by, for example, the type of dispersion medium, the content of constituent components in the polymer, and the like.
[0283] From the viewpoint of the dispersion stability of the solid particles, the polymer forming the low-adsorption binder preferably has an SP value of 10 to 24, more preferably 14 to 22, and still more preferably 16 to 20. The difference (absolute value) in SP value between the polymer forming the low-adsorption binder and the dispersion medium will be described later.
[0284] The calculation method of the SP value is described.
[0285] (1) Calculate the SP value of the structural unit.
[0286] First, for a polymer, a structural unit that specifies an SP value is determined.
[0287] That is, in the present invention, when calculating the SP value of a polymer, when the polymer (segment) is a chain polymerization polymer, it is set as a structural unit that is the same as the constituent component derived from the raw material compound, and when the polymer is a step-polymerization polymer, it is set as a unit that is different from the constituent component derived from the raw material compound.
[0288] For example, as a polymer that is polymerized stepwise, taking polyurethane as an example, the structural unit with a designated SP value is defined as follows. As a structural unit derived from a polyisocyanate compound, it is a unit (a unit having one carbamate bond) in which an -O- group is bonded to one -NH-CO- group and the remaining -NH-CO- group is removed relative to the constituent component represented by the above-mentioned formula (I-1) derived from a polyisocyanate compound. On the other hand, as a structural unit derived from a polyol compound, it is a unit (a unit having one carbamate bond) in which a -CO-NH- group is bonded to one -O- group and the remaining -O- group is removed relative to the constituent component represented by the later-described formula (I-3) derived from a polyol compound.
[0289] In addition, in the case of other stepwise polymerization polymers, as the polymer having the bond (I), the structural unit is determined in the same manner as in the case of polyurethane.
[0290] Specific examples of structural units in polyurethane (when each specific example includes parentheses or square brackets, structural units enclosed in square brackets) are shown below together with their SP values.
[0291] [Chemical formula 12]
[0292]
[0293] Next, unless otherwise specified, the SP value of each structural unit was determined by the Hoy method (see HL Hoy JOURNAL OF PAINT TECHNOLOGY Vol. 42, No. 541, 1970, 76-118 and POLYMER HANDBOOK 4 th , Chapter 59, VII 686, Table 5, Table 6 and the following formula in Table 6).
[0294] [Mathematical formula 1]
[0295]
[0296] In the formula, δ t Indicates the SP value. t Molar attraction function (J×cm 3 ) 1 / 2 / mol, represented by the following formula. V is the molar volume (cm 3 / mol), represented by the following formula. It is represented by the following formula.
[0297] F t =∑n i F t.i V=∑ni V i
[0298]
[0299] In the above formula, F t,i represents the molar attraction function of each structural unit, V i represents the molar volume of each structural unit, Δ (p) T,i Represents the correction value of each structural unit, n i Indicates the number of each structural unit.
[0300] (2) SP value of polymer
[0301] The SP value determined as described above was used to calculate the SP value according to the following formula. 1 / 2 )(For example, 1cal 1 / 2 cm -3 / 2 ≈2.05J 1 / 2 cm -3 / 2 ≈2.05MPa 1 / 2 ) and use.
[0302] SP p 2 =(SP1 2 ×W1)+(SP2 2 ×W2)+……
[0303] In the formula, SP1, SP2, ... represent the SP values of the structural units, and W1, W2, ... represent the mass fractions of the structural units.
[0304] In the present invention, the mass fraction of a structural unit refers to the mass fraction of a constituent component (a raw material compound into which the constituent component is introduced) corresponding to the structural unit in a polymer.
[0305] The SP value of a polymer can be adjusted by the type and composition (type and content of constituent components) of the polymer.
[0306] The polymer forming the low adsorption binder preferably has a small contact angle θ between the polymer film produced by the polymer film and the dispersion medium (also referred to as the contact angle θ between the dispersion medium and the polymer film) from the viewpoint of the dispersion stability of the solid particles. The polymer film referred to herein means a thin film of a polymer produced on a silicon wafer by the production method described later using the polymer forming the low adsorption binder contained in the composition containing the inorganic solid electrolyte. The production method of the polymer film and the method for measuring the contact angle are described later.
[0307] The details of the reason for improving the dispersion stability of solid particles by making the contact angle θ of the dispersion medium small relative to the polymer film are not clear, but it is considered as follows. The small contact angle of the dispersion medium relative to the polymer film of the low adsorption adhesive means that the affinity of the low adsorption adhesive to the dispersion medium is high. By improving this affinity, the osmotic pressure effect of the low adsorption adhesive in the composition (especially slurry) containing an inorganic solid electrolyte is improved, and the repulsive force acting between the low adsorption adhesives is increased. As a result, it is believed that the dispersibility of the solid particles is improved.
[0308] There is no particular limitation on the upper limit of the contact angle of the dispersion medium, but it is preferably smaller, for example, preferably less than 40°. The dispersion medium used for the measurement of the contact angle is not particularly limited as long as it is a dispersion medium used to prepare the inorganic solid electrolyte composition described later. It is preferably a dispersion medium of the same type as the dispersion medium contained in the same composition containing the inorganic solid electrolyte together with the low adsorption binder, for example, butyl butyrate can be cited. When the composition containing the inorganic solid electrolyte contains a plurality of dispersion media, the contact angle θ is measured using a dispersion medium mixture having the same composition as the dispersion medium composition in the composition.
[0309] The contact angle θ when butyl butyrate is used as the dispersion medium is not particularly limited, but is, for example, preferably 0 to 60°, more preferably 0 to 40°.
[0310] In the present invention, when the composition containing an inorganic solid electrolyte contains a plurality of low-adsorption binders, it is preferred that the above-mentioned contact angle θ be satisfied for the polymers that respectively form the low-adsorption binders.
[0311] - Fabrication of polymer films -
[0312] A solution or dispersion of a polymer forming a low-adsorption binder (the solvent or dispersion medium used is the same type of solvent or dispersion medium as the dispersion medium used to prepare the composition containing the inorganic solid electrolyte) of 100 μL is applied to a silicon wafer (3×N type, manufactured by AS ONE Corporation) using a spin coater under the following conditions, and then vacuum dried at 100°C for 2 hours to produce a polymer film of a low-adsorption binder.
[0313] Concentration of binder solution: 10% by mass
[0314] Spin coater speed: 2000rpm
[0315] Spin time of the spin coater: 5 seconds
[0316] -Determination of contact angle θ-
[0317] The contact angle θ of the dispersion medium with respect to the polymer film produced on the silicon wafer as described above is measured by the θ / 2 method in the drop method. Here, after the drop is brought into contact with the polymer film surface and dripped for 200 milliseconds, the angle between the sample surface (polymer film surface) and the drop (the angle located inside the drop) is taken as the contact angle θ.
[0318] The polymer forming the low adsorption binder may be a non-crosslinked polymer or a crosslinked polymer. Furthermore, when the polymer is crosslinked by heating or applying a voltage, the molecular weight may be greater than the above molecular weight. Preferably, when the all-solid-state secondary battery is first used, the mass average molecular weight of the polymer is in the range described below.
[0319] The mass average molecular weight of the polymer forming the low adsorption binder is not particularly limited. For example, it is preferably 15,000 or more, more preferably 30,000 or more, and further preferably 50,000 or more. The upper limit is actually 5,000,000 or less, preferably 4,000,000 or less, and more preferably 3,000,000 or less.
[0320] - Determination of Molecular Weight -
[0321] In the present invention, the molecular weight of a polymer, a polymer chain (polyether structure) and a macromonomer, unless otherwise specified, refers to the mass average molecular weight or number average molecular weight converted to standard polystyrene obtained by gel permeation chromatography (GPC). As a determination method thereof, it is basically set to the value measured by the method of the following condition 1 or condition 2 (preferred). Among them, a suitable eluent can be appropriately selected and used according to the type of the polymer or macromonomer.
[0322] (Condition 1)
[0323] Column: Two TOSOH TSKgel Super AWM-H (trade name, manufactured by TOSOH CORPORATION) connected
[0324] Carrier: 10mMLiBr / N-methylpyrrolidone
[0325] Measuring temperature: 40℃
[0326] Carrier flow rate: 1.0ml / min
[0327] Sample concentration: 0.1 mass%
[0328] Detector: RI (refractive index) detector
[0329] (Condition 2)
[0330] Column: A column connected with TOSOH TSKgel Super HZM-H, TOSOH TSKgel Super HZ4000, or TOSOH TSKgel Super HZ2000 (all trade names, manufactured by Tosoh Corporation) was used.
[0331] Carrier: Tetrahydrofuran
[0332] Measuring temperature: 40℃
[0333] Carrier flow rate: 1.0ml / min
[0334] Sample concentration: 0.1 mass%
[0335] Detector: RI (refractive index) detector
[0336] As specific examples of the polymer contained in the low adsorption binder, in addition to the polymers synthesized in the examples, the following polymers can be cited, but the present invention is not limited to these. In each specific example, the number marked on the lower right of the constituent component represents the content in the polymer, and its unit is mol%.
[0337] [Chemical formula 13]
[0338]
[0339] The composition containing an inorganic solid electrolyte of the present invention may contain one low-absorption binder or multiple binders. When containing multiple binders, there is no particular limitation, but preferably 2 to 4, and can also be 2 to 6. The preferred combination of two or more low-absorption binders will be described later.
[0340] The (total) content of the low-adsorption binder in the composition containing the inorganic solid electrolyte is not particularly limited, but is preferably 0.1 to 10.0% by mass, more preferably 0.2 to 5.0% by mass, and further preferably 0.3 to 4.0% by mass from the viewpoint of improving dispersion stability and handling properties and further showing strong adhesion. The (total) content of the low-adsorption binder in the composition containing the inorganic solid electrolyte is preferably 0.1 to 10.0% by mass, more preferably 0.3 to 8% by mass, and further preferably 0.5 to 7% by mass in 100% by mass of the solid content for the same reason.
[0341] When two or more low-adsorption adhesives are contained, the content of each low-adsorption adhesive is appropriately set within the range satisfying the above (total) content. For example, the content of one low-adsorption adhesive (for example, a low-adsorption adhesive composed of a step-polymerized polymer or a (meth) acrylic acid polymer in a more preferred combination described later) is preferably 0.01 to 5% by mass, more preferably 0.05 to 4% by mass, and further preferably 0.1 to 3% by mass in 100% by mass of the solid content. The content of the remaining low-adsorption adhesive (for example, a low-adsorption adhesive composed of a fluorine-containing polymer or a hydrocarbon polymer in a more preferred combination described later) is preferably 0.01 to 5% by mass, more preferably 0.05 to 4% by mass, and further preferably 0.1 to 3% by mass in 100% by mass of the solid content. In addition, the difference (absolute value) between the content of the above one low-adsorption adhesive in 100% by mass of the solid content and the content of the remaining low-adsorption adhesive is not particularly limited, and for example, can be set to 0 to 5% by mass, more preferably 0 to 3% by mass, and further preferably 0 to 2% by mass. In addition, the ratio of the content of the above-mentioned one low-adsorption binder in 100 mass% of the solid content to the content of the remaining low-adsorption binder (content of one low-adsorption binder / content of the remaining low-adsorption binder) is not particularly limited, for example, it is preferably 0.1 to 10, and more preferably 0.4 to 5.
[0342] When the composition containing an inorganic solid electrolyte contains a granular binder described later, the (total) content of the low-adsorption binder may be lower than the content of the granular binder, but is preferably the same or higher. Thus, the adhesion can be further enhanced without compromising the excellent dispersion stability and handling properties. In 100% by mass of the solid component, the difference (absolute value) between the (total) content of the low-adsorption binder and the content of the granular binder is not particularly limited, for example, it can be set to 0 to 6% by mass, more preferably 0 to 4% by mass, and further preferably 0 to 2% by mass. In addition, in 100% by mass of the solid component, the ratio of the (total) content of the low-adsorption binder to the content of the granular binder (the (total) content of the low-adsorption binder / the content of the granular binder) is not particularly limited, for example, preferably 1 to 4, more preferably 1 to 2.
[0343] In the present invention, the mass ratio of the total mass (total amount) of the inorganic solid electrolyte and the active material to the total mass of the polymer binder in 100% by mass of the solid content [(mass of the inorganic solid electrolyte + mass of the active material) / (total mass of the polymer binder)] is preferably in the range of 1,000 to 1. The ratio is more preferably 500 to 2, and even more preferably 100 to 10.
[0344] (granular adhesive)
[0345] The composition containing an inorganic solid electrolyte of the present invention preferably contains, as a polymer binder, one or more granular polymer binders (granular binders) that are insoluble in the dispersion medium in the composition in addition to the above-mentioned low-polarity binder. The shape of the granular binder is not particularly limited, and may be flat, amorphous, etc., preferably spherical or granular. The average particle size of the granular binder is preferably 1 to 1000 nm, more preferably 5 to 800 nm, further preferably 10 to 600 nm, and particularly preferably 50 to 500 nm. The average particle size can be measured in the same manner as the average particle size of the above-mentioned inorganic solid electrolyte.
[0346] The granular binder preferably has an adsorption rate of 60% or more with respect to the inorganic solid electrolyte. The adsorption rate with respect to the active material can be determined appropriately. The adsorption rate can be measured in the same manner as the low-adsorption binder.
[0347] If the composition containing the inorganic solid electrolyte contains a granular binder, the dispersion stability and handling improvement effect based on the low-polarity binder are not damaged, and the cohesiveness of the solid particles can be enhanced while suppressing the increase in interface resistance. As a result, for an all-solid-state secondary battery, the cycle characteristics can be further improved, and preferably further low resistance can be achieved.
[0348] As the granular binder, various granular binders for manufacturing all-solid-state secondary batteries can be used without particular limitation. For example, a granular binder composed of the above-mentioned stepwise polymerization polymer or chain polymerization polymer can be cited, specifically, polymers T-2, T-3 and D-1 synthesized in the examples can be cited. In addition, binders described in Japanese Patent Publication No. 2015-088486, International Publication No. 2018 / 020827, etc. can also be cited.
[0349] The content of the particulate binder in the composition containing the inorganic solid electrolyte is not particularly limited, but is preferably 0.01 to 4% by mass, more preferably 0.05 to 2% by mass, and further preferably 0.1 to 1% by mass in 100% by mass of the solid content from the viewpoint of improving dispersion stability and handling properties and showing strong adhesion. In addition, the content of the particulate binder can be appropriately set within the above range, but considering the solubility of the particulate binder, it is preferably a content that does not dissolve in the composition containing the inorganic solid electrolyte.
[0350] (High adsorption adhesive)
[0351] The composition containing an inorganic solid electrolyte of the present invention may contain a high-absorption binder having an adsorption rate of 60% or more relative to the inorganic solid electrolyte. The high-absorption binder is not particularly limited as long as the adsorption rate is 60% or more, and examples thereof include binders commonly used as binders for secondary batteries.
[0352] (Combination of polymer binders)
[0353] As described above, the polymer binder contained in the composition containing an inorganic solid electrolyte of the present invention only needs to include at least one low-adsorption binder, and may include two or more. When two or more are included, the number is not particularly limited, for example, preferably 2 to 5, and may also be 2 to 7.
[0354] As a method in which the polymer binder contains a low adsorption binder, there can be cited a method in which the low adsorption binder is contained alone, a method in which two or more low adsorption binders are contained, a method in which one or more low adsorption binders and a granular binder are contained, and a method in which each method also contains a high adsorption binder.
[0355] When two or more low-adsorption binders are included, the effects of dispersion stability, handling properties, and adhesion to the collector foil can be obtained at a higher level. In the method of including two or more low-adsorption binders (including the method of containing granular binders), there is no particular limitation on the low-adsorption binders used in combination, and they can be appropriately set according to the adsorption rate, the polymer forming the low-adsorption binder, the type and content of the functional group, etc. For example, if the polymer forming the low-adsorption binder is concerned, it is preferably a combination of two or more polymers selected from polymers having a polymer chain having at least one bond selected from a carbamate bond, a urea bond, an amide bond, an imide bond, and an ester bond in the main chain, or a carbon-carbon double bond, and more preferably a step-polymerized polymer or a combination of a (meth)acrylic polymer (a low-adsorption binder) and a fluorine-containing polymer or a hydrocarbon polymer (a low-adsorption binder). The fluorine-containing polymer and the hydrocarbon polymer used in combination may or may not have a constituent component represented by any one of the above formulas (1-1) to (1-5).
[0356] When the composition containing an inorganic solid electrolyte of the present invention contains a low-adsorption binder and other polymer binders as a polymer binder, the total content of the polymer binder in the composition containing an inorganic solid electrolyte is not particularly limited. From the viewpoint of dispersion stability and handleability, and thus enhanced adhesion of solid particles, it is preferably 0.01 to 10.0% by mass, more preferably 0.05 to 8% by mass, and even more preferably 0.1 to 6% by mass, based on 100% by mass of the solid content.
[0357] <Dispersion medium>
[0358] The inorganic solid electrolyte-containing composition of the present invention preferably contains a dispersion medium for dispersing the above-mentioned components.
[0359] The dispersion medium may be any organic compound that is liquid in the use environment, and examples thereof include various organic solvents, specifically, alcohol compounds, ether compounds, amide compounds, amine compounds, ketone compounds, aromatic compounds, aliphatic compounds, nitrile compounds, ester compounds, and the like.
[0360] The dispersion medium may be a non-polar dispersion medium (hydrophobic dispersion medium) or a polar dispersion medium (hydrophilic dispersion medium), and a non-polar dispersion medium is preferred from the viewpoint of being able to exhibit excellent dispersibility. A non-polar dispersion medium generally refers to a property of having low affinity for water, but in the present invention, for example, ester compounds, ketone compounds, ether compounds, aromatic compounds, aliphatic compounds, etc. may be cited.
[0361] Examples of the alcohol compound include methanol, ethanol, 1-propanol, 2-propanol, 2-butanol, ethylene glycol, propylene glycol, glycerol, 1,6-hexanediol, cyclohexanediol, sorbitol, xylitol, 2-methyl-2,4-pentanediol, 1,3-butanediol, and 1,4-butanediol.
[0362] Examples of the ether compound include alkylene glycols (diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, etc.), alkylene glycol monoalkyl ethers (ethylene glycol monomethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), alkylene glycol dialkyl ethers (ethylene glycol dimethyl, etc.), dialkyl ethers (dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, etc.), and cyclic ethers (tetrahydrofuran, dioxane (including 1,2-, 1,3-, and 1,4-isomers), etc.).
[0363] Examples of the amide compound include N,N-dimethylformamide, N-methyl-2-pyrrolidone, 2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, ε-caprolactam, formamide, N-methylformamide, acetamide, N-methylacetamide, N,N-dimethylacetamide, N-methylpropaneamide, and hexamethylphosphoric triamide.
[0364] Examples of the amine compound include triethylamine, diisopropylethylamine, and tri-n-butylamine.
[0365] Examples of the ketone compound include acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclopentanone, cyclohexanone, cycloheptanone, dipropyl ketone, dibutyl ketone, diisopropyl ketone, diisobutyl ketone (DIBK), isobutyl propyl ketone, sec-butyl propyl ketone, amyl propyl ketone, and butyl propyl ketone.
[0366] Examples of the aromatic compound include benzene, toluene, and xylene.
[0367] Examples of the aliphatic compound include hexane, heptane, octane, decane, cyclohexane, methylcyclohexane, ethylcyclohexane, cyclooctane, decalin, paraffin, gasoline, naphtha, kerosene, and light oil.
[0368] Examples of the nitrile compound include acetonitrile, propionitrile, and isobutyronitrile.
[0369] Examples of the ester compound include ethyl acetate, butyl acetate, propyl acetate, propyl butyrate, isopropyl butyrate, butyl butyrate, isobutyl butyrate, butyl valerate, ethyl isobutyrate, propyl isobutyrate, isopropyl isobutyrate, isobutyl isobutyrate, propyl pivalate, isopropyl pivalate, butyl pivalate, and isobutyl pivalate.
[0370] In the present invention, among these, ether compounds, ketone compounds, aromatic compounds, aliphatic compounds, and ester compounds are preferred, and ester compounds, ketone compounds, and ether compounds are more preferred.
[0371] The number of carbon atoms in the compound constituting the dispersion medium is not particularly limited, but is preferably 2 to 30, more preferably 4 to 20, further preferably 6 to 15, and particularly preferably 7 to 12.
[0372] From the viewpoint of the dispersion stability of solid particles, the dispersion medium has an SP value (unit: MPa). 1 / 2 ) is preferably 14 to 24, the SP value is more preferably 15 to 22, and the SP value is further preferably 16 to 20. There is no particular limitation on the difference (absolute value) in SP value between the dispersion medium and the polymer forming the low-adsorption binder. From the perspective of further improving the dispersion stability of the solid particles by extending the molecular chain of the polymer forming the low-adsorption binder in the dispersion medium to improve its own dispersibility, the difference is preferably 3 or less, more preferably 0 to 2, and further preferably 0 to 1. Regarding the above-mentioned difference in SP value (absolute value), when the composition containing an inorganic solid electrolyte of the present invention contains two or more low-adsorption binders, it is preferred that at least one low-adsorption binder satisfies the above-mentioned difference in SP value (absolute value). It is also a preferred embodiment that all low-adsorption binders satisfy the above-mentioned difference in SP value (absolute value).
[0373] The SP value of the dispersion medium is the SP value calculated by the above-mentioned Hoy method converted into a unit of MPa. 1 / 2 When the composition containing an inorganic solid electrolyte contains two or more dispersion media, the SP value of the dispersion medium refers to the SP value of the entire dispersion medium, and is set to the sum of the products of the SP value of each dispersion medium and the mass fraction. Specifically, it is calculated in the same manner as the calculation method of the SP value of the above-mentioned polymer, except that the SP value of each dispersion medium is used instead of the SP value of the constituent component.
[0374] The SP values of the dispersion media are shown below (units omitted).
[0375] MIBK (18.4), diisopropyl ether (16.8), dibutyl ether (17.9), diisobutyl ketone (17.9), DIBK (17.9), butyl butyrate (18.6), butyl acetate (18.9), toluene (18.5), ethyl cyclohexane (17.1), cyclooctane (18.8), isobutyl ethyl ether (15.3), N-methylpyrrolidone (NMP, SP value: 25.4)
[0376] The contact angle θ of the dispersion medium with respect to the polymer film is preferably small, and more preferably satisfies the above range.
[0377] The boiling point of the dispersion medium at normal pressure (1 atmosphere) is preferably 50° C. or higher, more preferably 70° C. or higher. The upper limit is preferably 250° C. or lower, more preferably 220° C. or lower.
[0378] The inorganic solid electrolyte-containing composition of the present invention only needs to contain at least one dispersion medium, and may contain two or more.
[0379] In the present invention, the content of the dispersion medium in the composition containing the inorganic solid electrolyte is not particularly limited and can be appropriately set. For example, in the composition containing the inorganic solid electrolyte, it is preferably 20 to 80% by mass, more preferably 30 to 70% by mass, and particularly preferably 40 to 60% by mass.
[0380] <Active substances>
[0381] The composition containing the inorganic solid electrolyte of the present invention may further contain an active material capable of inserting and extracting ions of metals belonging to Group 1 or Group 2 of the periodic table. As the active material, as described below, positive electrode active materials and negative electrode active materials can be cited.
[0382] In the present invention, a composition containing an inorganic solid electrolyte and containing an active material (positive electrode active material or negative electrode active material) may be referred to as an electrode composition (positive electrode composition or negative electrode composition).
[0383] (Positive electrode active material)
[0384] The positive electrode active material is preferably a positive electrode active material that can reversibly insert and remove lithium ions. As long as the material has the above-mentioned properties, there is no particular limitation, and it may be a transition metal oxide that decomposes the battery or an element that can be complexed with Li, such as sulfur.
[0385] Among them, as the positive electrode active material, it is preferred to use a transition metal oxide, and more preferably a transition metal element M a(one or more elements selected from Co, Ni, Fe, Mn, Cu and V) transition metal oxide. In addition, the element M may be mixed in the transition metal oxide. b (Metals other than lithium, elements of Group 1 (Ia) of the periodic table, elements of Group 2 (IIa), Al, Ga, In, Ge, Sn, Pb, Sb, Bi, Si, P, B, etc.) As a mixed amount, it is preferred to have an amount of 1:1 relative to the transition metal element M a The amount of Li / M is preferably 0 to 30 mol%. a The components are mixed and synthesized so that the molar ratio of them becomes 0.3 to 2.2.
[0386] Specific examples of transition metal oxides include (MA) transition metal oxides having a layered rock salt structure, (MB) transition metal oxides having a spinel structure, (MC) lithium-containing transition metal phosphate compounds, (MD) lithium-containing transition metal halophosphate compounds, and (ME) lithium-containing transition metal silicate compounds.
[0387] Specific examples of transition metal oxides having a layered rock salt structure (MA) include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0388] Specific examples of the transition metal oxide (MB) having a spinel structure include LiMn2O4 (LMO), LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8 and Li2NiMn3O8.
[0389] As (MC) lithium-containing transition metal phosphate compounds, for example, olivine-type iron phosphates such as LiFePO4 and Li3Fe2(PO4)3, pyrophosphates such as LiFeP2O7, cobalt phosphates such as LiCoPO4, and monoclinic NASICON-type vanadium phosphates such as Li3V2(PO4)3 (lithium vanadium phosphate) can be listed.
[0390] Examples of the (MD) lithium-containing transition metal halophosphate compound include iron fluorophosphates such as Li2FePO4F, manganese fluorophosphates such as Li2MnPO4F, and cobalt fluorophosphates such as Li2CoPO4F.
[0391] Examples of the (ME) lithium-containing transition metal silicate compound include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.
[0392] In the present invention, (MA) is preferably a transition metal oxide having a layered rock salt structure, and more preferably LCO or NMC.
[0393] The shape of the positive electrode active material is not particularly limited, and is preferably granular. The particle size (volume average particle size) of the positive electrode active material is not particularly limited. For example, it can be set to 0.1 to 50 μm. The particle size of the positive electrode active material particles can be measured in the same manner as the particle size of the above-mentioned inorganic solid electrolyte. In order to make the positive electrode active material a specified particle size, a conventional pulverizer or classifier is used. For example, a mortar, a ball mill, a sand mill, a vibrating ball mill, a satellite ball mill, a planetary ball mill, and a rotary airflow type jet mill or a sieve can be appropriately used. During pulverization, wet pulverization in which a dispersion medium such as water or methanol coexists can also be appropriately performed. In order to set the desired particle size, it is preferably classified. The classification is not particularly limited, and can be performed using a sieve, a wind classifier, etc. Both dry and wet classification can be used.
[0394] The positive electrode active material obtained by the calcination method may be used after being washed with water, an acidic aqueous solution, an alkaline aqueous solution, or an organic solvent.
[0395] The positive electrode active material may be used alone or in combination of two or more.
[0396] When a positive electrode active material layer is formed, the positive electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the positive electrode active material is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0397] The content of the positive electrode active material in the composition containing the inorganic solid electrolyte is not particularly limited, and is preferably 10 to 97% by mass, more preferably 30 to 95% by mass, further preferably 40 to 93% by mass, and particularly preferably 50 to 90% by mass, based on 100% by mass of the solid content.
[0398] (Negative electrode active material)
[0399] The negative electrode active material is preferably a negative electrode active material that can reversibly embed and deintercalate lithium ions. The material is not particularly limited as long as it has the above-mentioned characteristics, and carbonaceous materials, metal oxides, metal composite oxides, lithium monomers, lithium alloys, negative electrode active materials that can form alloys with lithium, etc. can be cited. Among them, from the perspective of reliability, carbonaceous materials, metal composite oxides or lithium monomers are preferably used.
[0400] The carbonaceous material used as the negative electrode active material refers to a material substantially composed of carbon. For example, carbon black such as petroleum pitch, acetylene black (AB), graphite (natural graphite, artificial graphite such as vapor-grown graphite, etc.), and various synthetic resins such as PAN (polyacrylonitrile) resin or furfuryl alcohol resin can be calcined to form the carbonaceous material. In addition, various carbon fiber types such as PAN-based carbon fiber, cellulose-based carbon fiber, asphalt-based carbon fiber, vapor-grown carbon fiber, dehydrated PVA (polyvinyl alcohol)-based carbon fiber, lignin carbon fiber, glassy carbon fiber and activated carbon fiber, mesophase microspheres, graphite whiskers and flat graphite can also be listed.
[0401] These carbonaceous materials are divided into difficult graphitization carbonaceous materials (also referred to as hard carbon) and graphite-based carbonaceous materials by the degree of graphitization. In addition, the carbonaceous material preferably has the surface spacing or density and crystallite size recorded in Japanese Patent Publication No. 62-22066, Japanese Patent Publication No. 2-6856, and Japanese Patent Publication No. 3-45473. Carbonaceous materials do not need to be a single material, and a mixture of natural graphite and artificial graphite recorded in Japanese Patent Publication No. 5-90844, and graphite with a coating layer recorded in Japanese Patent Publication No. 6-4516 can also be used.
[0402] As the carbonaceous material, hard carbon or graphite is preferably used, and graphite is more preferably used.
[0403] As oxides of metal or semi-metal elements suitable as negative electrode active materials, there are no particular restrictions as long as they are oxides that can absorb and release lithium, and examples include oxides of metal elements (metal oxides), composite oxides of metal elements or composite oxides of metal elements and semi-metal elements (collectively referred to as metal composite oxides), and oxides of semi-metal elements (semi-metal oxides). As these oxides, amorphous oxides are preferred, and further preferred examples are chalcogenides, which are reaction products of metal elements and elements of Group 16 of the periodic table. In the present invention, semi-metal elements refer to elements that show properties intermediate between metal elements and non-semi-metal elements, and generally include six elements of boron, silicon, germanium, arsenic, antimony and tellurium, and further include three elements of selenium, polonium and astatine. In addition, amorphous refers to a material having a broad scattering band with a vertex in the region of 20° to 40° at a 2θ value by an X-ray diffraction method using CuKα rays, and may also have crystalline diffraction lines. The strongest intensity among the crystalline diffraction lines appearing in the region of 40° to 70° at 2θ values is preferably 100 times or less, more preferably 5 times or less, the intensity of the diffraction line at the top of the broad scattering band appearing in the region of 20° to 40° at 2θ values, and particularly preferably a diffraction line without crystallinity.
[0404] Among the compound groups including the above-mentioned amorphous oxides and chalcogenides, amorphous oxides of semimetallic elements or the above-mentioned chalcogenides are more preferred, and (complex) oxides or chalcogenides containing one or a combination of two or more elements selected from Groups 13 (IIIB) to 15 (VB) of the periodic table (e.g., Al, Ga, Si, Sn, Ge, Pb, Sb, and Bi) are particularly preferred. Specific examples of preferred amorphous oxides and chalcogenides include, for example, Ga2O3, GeO, PbO, PbO2, Pb2O3, Pb2O4, Pb3O4, Sb2O3, Sb2O4, Sb2O8Bi2O3, Sb2O8Si2O3, Sb2O5, Bi2O3, Bi2O4, GeS, PbS, PbS2, Sb2S3, or Sb2S5.
[0405] Preferred negative electrode active materials that can be used together with the amorphous oxides containing Sn, Si, or Ge as the core include carbonaceous materials that can absorb and / or release lithium ions or lithium metal, lithium monomers, lithium alloys, and negative electrode active materials that can alloy with lithium.
[0406] From the viewpoint of high current density charge and discharge characteristics, the oxide of metal or semimetal element, especially metal (composite) oxide and the above-mentioned chalcogenide preferably contains at least one of titanium and lithium as a constituent component. As the metal composite oxide containing lithium (lithium composite metal oxide), for example, a composite oxide of lithium oxide and the above-mentioned metal (composite) oxide or the above-mentioned chalcogenide can be cited, and more specifically, Li2SnO2 can be cited.
[0407] The negative electrode active material, such as a metal oxide, preferably contains titanium (titanium oxide). Specifically, due to Li4Ti5O 12 (Lithium titanate [LTO]) has a small volume change when absorbing and releasing lithium ions, and therefore has excellent rapid charge and discharge characteristics, and is preferred in terms of suppressing electrode degradation and being able to extend the life of lithium ion secondary batteries.
[0408] The lithium alloy as the negative electrode active material is not particularly limited as long as it is an alloy generally used as a negative electrode active material for secondary batteries, and examples thereof include lithium aluminum alloys.
[0409] The negative electrode active material that can form an alloy with lithium is not particularly limited as long as it is a negative electrode active material commonly used as a secondary battery. This active material has a large expansion and contraction caused by the charge and discharge of the all-solid-state secondary battery, and accelerates the reduction of the cycle characteristics, but the composition containing the inorganic solid electrolyte of the present invention contains the above-mentioned low adsorption binder, so it can suppress the decline of the cycle characteristics. As such an active material, there can be cited (negative electrode) active materials (alloys, etc.) having silicon or tin elements, metals such as Al and In, preferably a negative electrode active material (active material containing silicon element) having silicon element that can achieve a higher battery capacity, and more preferably an active material containing silicon element having a silicon element content of more than 50 mol% of all constituent elements.
[0410] Generally, the negative electrode containing these negative electrode active materials (Si negative electrode containing active materials containing silicon elements, Sn negative electrode containing active materials having tin elements, etc.) can absorb more Li ions compared with carbon negative electrodes (graphite and acetylene black, etc.). That is, the amount of Li ions absorbed per unit mass increases. Therefore, the battery capacity can be increased. As a result, it has the advantage of being able to extend the battery driving time.
[0411] As active materials containing silicon elements, for example, silicon materials such as Si and SiOx (0<x≤1), and silicon-containing alloys (for example, LaSi2, VSi2, La-Si, Gd-Si, Ni-Si) or organized active materials (for example, LaSi2 / Si) containing titanium, vanadium, chromium, manganese, nickel, copper, lanthanum, etc., and active materials containing silicon elements such as SnSiO3 and SnSiS3 and tin elements, etc. In addition, SiOx itself can be used as a negative electrode active material (semi-metallic oxide), and Si is generated by the operation of an all-solid-state secondary battery, so it can be used as a negative electrode active material (its precursor material) that can be alloyed with lithium.
[0412] Examples of negative electrode active materials containing tin include active materials containing Sn, SnO, SnO2, SnS, SnS2, and the above-mentioned silicon and tin elements, etc. Also, composite oxides with lithium oxide, such as Li2SnO2, can be cited.
[0413] In the present invention, the above-mentioned negative electrode active material can be used without particular restrictions, but from the viewpoint of battery capacity, as the negative electrode active material, it is preferably a negative electrode active material that can alloy with lithium, among which the above-mentioned silicon material or silicon-containing alloy (alloy containing silicon element) is more preferred, and it is further preferred to contain silicon (Si) or a silicon-containing alloy.
[0414] As a measurement method, inductively coupled plasma (ICP) emission spectrometry can be used. As a simple method, the chemical formula of the compound obtained by the above-mentioned calcination method can be calculated from the mass difference of the powder before and after calcination.
[0415] The shape of the negative electrode active material is not particularly limited, and is preferably granular. The volume average particle size of the negative electrode active material is not particularly limited, and is preferably 0.1 to 60 μm. The volume average particle size of the negative electrode active material particles can be measured in the same manner as the average particle size of the inorganic solid electrolyte. In order to set the particle size to a predetermined size, a conventional pulverizer or classifier is used in the same manner as the positive electrode active material.
[0416] The above-mentioned negative electrode active materials may be used alone or in combination of two or more.
[0417] When forming a negative electrode active material layer, the negative electrode active material layer has a unit area (cm 2 The mass (mg) (weight per unit area) of the negative electrode active material is not particularly limited. It can be appropriately determined according to the designed battery capacity, for example, it can be set to 1 to 100 mg / cm 2 .
[0418] The content of the negative electrode active material in the composition containing the inorganic solid electrolyte is not particularly limited, but is preferably 10 to 90% by mass, more preferably 20 to 85% by mass, more preferably 30 to 80% by mass, and further preferably 40 to 75% by mass based on 100% by mass of the solid content.
[0419] In the present invention, when the negative electrode active material layer is formed by charging the secondary battery, ions of metals belonging to the first or second group of the periodic table generated in the all-solid-state secondary battery can be used instead of the above-mentioned negative electrode active material. The negative electrode active material layer can be formed by bonding the ions with electrons to precipitate as metal.
[0420] (Encapsulation of active substances)
[0421] The surfaces of the positive electrode active material and the negative electrode active material can also be coated with different metal oxides. As the surface coating agent, metal oxides containing Ti, Nb, Ta, W, Zr, Al, Si or Li can be listed. Specifically, titanate spinel, tantalum oxide, niobium oxide, lithium niobate compounds, etc. can be listed. Specifically, Li4Ti5O 12 , Li2Ti2O5, LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4, Li2MoO4, Li3BO3, LiBO2, Li2CO3, Li2SiO3, SiO2, TiO2, ZrO2, Al2O3, B2O3, etc.
[0422] Furthermore, the surface of the electrode including the positive electrode active material or the negative electrode active material may be surface-treated with sulfur or phosphorus.
[0423] Furthermore, the surface of the particles of the positive electrode active material or the negative electrode active material may be subjected to a surface treatment using actinic rays or an active gas (plasma, etc.) before and after the above-mentioned surface coating.
[0424] <Conductive additive>
[0425] The inorganic solid electrolyte-containing composition of the present invention preferably contains a conductive auxiliary agent. For example, it is preferable to use a conductive auxiliary agent in combination with an active material containing silicon atoms as a negative electrode active material.
[0426] There are no particular restrictions on the conductive aid, and generally known conductive aids can be used. For example, graphites such as natural graphite and artificial graphite, carbon blacks such as acetylene black, Ketjenblack, and furnace black, amorphous carbon such as needle coke, carbon fibers such as vapor-grown carbon fibers or carbon nanotubes, carbonaceous materials such as graphene or fullerene, and metal powders and metal fibers such as copper and nickel can be used. Conductive polymers such as polyaniline, polypyrrole, polythiophene, polyacetylene, and polyphenylene derivatives can also be used.
[0427] In the present invention, when an active material and a conductive aid are used in combination, among the conductive aids, when the battery is charged and discharged, the ions (preferably Li ions) of metals belonging to the first or second group of the periodic table are not embedded and deintercalated, and those that do not function as active materials are used as conductive aids. Therefore, among the conductive aids, those that can function as active materials in the active material layer when the battery is charged and discharged are classified as active materials rather than conductive aids. Whether or not to function as an active material when the battery is charged and discharged is determined by the combination with the active material, rather than being determined in general.
[0428] The conductive auxiliary agent may be contained alone or in combination of two or more.
[0429] The shape of the conductive additive is not particularly limited, but is preferably in a granular form.
[0430] When the inorganic solid electrolyte-containing composition of the present invention contains a conductive auxiliary agent, the content of the conductive auxiliary agent in the inorganic solid electrolyte-containing composition is preferably 0 to 10% by mass based on 100% by mass of the solid content.
[0431] <Lithium salt>
[0432] The inorganic solid electrolyte-containing composition of the present invention preferably further contains a lithium salt (supporting electrolyte).
[0433] The lithium salt is preferably a lithium salt commonly used for such products, without particular limitation. For example, the lithium salts described in paragraphs 0082 to 0085 of JP-A-2015-088486 are preferred.
[0434] When the composition containing an inorganic solid electrolyte of the present invention contains a lithium salt, the content of the lithium salt is preferably 0.1 parts by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the solid electrolyte. As an upper limit, it is preferably 50 parts by mass or less, more preferably 20 parts by mass or less.
[0435] <Dispersant>
[0436] In the composition containing an inorganic solid electrolyte of the present invention, the above-mentioned low adsorption binder also acts as a dispersant, so it may not contain a dispersant other than the low adsorption binder, or it may contain a dispersant. As a dispersant, a dispersant commonly used in all-solid-state secondary batteries can be appropriately selected for use. Usually, the desired compound in particle adsorption, steric repulsion and / or electrostatic repulsion is appropriately used.
[0437] <Other additives>
[0438] The composition containing inorganic solid electrolyte of the present invention can appropriately contain ionic liquid, thickener, crosslinking agent (substances that undergo crosslinking reaction by free radical polymerization, polycondensation or ring-opening polymerization, etc.), polymerization initiator (substances that generate acid or free radicals by heat or light, etc.), defoamer, leveling agent, dehydrating agent, antioxidant, etc. as other ingredients other than the above-mentioned components. Ionic liquid is a liquid contained in order to further improve ionic conductivity, and known liquids can be used without particular restrictions. In addition, polymers other than the polymers that form the above-mentioned polymer binder may contain commonly used binders, etc.
[0439] (Preparation of Composition Containing Inorganic Solid Electrolyte)
[0440] The composition containing an inorganic solid electrolyte of the present invention can be prepared as a mixture, preferably as a slurry, by mixing an inorganic solid electrolyte, the above-mentioned low adsorption binder as a polymer binder, a dispersion medium, preferably a polymer binder other than the low adsorption binder (e.g., a granular binder), a conductive aid, and an appropriate lithium salt, and any other components in various commonly used mixers. In the case of an electrode composition, an active material is further mixed.
[0441] The mixing method is not particularly limited, and the mixture may be mixed all at once or sequentially. The mixing environment is not particularly limited, and examples thereof include dry air or inert gas.
[0442] [Sheet for all-solid-state secondary batteries]
[0443] The sheet material for all-solid-state secondary batteries of the present invention is a sheet-like molded body capable of forming a constituent layer of an all-solid-state secondary battery, and includes various modes according to its use. For example, a sheet material preferably used for a solid electrolyte layer (also referred to as a solid electrolyte sheet for an all-solid-state secondary battery), a sheet material preferably used for a laminate of an electrode or an electrode and a solid electrolyte layer (electrode sheet for an all-solid-state secondary battery), etc. can be cited. In the present invention, these various sheets are collectively referred to as sheets for all-solid-state secondary batteries.
[0444] The solid electrolyte sheet for an all-solid-state secondary battery of the present invention can be a sheet having a solid electrolyte layer, and can be a sheet having a solid electrolyte layer formed on a substrate, or can be a sheet having no substrate and formed by a solid electrolyte layer. The solid electrolyte sheet for an all-solid-state secondary battery can also have other layers in addition to the solid electrolyte layer. As other layers, for example, a protective layer (peel-off sheet), a current collector, a coating, etc. can be cited.
[0445] As a solid electrolyte sheet for an all-solid-state secondary battery of the present invention, for example, a sheet having a layer composed of a composition containing an inorganic solid electrolyte of the present invention, a common solid electrolyte layer and a protective layer in sequence on a substrate can be cited. The solid electrolyte layer possessed by the solid electrolyte sheet for an all-solid-state secondary battery is preferably formed by a composition containing an inorganic solid electrolyte of the present invention. The content of each component in the solid electrolyte layer is not particularly limited, and the preferred meaning is the same as the content of each component in the solid component of the composition containing an inorganic solid electrolyte of the present invention. The thickness of each layer constituting the solid electrolyte sheet for an all-solid-state secondary battery is the same as the thickness of each layer described in the all-solid-state secondary battery described later.
[0446] As a substrate, as long as it is a substrate that can support a solid electrolyte layer, it is not particularly limited, and can include sheet bodies (plate bodies) such as materials described in the collector described later, organic materials, and inorganic materials. As organic materials, various polymers can be listed, specifically, polyethylene terephthalate, polypropylene, polyethylene, and cellulose can be listed. As inorganic materials, for example, glass and ceramics can be listed.
[0447] The electrode sheet for all-solid-state secondary batteries of the present invention (also referred to as "electrode sheet" for short) can be an electrode sheet with an active material layer, and can be a sheet in which the active material layer is formed on a substrate (collector), or can be a sheet without a substrate and formed by an active material layer. The electrode sheet is usually a sheet with a collector and an active material layer, but also includes a form having a collector, an active material layer and a solid electrolyte layer in sequence, and a form having a collector, an active material layer, a solid electrolyte layer and an active material layer in sequence. The solid electrolyte layer and active material layer possessed by the electrode sheet are preferably formed by a composition containing an inorganic solid electrolyte of the present invention. The content of each component in the solid electrolyte layer or the active material layer is not particularly limited, and the preferred meaning is the same as the content of each component in the solid component of the composition containing an inorganic solid electrolyte (electrode composition) of the present invention. The thickness of each layer constituting the electrode sheet of the present invention is the same as the thickness of each layer described in the all-solid-state secondary battery described later. The electrode sheet of the present invention may have the above-mentioned other layers.
[0448] In the all-solid-state secondary battery sheet of the present invention, at least one layer in the solid electrolyte layer and the active material layer is formed by the composition containing an inorganic solid electrolyte of the present invention, with a flat surface and a low-resistance constituent layer. Therefore, the all-solid-state secondary battery sheet of the present invention is used as the constituent layer of the all-solid-state secondary battery, thereby enabling the excellent cycle characteristics and low resistance (high conductivity) of the all-solid-state secondary battery. In particular, in the all-solid-state secondary battery electrode sheet and the all-solid-state secondary battery in which the active material layer is formed by the composition containing an inorganic solid electrolyte of the present invention, the active material layer and the collector show a firm adhesion, and further improvement of the cycle characteristics can be achieved. Therefore, the all-solid-state secondary battery sheet of the present invention is suitable for use as a sheet capable of forming the constituent layer of an all-solid-state secondary battery.
[0449] [Method for producing a sheet for an all-solid-state secondary battery]
[0450] The manufacturing method of the sheet material for all-solid-state secondary batteries of the present invention is not particularly limited, and the above-mentioned layers can be formed using the composition containing an inorganic solid electrolyte of the present invention and manufactured. For example, it is preferred to cite a method of forming a layer (coating and drying layer) consisting of a composition containing an inorganic solid electrolyte on a substrate or a collector (may be via another layer.). Thus, a sheet material for all-solid-state secondary batteries having a substrate or a collector and a coating and drying layer can be made. In particular, when the composition containing an inorganic solid electrolyte of the present invention is film-formed on a collector to make a sheet material for all-solid-state secondary batteries, the close fit of the collector and the active material layer can be made firm. Here, the coating and drying layer refers to a layer formed by applying a composition containing an inorganic solid electrolyte of the present invention and drying a dispersion medium (that is, a layer formed by using a composition containing an inorganic solid electrolyte of the present invention, and removing a composition containing an inorganic solid electrolyte from the composition containing an inorganic solid electrolyte of the present invention). The dispersion medium may remain in the active material layer and the dried coating layer within a range that does not impair the effects of the present invention, and the residual amount may be, for example, 3% by mass or less in each layer.
[0451] In the method for producing the sheet for an all-solid-state secondary battery of the present invention, each step such as coating and drying will be described below in the method for producing an all-solid-state secondary battery.
[0452] In the method for producing the all-solid-state secondary battery sheet of the present invention, the applied dried layer obtained in the above manner may be pressurized. The pressurization conditions and the like will be described in the method for producing the all-solid-state secondary battery described later.
[0453] Furthermore, in the method for producing the sheet for an all-solid-state secondary battery of the present invention, the substrate, the protective layer (particularly the release sheet), and the like can also be peeled off.
[0454] [All-solid-state secondary battery]
[0455] The all-solid-state secondary battery of the present invention comprises a positive electrode active material layer, a negative electrode active material layer opposite to the positive electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer. The positive electrode active material layer is preferably formed on the positive electrode collector and constitutes the positive electrode. The negative electrode active material layer is preferably formed on the negative electrode collector and constitutes the negative electrode.
[0456] At least one of the negative electrode active material layer, the positive electrode active material layer and the solid electrolyte layer is formed by the composition containing an inorganic solid electrolyte of the present invention, and preferably at least one of the solid electrolyte layer or the negative electrode active material layer and the positive electrode active material layer is formed by the composition containing an inorganic solid electrolyte of the present invention. It is also one of the preferred modes that all layers are formed by the composition containing an inorganic solid electrolyte of the present invention. For the types of components contained and their content ratios, the active material layer or solid electrolyte layer formed by the composition containing an inorganic solid electrolyte of the present invention is preferably the same as the solid component of the composition containing an inorganic solid electrolyte of the present invention. In addition, when the active material layer or the solid electrolyte layer is not formed by the composition containing an inorganic solid electrolyte of the present invention, known materials can be used.
[0457] The thickness of each of the negative electrode active material layer, the solid electrolyte layer and the positive electrode active material layer is not particularly limited. Considering the size of a general all-solid-state secondary battery, the thickness of each layer is preferably 10 to 1,000 μm, more preferably 20 μm or more and less than 500 μm. In the all-solid-state secondary battery of the present invention, the thickness of at least one of the positive electrode active material layer and the negative electrode active material layer is further preferably 50 μm or more and less than 500 μm.
[0458] Each of the positive electrode active material layer and the negative electrode active material layer may include a current collector on the side opposite to the solid electrolyte layer.
[0459] <Frame>
[0460] The all-solid-state secondary battery of the present invention can be used as an all-solid-state secondary battery in the state of the above structure according to the purpose, but in order to make it in the form of a dry cell, it is preferably further enclosed in an appropriate shell for use. The shell can be a metallic shell or a resin (plastic) shell. In the case of using a metallic shell, for example, a shell made of aluminum alloy or stainless steel can be cited. Preferably, the metallic shell is divided into a positive electrode side shell and a negative electrode side shell and is electrically connected to the positive electrode collector and the negative electrode collector, respectively. Preferably, the shell on the positive electrode side is joined to the shell on the negative electrode side via a short circuit prevention gasket and becomes one.
[0461] Below, reference Figure 1, an all-solid-state secondary battery according to a preferred embodiment of the present invention is described, but the present invention is not limited thereto.
[0462] Figure 1 This is a cross-sectional view schematically showing an all-solid-state secondary battery (lithium-ion secondary battery) according to a preferred embodiment of the present invention. When viewed from the negative electrode side, the all-solid-state secondary battery 10 of this embodiment has a negative electrode collector 1, a negative electrode active material layer 2, a solid electrolyte layer 3, a positive electrode active material layer 4, and a positive electrode collector 5 in sequence. Each layer is in contact with each other and has an adjacent structure. By adopting such a structure, electrons (e) are supplied to the negative electrode side during charging. - ) and accumulate lithium ions (Li + On the other hand, during discharge, the lithium ions (Li + ) returns to the positive electrode side, and supplies electrons to the working portion 6. In the example shown in the figure, a light bulb is used as a model in the working portion 6, and the light bulb is lit by discharge.
[0463] In will have Figure 1 When the all-solid-state secondary battery with the layer structure shown is placed in a 2032-type button-type battery box, the all-solid-state secondary battery is sometimes also referred to as a laminate for an all-solid-state secondary battery, and the battery produced by placing the all-solid-state secondary battery laminate in a 2032-type button-type battery box is called an all-solid-state secondary battery.
[0464] (Positive electrode active material layer, solid electrolyte layer, negative electrode active material layer)
[0465] In the all-solid-state secondary battery 10, the positive electrode active material layer, the solid electrolyte layer and the negative electrode active material layer are all formed by the composition containing the inorganic solid electrolyte of the present invention. The all-solid-state secondary battery 10 shows excellent battery performance. The inorganic solid electrolyte and the polymer binder (low adsorption binder) contained in the positive electrode active material layer 4, the solid electrolyte layer 3 and the negative electrode active material layer 2 can be the same type or different types.
[0466] In the present invention, either or both of the positive electrode active material layer and the negative electrode active material layer are simply referred to as active material layer or electrode active material layer. Also, either or both of the positive electrode active material and the negative electrode active material are simply referred to as active material or electrode active material.
[0467] In the present invention, when the constituent layers are formed from the composition containing the inorganic solid electrolyte of the present invention, an all-solid-state secondary battery having excellent cycle characteristics and an all-solid-state secondary battery having low resistance can be realized.
[0468] In the all-solid-state secondary battery 10 , the negative electrode active material layer can be a lithium metal layer.
[0469] Examples of the lithium metal layer include a layer formed by depositing or molding lithium metal powder, lithium foil, and lithium vapor-deposited film. The thickness of the lithium metal layer is independent of the thickness of the negative electrode active material layer, and can be, for example, 1 to 500 μm.
[0470] The positive electrode current collector 5 and the negative electrode current collector 1 are preferably electron conductors.
[0471] In the present invention, either the positive electrode current collector or the negative electrode current collector, or both of them together, may be simply referred to as a current collector.
[0472] As the material forming the positive electrode collector, in addition to aluminum, aluminum alloy, stainless steel, nickel and titanium, it is preferred to treat the surface of aluminum or stainless steel with carbon, nickel, titanium or silver (forming a thin film), among which aluminum and aluminum alloy are more preferred.
[0473] As the material for forming the negative electrode collector, in addition to aluminum, copper, copper alloys, stainless steel, nickel and titanium, it is preferred to use a material in which the surface of aluminum, copper, copper alloys or stainless steel is treated with carbon, nickel, titanium or silver, and aluminum, copper, copper alloys and stainless steel are more preferred.
[0474] The shape of the current collector is generally a film sheet, but a mesh, a perforated body, a lath body, a porous body, a foamed body, a molded body of a fiber group, or the like may also be used.
[0475] The thickness of the current collector is not particularly limited, but is preferably 1 to 500 μm. It is also preferred that the surface of the current collector be provided with irregularities by surface treatment.
[0476] In the above-described all-solid-state secondary battery 10 , the positive electrode active material layer can also be formed of a layer formed of a known constituent layer forming material.
[0477] In the present invention, functional layers, components, etc. may be appropriately inserted or arranged between or outside the negative electrode collector, the negative electrode active material layer, the solid electrolyte layer, the positive electrode active material layer, and the positive electrode collector. Furthermore, each layer may be configured as a single layer or as a multilayer.
[0478] [Manufacturing of all-solid-state secondary batteries]
[0479] The all-solid-state secondary battery can be manufactured by a conventional method. Specifically, the all-solid-state secondary battery can be manufactured by forming the above-mentioned layers using the composition containing the inorganic solid electrolyte of the present invention. This will be described in detail below.
[0480] The all-solid-state secondary battery of the present invention can be manufactured by a method (manufacturing method of a sheet for an all-solid-state secondary battery of the present invention) comprising (via) a step of appropriately coating the composition containing an inorganic solid electrolyte of the present invention on a substrate (e.g., a metal foil serving as a current collector) to form a coating (film formation).
[0481] For example, a composition containing an inorganic solid electrolyte as a positive electrode material (positive electrode composition) and containing a positive electrode active material is applied to a metal foil as a positive electrode collector to form a positive electrode active material layer to make a positive electrode sheet for an all-solid-state secondary battery. Next, a composition containing an inorganic solid electrolyte for forming a solid electrolyte layer is applied to the positive electrode active material layer to form a solid electrolyte layer. In addition, a negative electrode active material layer is formed by applying a composition containing an inorganic solid electrolyte as a negative electrode material (negative electrode composition) on the solid electrolyte layer. By overlapping the negative electrode collector (metal foil) on the negative electrode active material layer, an all-solid-state secondary battery with a structure in which a solid electrolyte layer is sandwiched between the positive electrode active material layer and the negative electrode active material layer can be obtained. It can also be enclosed in a shell as a desired all-solid-state secondary battery.
[0482] Furthermore, in contrast to the method of forming each layer, an all-solid-state secondary battery can be manufactured by forming a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer on a negative electrode collector and stacking the positive electrode collector.
[0483] As other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery is prepared as described above. Furthermore, a composition containing an inorganic solid electrolyte as a negative electrode material (negative electrode composition) and containing a negative electrode active material is applied to a metal foil as a negative electrode collector to form a negative electrode active material layer to prepare a negative electrode sheet for an all-solid-state secondary battery. Next, on the active material layer of any one of these sheets, a solid electrolyte layer is formed as described above. Furthermore, on the solid electrolyte layer, another of the positive electrode sheet for an all-solid-state secondary battery and the negative electrode sheet for an all-solid-state secondary battery are stacked in such a manner that the solid electrolyte layer is in contact with the active material layer. In this way, an all-solid-state secondary battery can be manufactured.
[0484] Furthermore, as other methods, the following methods can be cited. That is, a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery are prepared as described above. In addition, a solid electrolyte sheet for an all-solid-state secondary battery consisting of a solid electrolyte layer is prepared by applying a composition containing an inorganic solid electrolyte to a substrate. Moreover, the solid electrolyte layer peeled off from the substrate is sandwiched by a positive electrode sheet for an all-solid-state secondary battery and a negative electrode sheet for an all-solid-state secondary battery. In this way, an all-solid-state secondary battery can be manufactured.
[0485] The solid electrolyte layer and the like are formed, for example, by pressure-molding a composition containing an inorganic solid electrolyte and the like on a substrate or an active material layer under pressure conditions described later.
[0486] In the above-mentioned manufacturing method, the composition containing an inorganic solid electrolyte of the present invention can be used for any one of the positive electrode composition, the composition containing an inorganic solid electrolyte and the negative electrode composition. It is preferred to use the composition containing an inorganic solid electrolyte of the present invention for the composition containing an inorganic solid electrolyte, and the composition containing an inorganic solid electrolyte of the present invention can also be used for any composition.
[0487] <Formation of each layer (film formation)>
[0488] The method for coating the composition containing the inorganic solid electrolyte is not particularly limited and can be appropriately selected, and examples thereof include coating (preferably wet coating), spray coating, spin coating, dip coating, slit coating, stripe coating, and bar coating.
[0489] At this time, the composition containing the inorganic solid electrolyte can be dried after being coated separately, or it can be dried after being coated in multiple layers. There is no particular restriction on the drying temperature. The lower limit is preferably above 30°C, more preferably above 60°C, and more preferably above 80°C. The upper limit is preferably below 300°C, more preferably below 250°C, and more preferably below 200°C. By heating within such a temperature range, the dispersion medium can be removed to obtain a solid state (coating dry layer). Moreover, the temperature will not be too high and the components of the all-solid-state secondary battery will not be damaged, so it is preferred. As a result, in the all-solid-state secondary battery, excellent overall performance is exhibited and good adhesion and good ion conductivity can be obtained without pressurization.
[0490] As described above, when the inorganic solid electrolyte-containing composition of the present invention is applied and dried, the solid particles can be bonded while suppressing the variation in contact state, and a coated and dried layer having a flat surface can be formed.
[0491] Preferably, after applying the composition containing the inorganic solid electrolyte, each layer or the all-solid-state secondary battery is pressurized after overlapping the constituent layers or after making the all-solid-state secondary battery. In addition, it is also preferred to pressurize in a state where each layer is stacked. As a pressurization method, a hydraulic cylinder punching machine or the like can be cited. There is no particular limitation on the pressure, and it is usually preferably in the range of 5 to 1500 MPa.
[0492] Furthermore, the applied composition containing an inorganic solid electrolyte may be heated while being pressurized. The heating temperature is not particularly limited, but is generally in the range of 30 to 300° C. Punching may also be performed at a temperature higher than the glass transition temperature of the inorganic solid electrolyte. In addition, punching may also be performed at a temperature higher than the glass transition temperature of the polymer contained in the polymer binder. However, it is generally a temperature not exceeding the melting point of the polymer.
[0493] The pressurization may be performed in a state where the coating solvent or dispersion medium is dried in advance, or may be performed in a state where the solvent or dispersion medium remains.
[0494] In addition, the respective compositions may be applied simultaneously, or applied, dried, and pressed simultaneously and / or sequentially. After being applied to respective substrates, the compositions may be laminated by transfer.
[0495] The pressurized environment is not particularly limited, and may be any environment such as atmospheric pressure, dry air (dew point -20°C or lower), or an inert gas (for example, argon, helium, or nitrogen).
[0496] The punching time can be a short time (e.g., within a few hours) to apply high pressure, or a long time (more than 1 day) to apply moderate pressure. In addition to the sheet for all-solid-state secondary batteries, for example, in the case of all-solid-state secondary batteries, it is possible to use a restraining tool (screw tightening pressure, etc.) of the all-solid-state secondary battery to continuously apply moderate pressure.
[0497] The pressing pressure may be uniform or different relative to the pressure receiving portion such as the sheet surface.
[0498] The pressing pressure can be changed according to the area or film thickness of the pressure receiving portion, and the pressure can be changed in stages to different pressures on the same portion.
[0499] The stamping surface can be smooth or rough.
[0500] <Initialization>
[0501] The all-solid-state secondary battery manufactured in the above manner is preferably initialized after manufacturing or before use. There is no particular limitation on initialization, for example, initial charging and discharging can be performed under an increased stamping pressure, and then the pressure is released until the general use pressure of the all-solid-state secondary battery is reached.
[0502] [Applications of all-solid-state secondary batteries]
[0503] The all-solid-state secondary battery of the present invention can be applied to a variety of purposes. The applicable mode is not particularly limited. For example, when it is mounted on an electronic device, a notebook computer, a pen input computer, a mobile computer, an e-book reader, a mobile phone, a wireless telephone sub-machine, a pager, a handheld terminal, a portable fax machine, a portable copier, a portable printer, a stereo headset, a camcorder, a liquid crystal television, a portable vacuum cleaner, a portable CD, a small disk, an electric shaver, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, etc. As other civilian products, automobiles, electric vehicles, motors, lighting fixtures, toys, game consoles, load regulators, clocks, flashlights, cameras, and medical equipment (pacemakers, hearing aids, and shoulder massagers, etc.) can be listed. Moreover, it can be used as various military products and aviation products. Moreover, it can also be combined with solar cells.
[0504] Example
[0505] The present invention will be described in further detail below with reference to the Examples, but the present invention is not limited thereto and should not be construed. In the following Examples, "parts" and "%" representing the composition are by mass unless otherwise specified. In the present invention, "room temperature" means 25°C.
[0506] 1. Synthesis of polymers and preparation of adhesive solutions or dispersions
[0507] The polymers shown in the following chemical formula and Table 1-1 and Table 1-2 (collectively referred to as Table 1) were synthesized as follows.
[0508] [Synthesis Example 1: Synthesis of polymer S-1 and preparation of binder solution S-1]
[0509] Polymer S-1 was synthesized, and a butyl butyrate solution S-1 of the polymer was prepared.
[0510] 28.80 g of NISSO-PB GI1000 (trade name, manufactured by Nippon Soda Co., Ltd.) and 1.92 g of polypropylene glycol (PPG400, manufactured by FUJIFILM Wako Pure Chemical Corporation) were added to a 200 mL three-necked flask and dissolved in 55.5 g of butyl butyrate (manufactured by Tokyo Chemical Industry Co., Ltd.). 6.30 g of dicyclohexylmethane-4,4'-diisocyanate (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the solution and stirred at 80°C to uniformly dissolve it. 100 mg of NEOSTANN U-600 (trade name, manufactured by NITTOH CHEMICAL Co., Ltd.) was added to the obtained solution and stirred at 80°C for 10 hours to synthesize polymer S-1 (polyurethane), thereby obtaining a solution S-1 (concentration 40 mass %) of an adhesive composed of polymer S-1.
[0511] [Synthesis Example 2: Synthesis of Polymer S-2 (Preparation of Binder Solution S-2)]
[0512] In Synthesis Example 1, a compound for introducing each constituent component is used to make the polymer S-2 have the composition (type and content of constituent components) shown in Table 1. In addition, polymer S-2 (polyurethane) is synthesized in the same manner as in Synthesis Example 1 to obtain a solution S-2 of an adhesive composed of polymer S-2.
[0513] [Synthesis Example 3: Synthesis of polymer S-3 (preparation of binder solution S-3)]
[0514] 180 g of NISSO-PB G3000 (trade name, manufactured by Nippon Soda Co., Ltd.) and 9.8 g of dimethyl adipate were added to a 500 mL three-necked flask and stirred. 50 mg of tetrabutyl orthotitanic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was added to the solution and stirred at 190° C. for 8 hours. After the solution was allowed to stand at room temperature, 190 g of butyl butyrate was added and stirred to uniformly dissolve.
[0515] In this way, polymer S-3 (polyester) was synthesized, and a binder solution S-3 composed of polymer S-3 was obtained.
[0516] [Synthesis Example 4: Synthesis of polymer S-4 (preparation of binder solution S-4)]
[0517] 6.39 g of glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 27.3 g of dodecyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.36 g of polymerization initiator V-601 (trade name, manufactured by FUJIFILM Wako Pure Chemical Corporation) were added to a 100 mL volumetric flask and dissolved in 36 g of butyl butyrate to prepare a monomer solution. 18 g of butyl butyrate was added to a 300 mL three-necked flask and the above monomer solution was added dropwise under stirring at 80° C. for 2 hours. After the addition was completed, the temperature was raised to 90° C. and stirred for 2 hours to synthesize polymer S-4 (methacrylic acid polymer), and a solution S-4 (concentration 40% by mass) of an adhesive composed of polymer S-4 was obtained.
[0518] [Synthesis Examples 5 to 18, 35: Synthesis of polymers S-5 to S-18, S-35 (Preparation of binder solutions S-5 to S-18, S-35)]
[0519] In Synthesis Example 4, polymers S-5 to S-18 and S-35 were synthesized in the same manner as in Synthesis Example 4 ((meth)acrylic acid polymers or ethylene polymers) to obtain solutions S-5 to S-18 and S-35 of adhesives composed of the polymers, respectively. In addition, polymer S-7 was insoluble in butyl butyrate, and an adhesive composed of polymer S-7 was obtained as dispersion S-7. The average particle size of the adhesive in the dispersion was 250 nm.
[0520] [Synthesis Example 19: Synthesis of polymer S-19 (preparation of binder solution S-19)]
[0521] 100 parts by mass of ion exchange water, 48 parts by mass of vinylidene fluoride, 30 parts by mass of hexafluoropropylene and 22 parts by mass of tetrafluoroethylene were added to the autoclave, and 2 parts by mass of a polymerization initiator PEROYL IPP (trade name, chemical name: diisopropyl peroxydicarbonate, manufactured by NOF CORPORATION) were further added, and stirred at 40°C for 24 hours. After stirring, the precipitate was filtered and dried at 100°C for 10 hours. 40 parts by mass of butyl butyrate was added to 10 parts by mass of the obtained polymer and dissolved to synthesize polymer S-19 (vinylidene fluoride-hexafluoropropylene-tetrafluoropropylene terpolymer), thereby obtaining a solution S-19 (polymer concentration 20% by mass) of an adhesive composed of polymer S-19.
[0522] [Synthesis Example 20: Synthesis of polymer S-20 (preparation of binder solution S-20)]
[0523] 100 parts by mass of ion exchange water, 68 parts by mass of vinylidene fluoride and 32 parts by mass of hexafluoropropylene were added to the autoclave, and 2 parts by mass of a polymerization initiator PEROYL IPP (trade name, chemical name: diisopropyl peroxydicarbonate, manufactured by NOFCORPORATION) were further added, and stirred at 40°C for 24 hours. After stirring, the precipitate was filtered and dried at 100°C for 10 hours. 40 parts by mass of butyl butyrate was added to 10 parts by mass of the obtained polymer and dissolved to synthesize polymer S-20 (vinylidene fluoride-hexafluoropropylene binary copolymer), thereby obtaining a solution S-20 (polymer concentration 20% by mass) of an adhesive composed of polymer S-20.
[0524] [Synthesis Example 21: Synthesis of polymer S-21 (preparation of binder solution S-21)]
[0525] A fluorine-based copolymer S-21 was synthesized, and a binder solution S-21 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0526] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-19 synthesized in Synthesis Example 19 were added to a 500 mL three-necked flask with a reflux cooling tube, and 0.23 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was dropped into water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor (S-21).
[0527] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-21) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 12 parts by mass of dodecanethiol and 0.5 parts by mass of azobisisobutyronitrile (made by FUJIFILM Wako PureChemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-21 as a precipitate. The reduced pressure drying at 60°C was carried out for 5 hours and then dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-21 (concentration 10% by mass).
[0528] [Synthesis Example 22: Synthesis of polymer S-22 (preparation of binder solution S-22)]
[0529] A fluorine-based copolymer S-22 was synthesized, and an adhesive solution S-22 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0530] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-19 synthesized in Synthesis Example 19 were added to a 500 mL three-necked flask with a reflux cooling tube, and 0.23 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was dropped into water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor (S-22).
[0531] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-22) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 6 parts by mass of 6-mercapto-1-hexanol and 0.6 parts by mass of azobisisobutyronitrile (made by FUJIFILM Wako PureChemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-22 as a precipitate. The reduced pressure drying at 60°C was carried out for 5 hours and then dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-22 (concentration 10% by mass).
[0532] [Synthesis Example 23: Synthesis of polymer S-23 (preparation of binder solution S-23)]
[0533] A fluorine-based copolymer S-23 was synthesized, and a binder solution S-23 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0534] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-19 synthesized in Synthesis Example 19 were added to a 2L three-necked flask with a reflux cooling tube, and 0.23 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was dropped into water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor (S-23).
[0535] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-23) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 3 parts by mass of mercaptopropionic acid and 0.6 parts by mass of azobisisobutyronitrile (made by FUJIFILM Wako PureChemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-23 as a precipitate. The reduced pressure drying at 60°C was carried out for 5 hours and then dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-23 (concentration 10% by mass).
[0536] [Synthesis Example 24: Synthesis of polymer S-24 (preparation of binder solution S-24)]
[0537] A fluorine-based copolymer S-24 was synthesized, and an adhesive solution S-24 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0538] Specifically, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-23) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 3 parts by mass of 6-mercapto-1-hexanol and 0.6 parts by mass of azobisisobutyronitrile (made by FUJIFILM WakoPure Chemical Corporation) were added, and stirring was continued for 5 hours, and 7 parts by mass of maleic anhydride were added, and stirring was further carried out for 2 hours. Then, it was added dropwise to hexane, and fluorine-based copolymer S-24 was obtained as a precipitate. After the reduced pressure drying at 60°C was carried out for 5 hours, it was dissolved in any solvent again. The obtained fluorine-based copolymer was dissolved in butyl butyrate, and an adhesive solution S-24 (concentration 10% by mass) was obtained.
[0539] [Synthesis Example 25: Synthesis of polymer S-25 (preparation of binder solution S-25)]
[0540] A fluorine-based copolymer S-25 was synthesized, and an adhesive solution S-25 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0541] Specifically, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-21) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min for 10 minutes and the temperature was raised to 75°C, and 22 parts by mass of 1H, 1H, 2H, 2H-perfluorodecanethiol and 1 part by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-25 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-25 (concentration 10% by mass).
[0542] [Synthesis Example 26: Synthesis of polymer S-26 (preparation of binder solution S-26)]
[0543] A fluorine-based copolymer S-26 was synthesized, and an adhesive solution S-26 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0544] Specifically, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the fluorine-based copolymer S-19 synthesized in Synthesis Example 19 were added to a 300 mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, 47.3 parts by mass of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 22.8 parts by mass of 1H, 1H, 2H, 2H-tridecafluorooctyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.1 parts by mass of copper chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 0.5 parts by mass of 4,4'-dimethyl-2,2'-bipyridyl were added, and nitrogen was introduced for 10 minutes, and nitrogen was introduced at a flow rate of 50 mL / min, and the temperature was raised to 100°C, and stirring was continued for 18 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-26 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain a binder solution S-26 (concentration: 10% by mass).
[0545] [Synthesis Example 27: Synthesis of polymer S-27 (preparation of binder solution S-27)]
[0546] A fluorine-based copolymer S-27 was synthesized, and a binder solution S-27 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0547] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-19 synthesized in Synthesis Example 19 were added to a 500 mL three-necked flask with a reflux cooling tube, and 0.12 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was dropped into water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor A (S-27).
[0548] Next, 135 parts by mass of N-methylpyrrolidone and 15 parts by mass of the above-mentioned polymer precursor A (S-27) were added to a 300 mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200 mL / min for 10 minutes and then the temperature was raised to 75°C, and 14 parts by mass of decanedithiol and 0.8 parts by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako PureChemical Corporation) were added, and stirring was continued for 5 hours. Then, it was added dropwise to hexane to obtain a polymer precursor B (S-27) as a precipitate.
[0549] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor B (S-27) were added to a 300 mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, 2 parts by mass of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 1 part by mass of methacrylate 1H, 1H, 2H, 2H-tridecafluorooctyl ester (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.1 parts by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and nitrogen was introduced at a flow rate of 200 mL / min for 10 minutes before heating to 75°C and stirring was continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-27 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-27 (concentration 10% by mass).
[0550] [Synthesis Example 28: Synthesis of polymer S-28 (preparation of binder solution S-28)]
[0551] A fluorine-based copolymer S-28 was synthesized, and a binder solution S-28 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0552] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-20 synthesized in Synthesis Example 20 were added to a 500 mL three-necked flask with a reflux cooling tube, and 0.23 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was added dropwise to water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor (S-28).
[0553] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-28) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 12 parts by mass of dodecanethiol and 0.5 parts by mass of azobisisobutyronitrile (made by FUJIFILM Wako PureChemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-28 as a precipitate. The reduced pressure drying at 60°C was carried out for 5 hours and then dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-28 (concentration 10% by mass).
[0554] [Synthesis Example 29: Synthesis of polymer S-29 (preparation of binder solution S-29)]
[0555] A fluorine-based copolymer S-29 was synthesized, and a binder solution S-29 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0556] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-20 synthesized in Synthesis Example 20 were added to a 500 mL three-necked flask with a reflux cooling tube, and 0.23 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was added dropwise to water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor (S-29).
[0557] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-29) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 6 parts by mass of 6-mercapto-1-hexanol and 0.6 parts by mass of azobisisobutyronitrile (made by FUJIFILM Wako PureChemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-29 as a precipitate. The reduced pressure drying at 60°C was carried out for 5 hours and then dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-29 (concentration 10% by mass).
[0558] [Synthesis Example 30: Synthesis of polymer S-30 (preparation of binder solution S-30)]
[0559] A fluorine-based copolymer S-30 was synthesized, and an adhesive solution S-30 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0560] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-20 synthesized in Synthesis Example 20 were added to a 2L three-necked flask with a reflux cooling tube, and 0.23 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was dropped into water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor (S-30).
[0561] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-30) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 3 parts by mass of mercaptopropionic acid and 0.6 parts by mass of azobisisobutyronitrile (made by FUJIFILM Wako PureChemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-30 as a precipitate. The reduced pressure drying at 60°C was carried out for 5 hours and then dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-30 (concentration 10% by mass).
[0562] [Synthesis Example 31: Synthesis of polymer S-31 (preparation of binder solution S-31)]
[0563] A fluorine-based copolymer S-31 was synthesized, and a binder solution S-31 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0564] Specifically, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-30) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min and the temperature was raised to 75°C after 10 minutes, and 3 parts by mass of 6-mercapto-1-hexanol and 0.6 parts by mass of azobisisobutyronitrile (made by FUJIFILM WakoPure Chemical Corporation) were added, and stirring was continued for 5 hours, and 7 parts by mass of maleic anhydride were added, and stirring was further carried out for 2 hours. Then, it was added dropwise to hexane, and fluorine-based copolymer S-31 was obtained as a precipitate. After 5 hours of reduced pressure drying at 60°C, it was dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-31 (concentration 10% by mass).
[0565] [Synthesis Example 32: Synthesis of polymer S-32 (preparation of binder solution S-32)]
[0566] A fluorine-based copolymer S-32 was synthesized, and an adhesive solution S-32 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0567] Specifically, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor (S-28) were added to a 300mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200mL / min for 10 minutes and the temperature was raised to 75°C, and 22 parts by mass of 1H, 1H, 2H, 2H-perfluorodecanethiol and 1 part by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and stirring continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-32 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-32 (concentration 10% by mass).
[0568] [Synthesis Example 33: Synthesis of polymer S-33 (preparation of binder solution S-33)]
[0569] A fluorine-based copolymer S-33 was synthesized, and a binder solution S-26 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0570] Specifically, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the fluorine-based copolymer S-20 synthesized in Synthesis Example 20 were added to a 300 mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, 47.3 parts by mass of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 22.8 parts by mass of 1H, 1H, 2H, 2H-tridecafluorooctyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 0.1 parts by mass of copper chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation) and 0.5 parts by mass of 4,4'-dimethyl-2,2'-bipyridine were added, and nitrogen was introduced for 10 minutes, and nitrogen was introduced at a flow rate of 50 mL / min, and the temperature was raised to 100°C, and stirring was continued for 18 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-33 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain a binder solution S-33 (concentration: 10% by mass).
[0571] [Synthesis Example 34: Synthesis of polymer S-34 (preparation of binder solution S-34)]
[0572] A fluorine-based copolymer S-34 was synthesized, and an adhesive solution S-34 (concentration: 10% by mass) composed of the fluorine-based copolymer was prepared.
[0573] Specifically, 180 parts by mass of tetrahydrofuran and 20 parts by mass of the fluorine-based copolymer S-20 synthesized in Synthesis Example 20 were added to a 500 mL three-necked flask with a reflux cooling tube, and 0.12 g of lithium hydroxide and 40 g of methanol were further added, and stirred at 60° C. for 6 hours. Then, it was dropped into water, the precipitate was filtered, and vacuum dried to obtain a polymer precursor A (S-34).
[0574] Next, 135 parts by mass of N-methylpyrrolidone and 15 parts by mass of the above-mentioned polymer precursor A (S-34) were added to a 300 mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, nitrogen was introduced at a flow rate of 200 mL / min for 10 minutes and then the temperature was raised to 75°C, and 14 parts by mass of decanedithiol and 0.8 parts by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako PureChemical Corporation) were added, and stirring was continued for 5 hours. Then, it was added dropwise to hexane to obtain a polymer precursor B (S-34) as a precipitate.
[0575] Next, 90 parts by mass of N-methylpyrrolidone and 10 parts by mass of the above-mentioned polymer precursor B (S-34) were added to a 300 mL three-necked flask with a reflux cooling tube and a gas introduction plug and dissolved. Then, 2 parts by mass of lauryl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation), 1 part by mass of methacrylate 1H, 1H, 2H, 2H-tridecafluorooctyl ester (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.1 parts by mass of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and nitrogen was introduced at a flow rate of 200 mL / min for 10 minutes before heating to 75°C and stirring was continued for 5 hours. Then, it was added dropwise to hexane to obtain a fluorine-based copolymer S-34 as a precipitate. After drying under reduced pressure at 60°C for 5 hours, it was dissolved in any solvent. The obtained fluorine-based copolymer was dissolved in butyl butyrate to obtain an adhesive solution S-34 (concentration 10% by mass).
[0576] [Synthesis Examples 35 and 36: Synthesis of Polymers T-1 and T-3 (Preparation of Binder Solution T-1 and Binder Dispersion T-3)]
[0577] In Synthesis Example 1, except that the compound introduced into each constituent component was used so that the polymers T-1 and T-3 had the composition (type and content of constituent components) shown in Table 1, polymers T-1 and T-3 (both polyurethanes) were synthesized in the same manner as in Synthesis Example 1, and a solution T-1 of an adhesive composed of polymer T-1 and a dispersion T-3 of an adhesive composed of polymer T-3 were obtained, respectively. The average particle size of the adhesive in the dispersion T-3 was 120 nm.
[0578] [Synthesis Example 37: Synthesis of Polymer T-2 (Preparation of Binder Dispersion T-2)]
[0579] In Synthesis Example 4, polymer T-2 ((meth)acrylic polymer) was synthesized in the same manner as in Synthesis Example 4, except that the compound introduced into each constituent component was used so that polymer T-2 had the composition (type and content of constituent components) shown in Table 1, to obtain dispersion T-2 of a binder composed of polymer T-2. The average particle size of the binder in dispersion T-2 was 180 nm.
[0580] [Synthesis Example 38: Synthesis of Polymer D-1 (Preparation of Binder Dispersion D-1)]
[0581] To a 100 mL volumetric flask, 11.7 g of mono(2-acryloyloxyethyl) succinate (Tokyo Chemical Industry Co., Ltd.) and 0.17 g of polymerization initiator V-601 (trade name, FUJIFILM Wako Pure Chemical Corporation) were added and dissolved in 13.6 g of butyl butyrate to prepare a monomer solution. 10.2 g of a macromonomer was added to a 200 mL three-necked flask, dissolved in 16.9 g of butyl butyrate, and the monomer solution was added dropwise at a position where stirring was performed at 80° C. for 2 hours. After the addition was completed, the mixture was stirred at 80° C. for 2 hours, and then the mixture was heated to 90° C. and stirred for 2 hours to prepare a dispersion D-1 of a (meth) acrylic polymer. The mass average molecular weight of the polymer D-1 thus obtained was 95,000, and the SP value was 21.5. The average particle size of the binder in the dispersion D-1 was 160 nm.
[0582] (Synthesis of Macromonomers)
[0583] In a 1L volumetric flask, 130.2 g of methyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 330.7 g of dodecyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.), 4.5 g of 3-mercaptopropionic acid, and 4.61 g of polymerization initiator V-601 (manufactured by FUJIFILM Wako Pure Chemical Corporation) were added, and the mixture was uniformly dissolved by stirring to prepare a monomer solution. In a 2L three-necked flask, 465.5 g of toluene (manufactured by FUJIFILM Wako Pure Chemical Corporation) was added, and the monomer solution was added dropwise to the position where the mixture was stirred at 80°C for 2 hours. After the addition was completed, the mixture was stirred at 80°C for 2 hours, and then the mixture was heated to 90°C and stirred for 2 hours. 2,2,6,6-tetramethylpiperidinyl 1-oxyl (manufactured by FUJIFILM Wako Pure Chemical Corporation) 275 mg, glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd.) 27.5 g, and tetrabutylammonium bromide (manufactured by FUJIFILM Wako PureChemical Corporation) 5.5 g were added, and stirred at 120°C for 3 hours. After the solution was allowed to stand at room temperature, it was poured into 1800 g of methanol and the supernatant was removed. Butyl butyrate was added thereto, and methanol was distilled off under reduced pressure to obtain a butyl butyrate solution of a macromonomer. The solid content concentration was 48.9% by mass.
[0584] The macromonomer obtained in this way had a mass average molecular weight of 10,000 and an SP value of 18.7.
[0585] The composition, SP value, presence or absence of functional groups, mass average molecular weight of each synthesized polymer and the form (solution or dispersion) of the adhesive in the composition described later are shown in Table 1. The SP value and mass average molecular weight of the polymer are measured by the above method. When two components corresponding to specific constituents are contained, " / " is used to record them together.
[0586] The synthesized polymers are shown below. The numbers recorded on the lower right of each component indicate the content (mol %). In S-21 to S-34 (except S-26 and S-33), for the components other than VDF, HPF and TFE indicated by "*" in Table 1, it indicates a mixture of positional isomers with different substitution (introduction) positions of dodecanethiol, etc.
[0587] [Chemical formula 14]
[0588]
[0589] [Chemical formula 15]
[0590]
[0591] [Chemical formula 16]
[0592]
[0593] [Chemical formula 17]
[0594]
[0595]
[0596]
[0597] <Abbreviations of the table>
[0598] In the table, "-" in the component column indicates that the corresponding component is not present.
[0599] In the table, "*" in the column of constituent components indicates constituent components other than VDF, HPF and TFE in the above-mentioned copolymers.
[0600] -Composition Component M1-
[0601] In the case of a step-polymerization polymer, constituent M1 represents a constituent represented by the above-mentioned formula (I-1) (a constituent having a functional group selected from the functional group group (a)); in the case of a (meth)acrylic polymer, etc., it represents constituents other than the constituent represented by formula (1-1) (constituents having a functional group selected from the functional group group (a) and other constituents).
[0602] H12MDI: dicyclohexylmethane 4,4'-diisocyanate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 22.4)
[0603] Dimethyl adipate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 20.1)
[0604] GMA: Glycidyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 22.2)
[0605] DmEA: (N,N-dimethylamino)ethyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 18.1)
[0606] HEA: 2-Hydroxyethyl acrylate (manufactured by FUJIFILM Wako Pure Chemical Corporation, SP value 25.9)
[0607] VI: Vinyl imidazole (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 20.8)
[0608] MEA: Methoxyethyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 20.9)
[0609] Hosmer PP: acid·phosphorus·polyoxy·propylene glycol·monomethacrylate (manufactured by Uni-Chemical Co., Ltd., SP value 21.4)
[0610] MA: Methacrylic acid (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 19.0)
[0611] PA: Propyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 19.8)
[0612] St: Styrene (manufactured by FUJIFILM Wako Pure Chemical Corporation, SP value 19.3)
[0613] MAA: Maleic anhydride (manufactured by FUJIFILM Wako Pure Chemical Corporation, SP value 26.9)
[0614] MMA: Methyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 19.4)
[0615] BnMA: benzyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 20.0)
[0616] AEHS: Mono(2-acryloyloxyethyl) succinate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 21.8)
[0617] MDI: diphenylmethane diisocyanate (manufactured by FUJIFILM Wako Pure Chemical Corporation, SP value 26.1)
[0618] VDF: Vinylidene fluoride (SP value 13.1)
[0619] HFP: Hexafluoropropylene (SP value 10.1)
[0620] TFE: Tetrafluoroethylene (SP value 10.1)
[0621] *As described above.
[0622] -Constituent M2-
[0623] The constituent M2 refers to the constituent represented by the above formula (1-2) in the case of a step-polymerization polymer, and refers to the constituent represented by the formula (1-1) in the case of a (meth)acrylic polymer.
[0624] NISSO-PB GI1000: Hydrogenated liquid polybutadiene diol (trade name, number average molecular weight 1400, manufactured by Nippon Soda Co., Ltd., SP value 17.4)
[0625] NISSO-PB G3000: Liquid polybutadiene diol (trade name, number average molecular weight 3000, manufactured by Nippon Soda Co., Ltd., SP value 17.8)
[0626] LMA: dodecyl methacrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 18.5)
[0627] LA: dodecyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 18.8)
[0628] OA: Octyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 18.4)
[0629] HFBA: 2,2,3,4,4,4-hexafluorobutyl acrylate (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 13.0)
[0630] -Composition Component M3-
[0631] In the case of a step-wise polymerization polymer, constituent M3 represents a constituent represented by the above formula (I-3A) (a constituent having a functional group selected from the functional group group (a)). The content is the content of constituent M1 ≥ the content of constituent M3
[0632] DMBA: 2,2-bis(hydroxymethyl)butyric acid (manufactured by Tokyo Chemical Industry Co., Ltd., SP value 23.7)
[0633] -Composition Component M4-
[0634] In the case of a step-polymerization polymer, constituent component M4 refers to a constituent component represented by the above formula (I-3B).
[0635] PPG400: polypropylene glycol (number average molecular weight 400, manufactured by FUJIFILM Wako Pure Chemical Corporation, SP value 20.6)
[0636] PEG200: polyethylene glycol (number average molecular weight 200, manufactured by FUJIFILM Wako Pure Chemical Corporation, SP value 22.6)
[0637] PTMG250: polytetramethylene glycol (number average molecular weight 250, manufactured by SIGMA-Aldrich, SP value 20.7)
[0638] A solution of a low adsorption binder composed of a commercially available polymer was prepared as follows.
[0639] [Preparation Example 1: Preparation of Low Adsorption Binder Solution UFB Composed of Fluoropolymer]
[0640] PVdF-HFP: Kynar Flex Ultraflex B (trade name, manufactured by Arkema SA) was dissolved in butyl butyrate to prepare a low adsorption binder solution UFB having a solid content concentration of 3% by mass.
[0641] The SP value of PVdF-HFP is 12.4 (MPa 1 / 2 ), the mass average molecular weight is 200000, and the copolymerization ratio [PVdF:HFP] (mass ratio) is 58:42. In addition, PVdF-HFP does not have the functional group included in the functional group group (a).
[0642] [Preparation Example 2: Preparation of Low-Adsorption Binder Solution T938 Composed of Fluoropolymer]
[0643] PVdF-HFP-TFE: Tecnoflon (trade name, manufactured by Solvay SA) was dissolved in butyl butyrate to prepare a low-adsorption binder solution T938 having a solid content concentration of 3% by mass.
[0644] The SP value of PVdF-HFP-TFE is 11.8 (MPa 1 / 2 ), the mass average molecular weight is 180000, and the copolymerization ratio [PVdF:HFP:TFE] (mass ratio) is 48:32:20. In addition, PVdF-HFP-TFE does not have the functional group included in the functional group group (a).
[0645] [Preparation Example 3: Preparation of Low-Adsorption Binder Solution H1041 Composed of Hydrocarbon-Based Polymer]
[0646] Tuftec (registered trademark) H1041: A hydrogenated styrene-based thermoplastic elastomer (trade name, SEBS, manufactured by ASAHIKASEI CORPORATION) was dissolved in butyl butyrate to prepare a low-adsorption binder solution H1041 having a solid content concentration of 10% by mass.
[0647] The SP value of hydrogenated styrene thermoplastic elastomer is 18.0 (MPa 1 / 2 ), a mass average molecular weight of 100,000, and a styrene / ethylene·butylene ratio of 30 / 70. In addition, the hydrogenated styrene-based thermoplastic elastomer does not have the functional groups included in the functional group group (a).
[0648] [Preparation Example 4: Preparation of Low-Adsorption Binder Solution M1911 Composed of Hydrocarbon-Based Polymer]
[0649] Tuftec (registered trademark) M1911: A maleic anhydride-modified hydrogenated styrene-based thermoplastic elastomer (trade name, SEBS, manufactured by ASAHI KASEI CORPORATION) was dissolved in butyl butyrate to prepare a low-adsorption binder solution M1911 having a solid content concentration of 10% by mass.
[0650] The SP value of maleic anhydride modified hydrogenated styrene thermoplastic elastomer is 18.0 (MPa 1 / 2 ), a mass average molecular weight of 120,000, a styrene / ethylene·butylene ratio of 30 / 70, and a maleic anhydride modification amount (content of constituent components having maleic anhydride groups) of 0.4 mol%. In addition, the maleic anhydride-modified hydrogenated styrene-based thermoplastic elastomer has a carboxylic anhydride group included in the functional group (a).
[0651] 2. Synthesis of sulfide-based inorganic solid electrolyte [Synthesis Example A]
[0652] The sulfide-based inorganic solid electrolyte was synthesized with reference to the non-patent literature of T. Ohtomo, A. Hayashi, M. Tatsumisago, Y. Tsuchida, S. Hama, K. Kawamoto, Journal of Power Sources, 233, (2013), pp231-235 and A. Hayashi, S. Hama, H. Morimoto, M. Tatsumisago, T. Minami, Chem. Lett., (2001), pp872-873.
[0653] Specifically, 2.42 g of lithium sulfide (Li2S, manufactured by Aldrich. Inc., purity>99.98%) and 3.90 g of phosphorus pentasulfide (P2S5, manufactured by Aldrich. Inc., purity>99%) were weighed in a glove box under an argon atmosphere (dew point -70°C), put into an agate mortar, and mixed for 5 minutes using an agate pestle. The mixing ratio of Li2S and P2S5 was set to Li2S:P2S5=75:25 in terms of molar ratio.
[0654] Next, 66 g of zirconia beads with a diameter of 5 mm were added to a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and the total amount of the mixture of the above-mentioned lithium sulfide and phosphorus pentasulfide was added, and the container was completely sealed under an argon atmosphere. A container was set in a planetary ball mill P-7 (trade name, manufactured by Fritsch Co., Ltd.) manufactured by Fritsch Co., Ltd., and mechanical grinding was performed for 20 hours at a temperature of 25°C and a rotation speed of 510 rpm to obtain 6.20 g of a yellow powder of a sulfide-based inorganic solid electrolyte (Li-PS-based glass, hereinafter sometimes labeled as LPS). The particle size of the Li-PS-based glass is 15 μm.
[0655] [Example 1]
[0656] Each composition shown in Table 2-1 to Table 2-5 (sometimes collectively referred to as Table 2) was prepared as follows.
[0657] <Preparation of a composition containing an inorganic solid electrolyte>
[0658] Into a 45 mL container made of zirconium oxide (made by Fritsch Japan Co., Ltd.), 60 g of zirconium oxide beads with a diameter of 5 mm were added. When 8.4 g of LPS or LLT synthesized in the above-mentioned synthesis example A, 0.6 g or 0.4 g (solid content mass) of the polymer binder solution or dispersion shown in Table 2, and 0.4 g of the polymer binder solution or dispersion were used, 0.2 g (solid content mass) of the granular binder dispersion shown in Table 2 and 11 g of butyl butyrate as a dispersion medium were further added. Then, the container was set in a planetary ball mill P-7 (trade name) made by Fritsch Co., Ltd. Mixing was carried out at a temperature of 25°C and a rotation speed of 150 rpm for 10 minutes to prepare compositions (slurries) K-1 to K-49 and Kc-11 to Kc-13 containing inorganic solid electrolytes, respectively.
[0659] Compositions K-46 to K-49 containing an inorganic solid electrolyte were prepared using two low-adsorption binders shown in Table 2-2, using 0.4 g of binder solution S-13 by solid content mass and 0.2 g of other binder solutions shown in Table 2-2 by solid content mass.
[0660] <Preparation of positive electrode composition>
[0661] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Co., Ltd.), 60 g of zirconium oxide beads with a diameter of 5 mm were added, and 8 g of LPS synthesized in Synthesis Example A and 13 g (total amount) of butyl butyrate as a dispersion medium were added. The container was set in a planetary ball mill P-7 (trade name) manufactured by Fritsch Co., Ltd., and stirred at 25° C. and 200 rpm for 30 minutes. Then, 27.5 g of NMC (manufactured by Sigma-Aldrich Co. LLC) as a positive electrode active material, 1.0 g of acetylene black (AB) as a conductive aid, 0.5 g (solid content mass) of a polymer binder solution or dispersion shown in Table 2, and 0.5 g (solid content mass) of a granular binder dispersion shown in Table 2 when 12.5 g of butyl butyrate is used for PK-4 to PK-8, PK-16 and PK-17, a planetary ball mill P-7 is set in the container, and mixing is continued at a temperature of 25°C and a rotation speed of 200 rpm for 30 minutes to prepare positive electrode compositions (slurries) PK-1 to PK-17, respectively.
[0662] Positive electrode compositions PK-9 and PK-10 were prepared using the two low-adsorption binders shown in Table 2-3, 12.5 g of butyl butyrate was used, and 0.5 g of each binder solution was used in terms of solid content.
[0663] <Preparation of negative electrode composition>
[0664] Into a 45 mL container made of zirconium oxide (manufactured by Fritsch Japan Co., Ltd.), 60 g of zirconium oxide beads with a diameter of 5 mm, 8.0 g or 7.6 g of LPS synthesized in Synthesis Example A, 0.4 g (solid content mass) of a polymer binder solution or dispersion shown in Table 2, and when 7.6 g of LPS is used in NK-4 to NK-8, NK-31, and NK-32, 0.4 g (solid content mass) of a granular binder dispersion shown in Table 2 and 17.5 g (total amount) of a dispersion medium shown in Table 2 were further added. The container was set in a planetary ball mill P-7 (trade name) manufactured by Fritsch Co., Ltd., and mixed at a temperature of 25° C. and a rotation speed of 300 rpm for 60 minutes. Then, 9.5 g of silicon (Si, manufactured by Aldrich) as a negative electrode active material and 1.0 g of VGCF (manufactured by SHOWA DENKO KK) as a conductive aid, or 10.5 g of graphite as a negative electrode active material were added, and the container was similarly set in a planetary ball mill P-7, and mixed at a temperature of 25°C and a rotation speed of 100 rpm for 10 minutes to prepare negative electrode compositions (slurries) NK-1 to NK-33 and NKc21 to NKc23, respectively.
[0665] Negative electrode compositions NK-9 and NK-10 were prepared using the two low-adsorption binders shown in Table 2-4, and used 7.6 g of LPS and 0.4 g of each binder solution in terms of solid content.
[0666] For each of the prepared binders, the adsorption rate A with respect to the inorganic solid electrolyte shown in Table 2 (the inorganic solid electrolyte used to prepare each composition) was measured by the following method. SE , relative to the adsorption rate A of the active substances (active substances used to prepare each composition) shown in Table 2 AM . And, for each composition, the difference (absolute value) between the SP value of the polymer forming the low adsorption binder and the SP value of the dispersion medium was calculated. The results are shown in Table 2. In addition, the contact angle (°) of the dispersion medium used in each composition relative to the polymer film made of the polymer forming the binder used in each composition was measured by the above method, and the results are shown in Table 2.
[0667] In Table 2, the composition content is the content (mass %) relative to the total mass of the composition, and the solid content is the content (mass %) relative to 100 mass % of the solid content of the composition, and units are omitted in the table.
[0668] Table 2 shows the SP values of the polymer and the dispersion medium that form the low adsorption binder. The unit of the SP value is MPa. 1 / 2 , which is omitted in Table 2.
[0669] [Adsorption rate of binder to inorganic solid electrolyte A SE Determination of
[0670] The adsorption rate A was measured using the inorganic solid electrolyte, polymer binder and dispersion medium used to prepare the compositions containing the inorganic solid electrolyte shown in Table 2. SE .
[0671] That is, a polymer binder (low adsorption binder, granular binder) was dissolved in a dispersion medium to prepare a binder solution with a concentration of 1% by mass. In addition, for polymers S-7, T-2, T-3 and D-1, a binder dispersion with a concentration of 1% by mass was prepared. The binder solution or dispersion and the inorganic solid electrolyte were placed in a 15 mL medicine bottle with a mass ratio of 42:1 in the binder solution or dispersion to the inorganic solid electrolyte, and stirred at a speed of 80 rpm for 1 hour at room temperature by a mixing rotor and then left to stand. The supernatant obtained by solid-liquid separation was filtered with a filter with a pore size of 1 μm, and the obtained filtrate was completely dried to dryness, and the mass of the polymer binder remaining in the filtrate (the mass of the polymer binder not adsorbed on the inorganic solid electrolyte) W was measured. A . From this mass W Aand the mass W of the binder contained in the binder solution used for determination B , the adsorption rate of the polymer binder to the inorganic solid electrolyte was calculated by the following formula.
[0672] Adsorption rate of polymer binder A SE The above measurement was performed twice and the adsorption rate was taken as an average value.
[0673] Adsorption rate (%) = [(W B -W A ) / W B ]×100
[0674] In addition, the adsorption rate A was measured using the inorganic solid electrolyte and the polymer binder taken out from the formed solid electrolyte layer and the dispersion medium used to prepare the composition containing the inorganic solid electrolyte. SE As a result, the same value was obtained.
[0675] [Adsorption rate of active substances by adhesive A AM Determination of
[0676] The adsorption rate A was measured using the active material, polymer binder and dispersion medium used to prepare each electrode composition shown in Table 2. AM .
[0677] In the above "adsorption rate A SE In the determination of ", an active material was used instead of an inorganic solid electrolyte, and in addition, the adsorption rate A SE The adsorption rate A was determined in the same way as AM .
[0678] In addition, the adsorption rate A was measured using the active material and polymer binder taken out from the film-formed active material layer and the dispersion medium used to prepare the electrode composition. AM As a result, the same value was obtained.
[0679]
[0680]
[0681]
[0682]
[0683]
[0684] <Abbreviations of the table>
[0685] LPS: LPS synthesized in Synthesis Example A
[0686] LLT:Li 0.33 La 0.55 TiO3 (average particle size 3.25 μm, manufactured by Toshima Manufacturing Co., Ltd.)
[0687] NMC:LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2
[0688] Si: Silicon
[0689] AB: Acetylene Black
[0690] VGCF: Carbon nanotube (manufactured by SHOWA DENKO KK)
[0691] When two low-adsorption adhesives are used, the corresponding contents are recorded in two sections, upper and lower, in the "Adhesive solution or dispersion" column and the "SP value difference" column.
[0692] <Manufacturing of solid electrolyte sheets for all-solid-state secondary batteries>
[0693] The compositions containing inorganic solid electrolytes shown in Table 3-1 and Table 3-2 (sometimes collectively referred to as Table 3) obtained above were applied to an aluminum foil having a thickness of 20 μm using a baking applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), heated at 80°C for 2 hours, and dried (dispersion medium removed) the compositions containing inorganic solid electrolytes. Then, using a hot press, the dried compositions containing inorganic solid electrolytes were heated and pressurized at a temperature of 120°C and a pressure of 40 MPa for 10 seconds, thereby producing solid electrolyte sheets for all-solid-state secondary batteries (marked as solid electrolyte sheets in Table 3) 101 to 149 and c11 to c13, respectively. The film thickness of the solid electrolyte layer was 50 μm.
[0694] <Manufacturing of positive electrode sheets for all-solid-state secondary batteries>
[0695] Using a baking applicator (trade name: SA-201), each positive electrode composition shown in the "Electrode Composition" column of Table 3 obtained above was applied to an aluminum foil with a thickness of 20 μm, heated at 80°C for 1 hour, and further heated at 110°C for 1 hour, and the composition containing the inorganic solid electrolyte was dried (removed from the dispersion medium). Then, using a hot press, the dried positive electrode composition was pressurized at 25°C (10 MPa, 1 minute), thereby producing positive electrode sheets for all-solid-state secondary batteries (i marked as positive electrode sheets in Table 3-2) 150 to 166 each having a positive electrode active material layer with a film thickness of 80 μm.
[0696] <Manufacturing of negative electrode sheets for all-solid-state secondary batteries>
[0697] Each negative electrode composition shown in the "Electrode Composition" column of Table 3 obtained above was applied to a copper foil having a thickness of 20 μm using a baking applicator (trade name: SA-201), heated at 80°C for 1 hour, and further heated at 110°C for 1 hour, and dried (dispersion medium removed) the negative electrode composition. Then, using a hot press, the dried negative electrode composition was pressed at 25°C (10 MPa, 1 minute), thereby producing all-solid-state secondary battery negative electrode sheets (referred to as negative electrode sheets in Table 3-2) 167 to 199 and c21 to c23 having a negative electrode active material layer having a film thickness of 70 μm.
[0698] <Manufacturing of positive electrode sheet for all-solid-state secondary battery with solid electrolyte layer>
[0699] Next, the solid electrolyte sheet shown in the "Solid Electrolyte Layer" column of Table 4 prepared above was stacked on the positive electrode active material layer of each all-solid-state secondary battery positive electrode sheet shown in the "Electrode Active Material Layer" column of Table 4 in such a manner that the solid electrolyte layer was in contact with the positive electrode active material layer. After being pressurized at 50 MPa at 25°C and transferred (laminated) using a press, the press was pressurized at 600 MPa at 25°C, thereby producing all-solid-state secondary battery positive electrode sheets (positive electrode active material layer with a thickness of 60 μm) 150 to 166 respectively having a solid electrolyte layer with a film thickness of 30 μm.
[0700] <Manufacturing of negative electrode sheet for all-solid-state secondary battery with solid electrolyte layer>
[0701] Next, the solid electrolyte sheet shown in the "Solid Electrolyte Layer" column of Table 4 prepared above was stacked on the negative electrode active material layer of each all-solid-state secondary battery negative electrode sheet shown in the "Electrode Active Material Layer" column of Table 4 in such a manner that the solid electrolyte layer was in contact with the negative electrode active material layer. After being pressurized at 50 MPa at 25°C and transferred (laminated) using a press, the press was then pressurized at 600 MPa at 25°C, thereby producing all-solid-state secondary battery negative electrode sheets (negative electrode active material layer with a thickness of 50 μm) 167~199 and c21~c23 respectively having a solid electrolyte layer with a thickness of 30 μm.
[0702] <Evaluation 1: Dispersion stability>
[0703] Each prepared composition (slurry) is put into a glass test tube with a diameter of 10 mm and a height of 4 cm until the height is 4 cm, and allowed to stand at 25°C for 24 hours. Calculate the solid content ratio of 1 cm from the slurry liquid surface before and after standing. Specifically, immediately after standing, take out 1 cm of liquid from the bottom of the slurry liquid surface and heat dry it at 120°C in an aluminum cup for 2 hours. Measure the mass of the solid content in the cup afterwards, and calculate the solid content before and after standing. Calculate the solid content ratio [WA / WB] of the solid content WA after standing relative to the solid content WB before standing.
[0704] According to which of the following evaluation criteria the solid content ratio is included in, the ease of precipitation of the inorganic solid electrolyte is evaluated as the dispersion stability of the solid electrolyte composition. In this test, the closer the solid content ratio is to 1, the better the dispersion stability is, and the evaluation criteria "D" or above are qualified levels. The results are shown in Table 3.
[0705] -Evaluation Criteria-
[0706] A: 0.9≤Solid content ratio≤1.0
[0707] B: 0.7≤Solid content ratio<0.9
[0708] C: 0.5≤Solid content ratio<0.7
[0709] D: 0.3≤Solid content ratio<0.5
[0710] E: 0.1≤Solid content ratio<0.3
[0711] F: Solid content ratio <0.1
[0712] <Evaluation 2: Handling>
[0713] In the same manner as each of the prepared compositions, except for the dispersion medium, the same mixing ratio was set, the amount of the dispersion medium was reduced, and a slurry with a solid content concentration of 75% by mass was prepared. A 2mL polyspot (manufactured by Atect Corporation) was arranged vertically so that the tip 10mm entered below the slurry interface, and the slurry was sucked for 10 seconds at 25°C, and the mass W of the polyspot containing the sucked slurry was measured. When the tare weight (self-weight) of the polyspot is set to W0, the slurry mass W-W0 is judged to be unable to be sucked with a dropper when it is less than 0.1g. When the slurry cannot be sucked with a dropper, the upper limit solid content concentration that can be sucked with a dropper while gradually adding the dispersion medium is grasped. Depending on which of the following evaluation criteria the obtained upper limit solid content concentration is included, the handleability of the composition (whether it has an appropriate viscosity to form a flat and well-surfaced constituent layer) is evaluated. The solid content concentration is calculated by placing 0.30g of the prepared slurry on an aluminum cup and heating it at 120°C for 2 hours to distill off the dispersion medium.
[0714] In this test, the higher the upper limit solid content concentration, the better the handling property was, and the evaluation standard "D" or higher was considered a pass level. The results are shown in Table 3.
[0715] -Evaluation Criteria-
[0716] A: Upper limit solid content concentration ≥ 70%
[0717] B: 70%>upper limit solid content concentration≥60%
[0718] C: 60%>Upper limit solid content concentration ≥ 50%
[0719] D: 50%>upper limit solid content concentration≥40%
[0720] E: 40%>Upper limit solid content concentration ≥ 30%
[0721] F: 30% > upper limit solid content concentration
[0722] <Evaluation 3: Current Collector Adhesion>
[0723] A test piece of 20 mm long and 20 mm wide was cut from each positive electrode sheet for all-solid-state secondary batteries and each negative electrode sheet for all-solid-state secondary batteries. For the test piece, 11 cuts were made at intervals of 1 mm in parallel with one side using a cutter to reach the substrate (aluminum foil or copper foil). In addition, 11 cuts were made at intervals of 1 mm in a direction perpendicular to the cut to reach the substrate. In this way, 100 squares were formed on the test piece.
[0724] A 15 mm long × 18 mm wide transparent tape was attached to the surface of the solid electrolyte layer to cover all the above 100 squares. Rub the surface of the transparent tape with an eraser, press it on the solid electrolyte layer and make it adhere. After sticking the transparent tape for 2 minutes, hold the end of the transparent tape and pull it vertically upward relative to the solid electrolyte layer and peel it off. After peeling off the transparent tape, visually observe the surface of the solid electrolyte layer, count the number of squares that have not peeled off from the collector at all, and evaluate the adhesion of the active material layer to the collector.
[0725] In this test, the more meshes that were not peeled off from the current collector, the better the adhesion to the current collector, and the evaluation standard "D" or higher was considered a pass level.
[0726] -Evaluation Criteria-
[0727] A: 80 or more
[0728] B: More than 60 grids and less than 80 grids
[0729] C: 40 or more and less than 60
[0730] D: 30 or more and less than 40
[0731] E: 10 or more and less than 30
[0732] F: Less than 10 grids
[0733] [Table 3-1]
[0734]
[0735] In the above "Polymer No." column, the adsorption rate A is shown. SE When two polymers are included in the polymer binder accounting for less than 60%, they are collectively described using " / ".
[0736] [Table 3-2]
[0737]
[0738]
[0739] In the above "Polymer No." column, the adsorption rate A is shown. SE When two polymers are included in the polymer binder accounting for less than 60%, they are collectively described using " / ".
[0740] <Manufacturing of all-solid-state secondary batteries>
[0741] The following is a Figure 1 All-solid-state secondary battery (No. 101) having the layer structure shown.
[0742] The positive electrode sheet No. 150 for all-solid-state secondary battery having the solid electrolyte layer obtained above (the aluminum foil from which the sheet containing the solid electrolyte has been peeled off) was cut into a disk with a diameter of 14.5 mm and Figure 2 The introduction assembly shown has a spacer and a gasket (in Figure 2 Next, a lithium foil cut into a disk shape with a diameter of 15 mm was stacked on the solid electrolyte layer. After further stacking the stainless steel foil thereon, the 2032 type button battery case 11 was riveted to produce a Figure 2 All-solid-state secondary battery 13 of No. 101 is shown.
[0743] The all-solid-state secondary battery manufactured in this way has Figure 1 The layer structure shown (wherein the lithium foil corresponds to the negative electrode active material layer 2 and the negative electrode current collector 1).
[0744] In the manufacture of the above-mentioned all-solid-state secondary battery (No. 101), instead of the all-solid-state secondary battery positive electrode sheet No. 150 having a solid electrolyte layer, an all-solid-state secondary battery positive electrode sheet having a solid electrolyte layer represented by No. shown in the "Electrode Active Material Layer" column of Table 4 was used. Apart from this, all-solid-state secondary batteries (No. 102 to 117) were manufactured respectively in the same manner as the all-solid-state secondary battery (No. 101).
[0745] The following is a Figure 1 All-solid-state secondary battery (No. 118) having the layer structure shown.
[0746] Each of the all-solid-state secondary battery negative electrode sheets No. 167 (aluminum foil from which the sheet containing the solid electrolyte has been peeled off) having the solid electrolyte layer obtained above was cut into a disk shape having a diameter of 14.5 mm and Figure 2 The introduction assembly shown has a spacer and a gasket (in Figure 2 A 2032 type button battery case 11 made of stainless steel (not shown in the figure) is placed in the battery case. Next, a positive electrode sheet (positive electrode active material layer) punched out with a diameter of 14.0 mm from the positive electrode sheet for the all-solid-state secondary battery produced below is stacked on the solid electrolyte layer. A stainless steel foil (positive electrode collector) is further stacked thereon to form a stack 12 for the all-solid-state secondary battery (a stack consisting of stainless steel foil-aluminum foil-positive electrode active material layer-solid electrolyte layer-negative electrode active material layer-copper foil). Afterwards, the 2032 type button battery case 11 is crimped to produce a Figure 2 All-solid-state secondary battery No.118 shown.
[0747] A positive electrode sheet for a solid secondary battery used to manufacture an all-solid-state secondary battery (No. 118) was prepared as follows.
[0748] (Preparation of positive electrode composition)
[0749] 180 g of 5 mm diameter zirconia beads were added to a 45 mL zirconia container (manufactured by Fritsch Co., Ltd.), and 2.7 g of LPS synthesized in the above synthesis example A, 0.3 g of KYNAR FLEX 2500-20 (trade name, PVdF-HFP: polyvinylidene fluoride hexafluoropropylene copolymer, manufactured by ARKEMA) and 22 g of butyl butyrate were added. The container was placed in a planetary ball mill P-7 (trade name) manufactured by Fritsch Co., Ltd. and stirred at 25°C and 300 rpm for 60 minutes. After that, 7.0 g of LiNi was added as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NMC), and the containers were assembled in a planetary ball mill P-7 in the same manner, and mixing was continued at 25°C and 100 rpm for 5 minutes to prepare positive electrode compositions.
[0750] (Manufacturing of positive electrode sheets for all-solid-state secondary batteries)
[0751] The positive electrode composition obtained above was applied to an aluminum foil (positive electrode current collector) having a thickness of 20 μm using a baking applicator (trade name: SA-201, manufactured by TESTER SANGYO CO,.LTD.), heated at 100°C for 2 hours, and dried (dispersion medium removed) the positive electrode composition. Then, the dried positive electrode composition was pressed at 25°C (10 MPa, 1 minute) using a hot press to produce a positive electrode sheet for an all-solid-state secondary battery having a positive electrode active material layer having a thickness of 80 μm.
[0752] In the manufacture of the above-mentioned all-solid-state secondary battery (No. 118), instead of the all-solid-state secondary battery negative electrode sheet No. 167 having a solid electrolyte layer, an all-solid-state secondary battery negative electrode sheet having a solid electrolyte layer represented by No. shown in the "Electrode active material layer" column of Table 4 was used. Apart from this, all-solid-state secondary batteries (No. 119 to 150 and c101 to c103) were manufactured in the same manner as the all-solid-state secondary battery (No. 118).
[0753] <Evaluation 4: Cycle characteristics>
[0754] For each of the manufactured all-solid-state secondary batteries, the discharge capacity maintenance rate was measured using a charge and discharge evaluation device TOSCAT-3000 (trade name, manufactured by TOYO SYSTEM Co., Ltd.).
[0755] Specifically, each all-solid-state secondary battery was charged at 25°C until the current density reached 0.1 mA / cm 2 The battery voltage reached 3.6 V. Then, the battery was discharged until the current density reached 0.1 mA / cm 2 The battery voltage reached 2.5 V. This charge and discharge was regarded as one charge and discharge cycle, and three cycles were repeated under the same conditions to initialize it. Then, the above charge and discharge cycles were repeated, and the discharge capacity of each all-solid-state secondary battery was measured using a charge and discharge evaluation device: TOSCAT-3000 (trade name) during each charge and discharge cycle.
[0756] When the discharge capacity (initial discharge capacity) of the first cycle of charge and discharge after initialization is set to 100%, the number of charge and discharge cycles when the discharge capacity retention rate (discharge capacity relative to the initial discharge capacity) reaches 80% is evaluated by which of the following evaluation criteria is included in the battery performance (cycle characteristics). In this test, the higher the evaluation standard, the better the battery performance (cycle characteristics), and the initial battery performance can be maintained even if multiple charge and discharge are repeated (even if used for a long time).
[0757] In addition, the initial discharge capacities of all-solid-state secondary batteries Nos. 101 to 150 all showed sufficient values to function as all-solid-state secondary batteries.
[0758] -Evaluation Criteria-
[0759] A: More than 500 cycles
[0760] B: 300 cycles or more and less than 500 cycles
[0761] C: 200 cycles or more and less than 300 cycles
[0762] D: 150 cycles or more and less than 200 cycles
[0763] E: 80 cycles or more and less than 150 cycles
[0764] F: 40 cycles or more and less than 80 cycles
[0765] <Evaluation 5: Ion conductivity measurement>
[0766] The ion conductivity of each manufactured all-solid-state secondary battery was measured. Specifically, for each all-solid-state secondary battery, the AC impedance was measured in a 30°C constant temperature bath using a 1255B FREQUENCY RESPONSE ANALYZER (trade name, manufactured by SOLARTRON) until the voltage amplitude was 5 mV and the frequency was 1 MHz to 1 Hz. Thus, the resistance in the layer thickness direction of the sample for ion conductivity measurement was obtained, and the ion conductivity was calculated by the following formula (1).
[0767] Formula (1): Ionic conductivity σ (mS / cm) =
[0768] 1000× sample layer thickness (cm) / [resistance (Ω)× sample area (cm 2 )]
[0769] In formula (1), the sample thickness is the value obtained by subtracting the thickness of the current collector (total thickness of the solid electrolyte layer and the electrode active material layer) measured before placing the laminate 12 in the 2032-type button box 11. The sample area is the area of the disk-shaped sheet with a diameter of 14.5 mm.
[0770] It is determined whether the obtained ion conductivity σ is included in any of the following evaluation criteria.
[0771] In the present experiment, the ion conductivity σ was evaluated as being "D" or higher, which was considered as passing.
[0772] -Evaluation Criteria-
[0773] A: 0.60≤σ
[0774] B: 0.50≤σ<0.60
[0775] C: 0.40≤σ<0.50
[0776] D: 0.30≤σ<0.40
[0777] E: 0.20≤σ<0.30
[0778] F: σ<0.20
[0779] [Table 4]
[0780]
[0781]
[0782] From the results shown in Tables 3 and 4, the following can be understood.
[0783] The compositions containing inorganic solid electrolytes shown in Comparative Examples Kc11 to Kc13 and NKc21 to NKc23, which do not contain a polymer binder satisfying the adsorption rate specified in the present invention, have poor dispersion stability and handling properties. In addition, the collector adhesion of the electrode sheets using the compositions NKc21 to NKc23 is also insufficient. The all-solid-state secondary batteries of Comparative Examples c101 to c103 using these compositions do not show sufficient cycle characteristics nor ion conductivity.
[0784] In contrast, the compositions containing inorganic solid electrolytes shown in K-1 to K-49, PK-1 to PK-17 and NK-1 to NK-33 of the present invention, which contain one or two binders with an adsorption rate of less than 60% as specified in the present invention, have both dispersion stability and handling properties at a high level. By using the composition containing inorganic solid electrolytes to form the constituent layers of an all-solid-state secondary battery, the adhesion of the collector to the obtained electrode sheet can be made strong, and the cycle characteristics of the obtained all-solid-state secondary battery can be improved, and high ion conductivity can be achieved.
[0785] Explanation of symbols
[0786] 1-negative electrode collector, 2-negative electrode active material layer, 3-solid electrolyte layer, 4-positive electrode active material layer, 5-positive electrode collector, 6-working part, 10-all-solid-state secondary battery, 11-2032 type button-type battery box, 12-laminated body for all-solid-state secondary battery, 13-button-type all-solid-state secondary battery.
Claims
1. A composition containing an inorganic solid electrolyte, comprising: an inorganic solid electrolyte having ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, a soluble polymer binder, and a dispersion medium, wherein: The composition containing an inorganic solid electrolyte does not contain or further contains an insoluble particulate polymer binder, The inorganic solid electrolyte is at least one of a sulfide-based inorganic solid electrolyte and an oxide-based inorganic solid electrolyte. The dispersion medium includes at least one of an ester compound, a ketone compound, an ether compound, an aromatic compound and an aliphatic compound, The soluble polymer binder includes a soluble polymer binder having an adsorption rate of less than 60% with respect to the inorganic solid electrolyte in the dispersion medium, The soluble polymer binder with an adsorption rate of less than 60% includes at least one of fluorine-based polymers, polyurethanes, polyesters, (meth)acrylic polymers, vinyl polymers, and styrene-based thermoplastic elastomers or hydrides thereof. The fluorine-based polymer is a chain polymer selected from the group consisting of polytetrafluoroethylene, polyvinylidene fluoride, a copolymer of polyvinylidene fluoride and hexafluoropropylene, and a copolymer of polyvinylidene fluoride, hexafluoropropylene and tetrafluoroethylene. The polyurethane has 10 mol% or more of a constituent component represented by the following formula (1-2) and 20 to 50 mol% of a constituent component represented by the following formula (I-1), The (meth)acrylic polymer is a polymer having 10 to 95 mol% of a constituent component represented by the following formula (1-1) or a polymer consisting of a constituent component represented by the following formula (1-1) or a constituent component represented by the following formula (b-1), The soluble polymer binder having an adsorption rate of less than 60% is dissolved in the dispersion medium, In formula (1-1), R 1 represents a hydrogen atom or an alkyl group having 1 to 12 carbon atoms, R 2 represents a group having an aliphatic hydrocarbon group having 4 or more carbon atoms, In formula (1-2), R 3 represents a linking group containing a polybutadiene chain or a polyisoprene chain or a hydrogenated product thereof and having a mass average molecular weight of 500 to 200,000, In formula (I-1), R P1 It refers to a hydrocarbon chain with a molecular weight of 20 to 200,000. In formula (b-1), R 1 represents a hydrogen atom, a cyano group, a halogen atom, an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, or an alkynyl group having 2 to 24 carbon atoms, and R 2 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 or 3 carbon atoms, L 1 represents a -CO-O- group, and n is 1.
2. The composition containing an inorganic solid electrolyte according to claim 1, wherein The difference between the SP value of the polymer forming the soluble polymer binder having the adsorption rate of less than 60% and the dispersion medium is 3 or less.
3. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein The polymer forming the soluble polymer binder having an adsorption rate of less than 60% comprises a constituent component having a functional group selected from the following functional group group (a), <Functional group (a)> Hydroxyl group, amino group, carboxyl group, sulfone group, phosphoric acid group, phosphonic acid group, sulfanyl group, ether bond, imino group, ester bond, amide bond, carbamate bond, urea bond, heterocyclic group, aromatic group, carboxylic anhydride group, fluoroalkyl group, siloxane group.
4. The composition containing an inorganic solid electrolyte according to claim 3, wherein The content of the constituent component having a functional group selected from the functional group group (a) in the polymer forming the soluble polymer binder is 0.01 to 50 mol %.
5. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein The content of the constituent component represented by the above formula (1-1) in the (meth)acrylic polymer having 10 to 95 mol % of the constituent component represented by the above formula (1-1) is 23 mol % or more.
6. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein R of the formula (1-1) 2 is an aliphatic hydrocarbon group having 4 or more carbon atoms or a group consisting of an aliphatic hydrocarbon group having 4 or more carbon atoms and the following linking group, The linking group is an alkylene group, an alkenylene group, an arylene group, an oxygen atom, a sulfur atom, an imino group, a carbonyl group, a phosphoric acid linking group, a phosphonic acid linking group or a group related to a combination thereof.
7. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein The dispersion medium has 2 to 30 carbon atoms.
8. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein The present invention comprises two or more soluble polymer binders having an adsorption rate of less than 60%, wherein the polymer forming at least one of the soluble polymer binders is a fluorine-based polymer.
9. The composition containing an inorganic solid electrolyte according to claim 1 or 2, characterized in that: The contact angle of the polymer forming the soluble polymer binder having an adsorption rate of less than 60% with respect to the dispersion medium is 40 degrees or less.
10. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein The present invention comprises two or more soluble polymer binders having an adsorption rate of less than 60%, wherein the polymer forming at least one of the soluble polymer binders is a styrene-based thermoplastic elastomer or a hydrogenated product thereof.
11. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein The average particle size of the insoluble granular polymer binder is 1 to 1000 nm. 12 . The inorganic solid electrolyte-containing composition according to claim 1 , comprising an active material.
13. The composition containing an inorganic solid electrolyte according to claim 12, wherein The adsorption rate of the soluble polymer binder having the adsorption rate of less than 60% with respect to the active material is 90% or less. 14 . The inorganic solid electrolyte-containing composition according to claim 1 , further comprising a conductive auxiliary agent.
15. The composition containing an inorganic solid electrolyte according to claim 1 or 2, wherein The inorganic solid electrolyte is a sulfide-based inorganic solid electrolyte. 16 . A method for producing a sheet for an all-solid-state secondary battery, comprising forming a film of the composition containing an inorganic solid electrolyte according to claim 1 . 17 . A sheet for an all-solid-state secondary battery, comprising: a layer formed by the method for producing a sheet for an all-solid-state secondary battery according to claim 16 . 18 . A method for manufacturing an all-solid-state secondary battery, comprising the method for manufacturing an all-solid-state secondary battery sheet according to claim 16 .
19. An all-solid-state secondary battery, comprising, in sequence, a positive electrode active material layer, a solid electrolyte layer, and a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the solid electrolyte layer, and the negative electrode active material layer is a layer formed by the method for producing a sheet for an all-solid-state secondary battery according to claim 16 .
Citation Information
Patent Citations
Latex agglutination reaction measuring instrument
JP1987022066A
Catalyst carrier and production thereof
JP1990006856A
Four-wheel steering device
JP1991045473A
Distortion compensator
JP1993090844A
Assignment decision support system
JP1994004516A